Enhancing Cr(VI) bioreduction via Na+-stimulated intracellular energy metabolism and electron transfer using methane as electron donor - Lianfu Liang; Xiaofeng Fu; Yuqing Ding; Keying Liu; Rui Lin; Zhaojin Chen (Bioresource Technology, 2027)

A moderate microcurrent-density window enhances apparent CO2 fixation in Scenedesmus quadricauda - Ding Tan; Xin Li; Yunhui Li; Xingjia Fu; Wenyan Peng; Yun Liu (Bioresource Technology, 2027)

Exploring land consolidation solutions towards land use low-carbon transition: Evidence from Shenzhen, China - Haiyue Fu; Xinyi Chen; Penghui Jiang; Ding Fei; Chuan Liao (Land Use Policy, 2026)

Synergistic interfacial polymerization mediated by in-situ bubbles and surfactant for Mg2+/Li+ separation - Yi Yuan; Tong Wu; Lijuan Hu; Yajie Ding; Jianqiang Wang; Fu Liu (Desalination, 2026)

Engineered small extracellular vesicles–integrated multifunctional hydrogel reprograms the wound immune microenvironment for accelerated skin repair - Zhong Liu; Xinyu Zhu; Jun Cheng; Kewei Li; Yang Lou; Xiaopeng Sun; Yuhong Fan; Min Wang; Hui Qian; Yanbin Liu; Hua Ding; Song Guo; et al. (Chemical Engineering Journal, 2026)

Hierarchical multiscale topography encodes stem cell fate for endogenous zonal regeneration of the mandibular condyle - Jiarun Fu; Zhenrong Zhu; Chaoran Xue; Peiqi Wang; Xianglong Han; Ding Bai; Yujiang Fan; Yong Sun; Hongzhe Wang (Chemical Engineering Journal, 2026)

Hydrological sensitivity and carbon dynamics during the evolution of a crater lake peatland in Northeast China - Yuefeng Li; Bo Ding; Zhengyu Xia; Yuwen Fu; Jingjing Sun; Zicheng Yu (CATENA, 2026)

Multi-objective optimization based on reduced order model for VHTR design - Yuanyuan Fan; Han Zhang; Yongwang Ding; Yingjie Wu; Jiong Guo; Fu Li (Annals of Nuclear Energy, 2026)

PRWformer: An interpretable transformer-based model for probabilistic regional wave forecasting - Jie Ding; Delei Li; Jiagen Wang; Guangming Fu; Jichao Wang (Ocean Engineering, 2026)

Research on the synthesis and functional mechanism of hydroxyethyl cellulose modified dust suppressant with high anti-disturbance performance - Xuhan Ding; Qingyun Fu; Kai Wang; Zhenmin Luo; Huitian Peng; Zidong Zhao (Journal of Environmental Chemical Engineering, 2026)

Simultaneous adsorption of polystyrene nanoplastics and phosphorus by a magnetic calcium-modified biochar from aqueous solutions: Mechanism and applications - Jingran Fu; Zelong Wang; Sishi Liu; Maoyu Jiao; Shefeng Li; Siyu Ding; Yong Zhang; Xuli Li; Haijun Lu; Jing Zhang; Hongyu Wang (Journal of Environmental Chemical Engineering, 2026)

Prediction and descriptor-level interpretation of organic pollutant adsorption by activated carbon using machine learning - Chuan Ding; Tao Yuan; Rongbing Fu; Yueqing Xie; Zhemin Shen (Journal of Environmental Chemical Engineering, 2026)

Magnetite-assisted hydrothermal upgrading of polyvinyl chloride into an efficient heterogeneous Fenton catalyst - Ziyi Ding; Qingze Chen; Haoyang Fu; Fangxin Deng; Yanping Zhu; Yunfei Xi; Runliang Zhu (Journal of Environmental Chemical Engineering, 2026)

From structural limitations to modification strategies: A review of Prussian blue analogs electrode for efficient and stable capacitive deionization - Haiyun Ding; Zhiqiang Wu; Hao Zhou; He Ren; Hao Fu; Chuanyan Li; Jun Yang (Desalination, 2026)

Integrating enzymatic activity into highly emissive metal-organic frameworks derived from AIE ligands via horseradish peroxidase immobilization for dual-mode optical sensing - Zuyao Fu; Lingfeng Yang; Yuanyuan Zhang; Xuanjun Zhang; Jing Xie; Zhaoyang Ding (Chemical Engineering Journal, 2026)

Delphinidin Attenuates MAPK/AKT/STAT-2 and Induces Apoptotic Signaling in Human Nasopharyngeal Carcinoma Cells - In Vitro, In Silico and Pharmacological Analysis - Zhong-jia Ding; Yan Zhang; Shenbo Fu; Periyannan Velu; Annamalai Vijayalakshmi; Li Chen (Journal of Pharmaceutical Innovation, 2026)

Microscopic deformation mechanism of clay aggregates in view of the montmorillonite particles rearrangements under cyclic loading-unloading conditions - Zi-Yu Ding; Kai-Wen Tong; Yong-Gui Chen; Qiong Wang; Wen-Jie Dai; Xing-Guang Zhao; Chang-Fu Wei; Zhi-Jun Zhang (Applied Clay Science, 2026)

Pomegranate Peel Polyphenols-incorporated PVA/CMC Hydrogels for High-efficiency Removal of Methylene Blue from Aqueous Solutions - Qihua Zhou; Chenyang Wang; Simin Xu; Ziyi Duan; Tiantian Fu; Zhonghai Ding; Na Li (Water, Air, & Soil Pollution, 2026)

Nanoscale interfacial scaffold enables perovskite/silicon tandems with 34% efficiency and an open-circuit voltage over 2.01 V - Huimin Zhang; Qingshui Zheng; Hongbo Mo; Fu Zhang; Zhijie Rao; Linyu Ning; Yue Yin; Dongsheng Yang; Zheng Fang; Lei Ding; Yongcai He; Xixiang Xu; et al. (Science Bulletin, 2026)

Monte Carlo simulation-based assessment of carcinogenic heavy metal risk following Spartina alterniflora invasion in a subtropical estuarine wetland of China - Yulin Ding; Junjie Fu; Jiabing Li; Jie Tang; Rongrong Xie; Xiaodan Ma (Marine Pollution Bulletin, 2026)

Fermentation optimization and characterization of extracellular protein-associated antifungal components from Bacillus velezensis SY01 against Cytospora pyri - Shuaishuai Sha; Lingkai Xu; Canpeng Fu; Qiuyan Han; Jiaqi Ding; Beibei Feng; Yan Zhang; Sabinur Nurmemet; Pan Xie (Physiological and Molecular Plant Pathology, 2026)

Methanol vehicles with low PN23 emissions may still exhibit a potential SubPN23 particle burden - Jie Yao; Xinping Yang; Yitu Lai; Wanyou Luo; Hongfei Chen; Yunjing Wang; Xin Li; Mingliang Fu; Hang Yin; Yan Ding (Journal of Cleaner Production, 2026)

Insights from the genomic epidemiology of Vibrio parahaemolyticus in Nantong, China: A comparative genomics study of the classic ST3 and emerging ST2516 lineages - Ailong Huang; Yue Zhao; Shicheng Fu; Ende Zhong; Xiaolong Ding; Weibing Zhang; Jianjun Dai; Xiangkai Zhuge (Food Microbiology, 2026)

Low-cost and compact spring-type origami triboelectric nanogenerator for human kinetic energy harvesting and intelligent motion interaction - Zhelin Jin; Jie Cao; Rui Lei; Xu Han; Xianpeng Fu; Guoxu Liu; Haisheng Liu; Guanggui Cheng; Jianning Ding (Chemical Engineering Journal, 2026)

From bacterial template to green catalyst: Bio-fabrication of nanostructured nickel hydroxycarbonate for oxygen evolution via microbial mineralization - Feng Duan; Qichang Li; Li Xu; Haifang Wu; Ercai Pan; Wei Ding; Junhui Guo; Hang Ping; Liuyi Zhao; Hao Xie; Zhengyi Fu; Zhaoyong Zou (Chemical Engineering Journal, 2026)

Coordination-number-driven orbital tuning of yttrium single-atom catalysts for high-performance lithium-oxygen batteries - Mengyao Ding; Ximeng Sun; Yaning Fu; Shuangshuang Zuo; Zhen Feng; Tong Liu; Youcai Lu; Qingchao Liua (Chemical Engineering Journal, 2026)

Dust transport and impacts on secondary aerosol formation: Contrasting strong dust and floating dust events - Yanfen Lin; Qingyan Fu; Ziwei Liu; Zhijian Ding; Fan Yang; Ali Darvishi Boloorani; Cheng Huang; Juntao Huo; Qian Wang; Jia Chen; Qiongzhen Wang; Sabur F. Abdullaev; et al. (Atmospheric Environment, 2026)

Fracture development characteristics in carbonate reservoirs: insights from stress field simulation with a heterogeneous rock mechanics model and adaptive boundaries - Yao Wang; Wenlong Ding; Zhongliang Guo; Chenggang Li; Bochao Tang; Ziyou Zhang; Dong Fu; Rui Xia (Carbonates and Evaporites, 2026)

Clay mineral-facilitated azo dye biodecolorization: Mineral-specific electron transfer pathway and microbial community response - Ying Zhang; Wei Yin; Tian-Lei Zhao; Yi-Ming Ding; Ling-Xiong Yuan; Qi-Zhi Yao; Sheng-Quan Fu; Gen-Tao Zhou (Applied Clay Science, 2026)

Root oxygen governs dryland ecosystem stability - Dongliang Han; Lei Ding; Guolong Zhang; Jianping Huang; Li Fu; Ming Peng; Changyu Li; Xiaoyue Liu (Plant and Soil, 2026)

Rare Earth Element and Yttrium Fingerprints in Human Kidney Stones: Tracing Environmental Exposure and Pathological Mineralization Pathway - Di Wang; Guilin Han; Chaochun Fu; Wenqian Sun; Ziyang Ding; Haibo Li (Biological Trace Element Research, 2026)

Goal-oriented zoning for multifunctional land use: A multi-objective optimization approach to low-carbon transition in Shenzhen, China - Renrong Jiang; Haiyue Fu; Xinyi Chen; Mengmeng Cai; Penghui Jiang; Ding Fei; Chuan Liao (Sustainable Cities and Society, 2026)

Retraction notice to “Using organo–mineral complex material to prevent the migration of soil Cd and As into crops: An agricultural practice and chemical mechanism study” [Sci. Total Environ. 883 (2023) 163662] - Xuehao Zheng; Miaomiao Zhao; Lina Sun; Luge Rong; Bin Zhang; Fengjie Fan; Fangxi Zhang; Chengqiang Shu; Xiangyu Shi; Dan Zhao; Jianfeng Fu; Yuxin Zhang; et al. (Science of The Total Environment, 2026)

Multi-driver landslide disasters: distribution, formation, and mitigation - Shufeng Tian; Ningsheng Chen; Haitao Ding; Xiangyu Shao; Mengjie Jiao; Yongjian Li; Jiming Jin; Muhib Ullah Khan; Mingyang Wu; Xiaohu Chen; Bishal Gurung; Yongzhi Wang; et al. (Science Bulletin, 2026)

Comparative effects of sodium butyrate and Artemisia seed polysaccharide on performance, and glucagon-like peptide-2 in post-weaning Ordos fine wool sheep lambs - Ding Yang; Xinshuai Bing; Lu Jin; Chunhua Zhang; Xiangxiong Zhang; Shengli Li; Chula Sa; Le Fu; Wenting Li; Haizhou Sun (Small Ruminant Research, 2026)

Machine-learning-assisted process interpretation of composting time across composting systems involving multiple organic wastes: Key explanatory contributions of temperature evolution during the cooling–maturation phase - Xia Yao; Weilin Fu; Chun Song; Xueyan Zhang; Shiyu Lv; Yongzhen Ding; Feng Wang (Journal of Environmental Management, 2026)

A robust constrained-weight physics-informed neural network for forward and inverse analyses of mechanics - Kailin Ding; Yong Fu; Dan Fang (Computer Physics Communications, 2026)

Interfacial hydrogen bonding as a key driver for selective phenolic compounds removal via Mg(OH)2-catalyzed peroxymonosulfate activation - Yuan Ding; Jiachun Cao; Shiting Li; Hong Huang; Honggen Peng; Xiaoxiao Fu; Chunyang Nie; Zhimin Ao (Chemical Engineering Journal, 2026)

Rational design of phosphide catalyst for high-performance vanadium redox flow batteries - Yadong Xu; Hao Cheng; Mei Ding; Xiaolei Huang; Jian Xu; Su Yan; Hu Fu; Ming Yang; Chuankun Jia (Chemical Engineering Journal, 2026)

DEHA-induced hepatotoxicity identified from screening food packaging non-phthalate plasticizers: An integrative computational, multi-omics, and experimental exposure study - Yihao Zhu; Guixiang Fu; Zhijie Wang; Jin Ding; Jianrong Guo (Chemico-Biological Interactions, 2026)

Occupant-centric air conditioning control: Fusing multi-modal sensing and probabilistic model prediction - Wanyue Chen; Shengze Lu; Yan Ding; Dandan Yu; Jihui Yuan; Shaohui Chu; Sujuan Fu (Building and Environment, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Numerical Investigation of Time-Dependent Deformation and Fracture Evolution in Flawed Sandstone - Teng-Fei Fu; Zhu-Guang Wang; Bi-Bi Qiao; Ya-Tao Li; Tao Ding; Chong-Feng Chen (Geotechnical and Geological Engineering, 2026)

Simple sequence repeat (SSR) marker-based genetic diversity and population structure of large-leaf tea germplasm across four major tea-producing regions of Yunnan, China - Qihuan Ding; Wuxiang Fu; Ning Chi; Jianmei Su; Shanshan Wu; Zhanxia Ma (Genetic Resources and Crop Evolution, 2026)

Baseline mathematical aptitude attenuates group differences in posterior P300 during arithmetic verification in high school athletes - Chia-Chi Hsu; Hui-Yu Hsu; Tsu-Jen Ding; Chen-Yu Yao; Zai-Fu Yao (Experimental Brain Research, 2026)

Dimethyl fumarate ameliorates quinolinic acid-induced ageing and neurodegeneration in Caenorhabditis elegans - Yi Sun; Ke Zhou; Jiaorong Cui; Haoxuan Ding; Iqra Shareef; Liuliang Du; Zhen Shi; Linlin Fu; Fenfen Sun; Zuobin Zhu; Wei Pan (Biogerontology, 2026)

Population Decline, Inbreeding and Hybridization Shape the Genetic Vulnerability of a Critically Endangered Seabird - Guoling Chen; Chenqing Zheng; Lanhui Peng; Hongzhou Lin; Feng Dong; Shou‐Hsien Li; Yiwei Lu; Siyu Wang; Zhongyong Fan; Yinan Fu; Peng Ding; Jian Zhang; et al. (Molecular Ecology, 2026)
Many endangered species have been rescued from the brink of extinction, yet their long‐term viability remains uncertain due to the prolonged genetic consequences of severe bottlenecks. In particular, the combined effects of inbreeding and hybridization with closely related species remain poorly understood. Using a comparative conservation genomic framework, we investigated these issues in the Chinese crested tern ( Thalasseus bernsteini ), a critically endangered seabird once presumed extinct but which has increased to approximately 100 individuals over the past two decades and its close relative, the great crested tern ( T. bergii ). We demonstrate that the Chinese crested tern has experienced ongoing genetic erosion. Its prolonged population decline has intensified genetic drift and reduced the efficiency of purifying selection, resulting in genome‐wide accumulation of highly deleterious mutations. Highly inbred individuals also carry significantly more homozygous deleterious mutations than less inbred individuals. In both species, runs of homozygosity (ROH) show a relative enrichment of moderately and weakly deleterious mutations. Even more concerning, we found an enrichment of moderately and weakly deleterious mutations in putatively introgressed regions in both species, suggesting that occasional hybridization may have facilitated the spread of deleterious variants and could potentially compromise long‐term fitness. These findings highlight that severe bottlenecks have lasting genomic consequences and that both inbreeding and hybridization can increase the genetic vulnerability of small populations—underscoring the importance of management strategies that promote population growth and sustained genetic monitoring.

Dynamic source apportionment of heavy metals in Bohai Bay sediments using a temporally hierarchical PCA-APCS-HBM model - Qiulian Wang; Long Han; Tong Han; Zhenchao Fu; Zeli Li; Han Ding (Marine Pollution Bulletin, 2026)

Regional-scale prediction and assessment of soil organic matter content in the Yuanmou Dry-Hot Valley, Southwest China, using satellite-derived phenological time series and deep learning - Dengdeng Ding; Jida Yang; Sihe Deng; Hongye Zhu; Zhengbo Ma; Chengxiu Fu; Junlang Deng; Dingyun Zhao; Zhen Long; Xiaoyan Wang; Peiwen Yang; Qibin Chen; et al. (Environmental Monitoring and Assessment, 2026)

Microbiome immune crosstalk in Sjögren’s syndrome: mechanistic insights and translational perspectives - Xiang-Yu Qi; Meng-Yuan Wang; Tian-Chi Wei; Fu-Biao Shao; Shu-Han Liu; Ding Han; Jing-Wen Cheng; Yun-He Zhao; Lei Shi; Jing Luo; Ting Cheng; Sheng-Xiao Zhang (Immunologic Research, 2026)

Targeted biofilm inhibition and gene expression to study the synergistic antibacterial mechanism of lauric acid and citral against Listeria monocytogenes - Menglong Liu; Haiyan Ding; Xiaoping Fu; Qiaoli Xue; Yongjin Hu (Food Research International, 2026)

The role of oxygen vacancies and metallic Ru in regulating oxide pathway mechanism for acidic water electrolysis - Dinghua Zhou; Yutian Ding; Tao Song; Jiayi Wu; Zengyu Su; Zhiyong Fang; Muhammad Bilal Hussain; Peili Zhang; Xian-Zhu Fu; Shao-Qing Liu; Shuwen Wu; Jing-Li Luo (Chemical Engineering Journal, 2026)

Dye displacement on a GO-like cationic porphyrin polymer for heparin sensing and quality control - Yusheng Fan; Yanlin Fu; Chunfei Bao; Weihua Zhang; Yubin Ding (Analytica Chimica Acta, 2026)

Time Tunnel to the past: Generative AI as an approach for visualizing ancient Chinese auroral records - Jia Wang; Libo Fu; Zhengkang Duan; Yi Li; Linfeng Wang; Boyi Wang; Ding Yuan (Advances in Space Research, 2026)

Corrigendum to “Rapid detection of Streptococcus agalactiae in tilapia using RPA-PfAgo detection systems” [Aquaculture, Volume 619, 30 May 2026, 743875] - Xiaojing Xia; Jiahui Fu; Qianlei Zhu; Kexin Wang; Jingjing Li; Xujie Zhao; Lei Wang; Yanwei Li; Chengshui Liao; Yimin Wang; Yueyu Bai; Yilin Bai; et al. (Aquaculture, 2026)

Effects of microplastics on carbon and nitrogen cycling in coastal wetlands: A critical meta-analysis - Feng Yuan; Hongyu Chen; Yue Xue; Yongcheng Ding; Qiujun An; Zhian Hu; Yifei Qiu; Jianguo Tao; Jin Luo; Guanghe Fu; Teng Wang; Xinqing Zou (Water Research, 2026)

Polystyrene nanoplastics disrupt iron homeostasis by promoting FPN1 ubiquitination in GC-2spd(ts) cells - Xinru Cui; Yitong Shang; Liyang Ding; Zhen Zhang; Yu Deng; Tengjiao He; Bo Xu; Xufeng Fu; Xing Du; Hang Han (Toxicology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Genome-wide analysis of the papaya bZIP gene family identifies CpbZIP52 as a key regulator of fruit postharvest ripening - Meiling Ding; Shanni Cao; Meng Zeng; Min Zhang; Hongya Tang; Xiaochun Chen; Xianqi Fu; Sicheng Bai; Min Yang; Kaidong Liu (Plant Science, 2026)

Heat-induced methylglyoxal impairs plant thermotolerance by repressing cpHSC70-1-mediated chloroplast protein import via post-translational modification - Feng Ding; Yue-Xin Liu; Shi-Hang Fan; Wei Hua; Ying-Tang Lu; Zheng-Wei Fu (Molecular Plant, 2026)

Internal recirculation enhances sulfide-driven autotrophic denitrification in nitrate-rich saline wastewater under coupled salinity and sulfide stress - Jiazheng Ding; Jiahao Liang; Fu Wen; Qinghong Wang; Changgang Li; Wenyu Xie; Ziwei Lv; Dingyuan Chen; Ximin Lai; Xiaoqing Chen; Dehao Li (Journal of Environmental Chemical Engineering, 2026)

A regime shift in great lakes nearshore total freeboard dynamics driven by synchronized climate patterns - Yihang Ding; C.K. Shum; Michael Bevis; Shuaiying Wu; Shengdao Wang; Yuan Xue; Xudong Fu (Earth and Planetary Science Letters, 2026)

Nanostructured interfaces in thermoplastic/thermosetting polymer blends for enhanced high-temperature capacitive energy storage - Chengjun Fu; Jingyuan Yang; Hao Chen; Ding Ai; Ziyu Lv; Yongbiao Zhai; Shuangwu Huang; Qiyan Zhang (Chemical Engineering Journal, 2026)

λ-Carrageenan inhibits African swine fever virus infection potentially through its interaction with the viral envelope protein CD2v - Kun Han; Limeng Sun; Can Jin; Siqi Wan; Caiqin Cao; Yulu Yue; Man Lu; Xiaotong Wang; Yi Zheng; Hailong Liu; Yilin Guo; Dagang Tao; et al. (Carbohydrate Polymers, 2026)

A Stochastic Dynamic Rubinstein Bargaining Framework for Transregional Water Resources Allocation Considering Inflow Forecasting Errors - Jisi Fu; Tong Ding; Yong Zheng; Bin Xu; Lianghui Li; Feng Yan; Zhongzheng He (Water Resources Management, 2026)

Hydrodynamic impacts of floating-raft aquaculture in the northern yellow sea: modeling and field experiments - Xiaomeng Fu; Jie Tian; Ming Li; Yuan Zhang; Junru Guo; Jun Song; Yang Ding; Congcong Bi (Ocean Dynamics, 2026)

Study on the synergistic efficacy and mechanism of CD24 silencing combined with trastuzumab in HER2-positive breast cancer - Yi Lu; Xinglu Zhou; Yue Gao; Zi Zhu; Bao Deng; Wubin Lv; Zhenkun Fu; He Ding; Lei Zhong (Journal of Molecular Histology, 2026)

Rapid Bølling-Allerød Interstadial deglaciation in the southeastern Tibetan Plateau: Evidence from 10Be chronology of the glacially polished bedrock surfaces in the Haizishan Plateau - Jiangtao Wang; Weijian Zhou; Guocheng Dong; Feng Xian; Yunchong Fu; Li Zhang; Pengkai Ding (Journal of Geographical Sciences, 2026)

Cuproptosis: a novel mechanism and 3PM-oriented therapeutic strategy for cancer - Ding Yang; Wei-Ting Hu; Miao Li; Fang-Qing Shen; Hao-Yu Wang; Jin-Ying Ye; Fu-Lu Ren; Yun Wang (EPMA Journal, 2026)

An MPC-ECMS Integrated Energy Management Strategy for Shipboard Gas Turbine–Photovoltaic–Hybrid Energy Storage Power Systems - Zhicheng Ye; Zemin Ding; Jinzhou Fu; Ge Xia (Journal of Marine Science and Engineering, 2026)
A real-time optimized model predictive control–equivalent consumption minimization strategy (MPC-ECMS) is proposed for the energy management of shipboard gas turbine–photovoltaic hybrid energy storage (GT-PV-HESS) power systems. Different from conventional MPC-ECMS methods that only adopt single-level SOC-based feedback regulation, the strategy aims to overcome the limitations of conventional methods, including the poor adaptability of rule-based strategies and the lack of foresight in traditional ECMS, which cannot achieve simultaneous improvements in fuel economy, generation efficiency, and battery lifespan while maintaining system stability under dynamic operating conditions. The proposed strategy integrates the forward-looking optimization ability of MPC and the real-time decision-making advantage of ECMS. MPC is used to predict short-term load and photovoltaic power and identify operating modes, and a two-level equivalent factor adjustment mechanism is designed based on predicted conditions and battery state of charge (SOC). The optimized factor is applied in ECMS to achieve optimal power allocation between the gas turbine and battery under system constraints, while the supercapacitor implements power secondary correction to suppress bus voltage fluctuations caused by gas turbine operation. The architectural novelty lies in the two-level coordination mechanism and the marine-oriented hybrid energy storage cooperation. Simulation studies are conducted on the MATLAB/Simulink R2021b platform, and the results validate that it yields superior performance to the rule-based control and traditional ECMS under typical ship operating conditions. It increases gas turbine efficiency to 15.62% (0.47% and 6.24% higher than the two conventional methods). Over the 120 s simulation period, the proposed strategy reduces total fuel consumption to 1.049 kg, which is lower than 1.054 kg for the rule-based strategy and 1.192 kg for conventional ECMS. The battery SOC fluctuation is restricted to only 3.89%. The maximum DC bus voltage fluctuation rate is controlled within 3.28%, which meets the stability requirements of shipboard DC microgrids. The proposed strategy achieves a comprehensive and superior balance among fuel economy, power generation efficiency, and battery life while ensuring stable system operation under all working conditions. This two-level MPC-ECMS framework provides a high-performance and practically feasible energy management solution for shipboard hybrid power systems.

Experimental study on the effects of fluid viscosity on the depositional patterns of filling material - Zukun Wang; Lei Song; Junquan Wang; Zhuangcai Tian; Yameng He; Linjun Wu; Luyun Ding; Hao Fu (Marine Georesources & Geotechnology, 2026)

Rapid detection of Streptococcus agalactiae in tilapia using RPA-PfAgo detection systems - Xiaojing Xia; Jiahui Fu; Qianlei Zhu; Kexin Wang; Jingjing Li; Xujie Zhao; Lei Wang; Yanwei Li; Chengshui Liao; Yimin Wang; Yueyu Bai; Yilin Bai; et al. (Aquaculture, 2026)

Learning to follow: An end-to-end deep learning approach for vision-based vessel control - Shigan Ding; Mao Zheng; Nan Hai; Xiumin Chu; Bowen Lin; Tianyue Zou; Kehao Zhang; Wubin Hua; Lingyu Fu (Ocean Engineering, 2026)

BSMT1, SABP3, and MAT2 assemble into a ternary complex vital for methyl salicylate biosynthesis and airborne defense - Baolong Sun; Wei Yang; Luyue Shang; Haimiao Zhang; Yang Liu; Lansu Wei; Yihan Zhang; Boyu Zhao; Yong Wang; Ziyi Yin; Chongchong Lu; Haipeng Zhao; et al. (Molecular Plant, 2026)

Large-scale gold incorporation in bulk pyrite mediated by arsenic - Zi-Yue Gao; Kun-Feng Qiu; Razvan Caracas; Bing-Cheng Luo; Xin Liu; Zheng-Yu Long; Deng-Yang He; Jia-Nan Fu; Mei-Jing Xu; Hao-Cheng Yu; Zheng-Jiang Ding; Jun Deng (Geochimica et Cosmochimica Acta, 2026)

Volatile metabolomics and Metaproteomics reveal key flavor formation mechanisms in mixed-culture fermented Rice slurry - Yuanyuan Ren; Yingjie Lei; Rui He; Jin Fu; Ding Ma; Geng Zhong (Food Research International, 2026)

A framework approach for analyzing water transformation characteristics of typical watersheds in arid zones during irrigation periods - Jingming Liu; Jianli Ding; Jinjie Wang; Zhe Zhang; Jie Zou; Zipeng Zhang; Xiao Wang; Zan Fu; Xiangyu Ge (Environmental Modelling & Software, 2026)

Simulation of soil-rock mixture fluidized landslide dynamics using the 3D-SPH-DEM method enhanced by reorientation and spherical cap cutting algorithms - Wendu Xie; Zheng Han; Gonghui Wang; Guangqi Chen; Bin Su; Yange Li; Haohui Ding; Bangjie Fu; Changli Li (Computers and Geotechnics, 2026)

Effects of different biomass amendments on the biogeochemical processes of arsenic transformation during tailings soil leaching: Insights into dissolved organic matter and arsenic-functional genes - Jun Zeng; Hong Wang; Qing Hu; Na Liu; Bowen Hu; Renchuan Fu; Longzhen Ding (Chemical Engineering Journal, 2026)

Map-based spatial perspective taking reveals frontal late negativity loss and posterior delta gain in mild cognitive impairment - Tsu-Jen Ding; Hui-Yu Hsu; Jui-Cheng Chen; Chen-Yu Yao; Zai-Fu Yao; Tzuhui Angie Tseng (GeroScience, 2026)

Excitation mechanisms and vibration response of a horizontal elbow in gas-liquid two-phase flow - Yitong Fu; Xiang Li; Bolun Ding; Yiran Duan; Lin Ding (Ocean Engineering, 2026)

Three-dimensional identification and attribution of flash and slow agricultural droughts in the North China Plain - Yiding Ding; Haishen Lü; Yonghua Zhu; Ali Levent Yagci; Qiqi Gou; Jianbin Su; Junxiang Cheng; Yiling Yao; Wen Liu; Jiaying Liu; Yinghao Fu (Journal of Hydrology, 2026)

Damkohler number effect on nanoparticle seeded blended hydrogen flames - Rahat Mollick; Chenrui Ma; Jingwen Fu; Yun Huang; Jianan Zhang; Hongtao Ding; Albert Ratner (Fuel, 2026)

Metabolomic investigation of flavor and metabolite evolutions in the submerged fermentation of miiuy croaker (Miichthys miiuy) surimi induced by Monascus purpureus - Wenjia He; Min Wang; Tao Zhou; Sufang Fu; Kang Chen; Yuting Ding; Xuxia Zhou (Food Chemistry, 2026)

Harnessing Machine learning to quantify ecosystem services in coastal Wetlands: A case study of the Bohai economic Rim - Ting Lu; Ya Ping Wang; Jiyuan Jin; Shibing Zhu; Jianhua Gao; Hu Ding; Qinglong Wu; Fu Wang; Chao Gao (Ecosystem Services, 2026)

Stromal reprogramming-primed nanofiber enhances immune activation for melanoma suppression - Mingyang Li; Junhao Liang; Linhan Ding; Wenjing Dong; Rongrong Li; Baotong Xu; Yuhan Lian; Yuhan Cui; Dongsheng Zhang; Guangyi Liu; Yulin Zhang; Xiao Fu (Chemical Engineering Journal, 2026)

Time-dependent dynamics of starch structure, functionality and quality in rice noodles during inoculated fermentation - Yuanyuan Ren; Yingjie Lei; Rui He; Jin Fu; Ding Ma; Geng Zhong (Carbohydrate Polymers, 2026)

Effects of Lactobacillus Acidophilus Mediated Improvement of Intestinal Barrier in Mice with Autism - Yong Song; Jia Shi; XiaoYi Fu; Dan Fu; Li Xu; WeiMei Liu; JingJing Cao; YaoCheng Ding; ShuPeng Huang; Lin Zhou; Kai Qian (Probiotics and Antimicrobial Proteins, 2026)

Aridity and grazing regulate the effects of grassland biodiversity on the trade-offs and synergies among ecosystem functions in drylands - Weiling Niu; Jingyi Ding; Wenwu Zhao; Jing Wang; Wenzhu Tu; Yue Liu; Bojie Fu (Agriculture, Ecosystems & Environment, 2026)

Unsteady Cavitation Flow Characteristics Around the Clark-Y Hydrofoil Cascade - Wenchun Bao; Yichen Zhu; Yule Ding; Mindi Zhang; Fu Chen (Journal of Marine Science and Engineering, 2026)
Both experimental and numerical studies were conducted to obtain the influence laws of complex cavitation flow structures around a Clark-Y hydrofoil cascade. The similarities and differences in cavitation flow characteristics between the cascade and single hydrofoil were compared to analyze the influence of the cascade configuration on the flow field structure. This study focuses on the correlations among cavity development, lift–drag characteristics, and flow field features of the hydrofoil cascade. The results indicate significant differences in the development degree and history of cavities at different positions within the cascade. The top layer of the cascade exhibits a cavitation pattern similar to a single hydrofoil; both generate large-scale shedding vortices at the trailing edge. In contrast, the cavitation phenomena in the middle and bottom layers are similar to each other. The suction side of the top-layer hydrofoil influences the middle and bottom layers. This interaction suppresses the formation of large-scale shedding bubbles and subsequently hinders re-entrant shocks. Furthermore, the cavities in the middle and bottom layers develop more rapidly, causing the dynamic characteristics of the cascade to reach their peak values earlier. At the cloud cavitation stage, the Strouhal numbers (St) for cavity collapse on the top and bottom hydrofoils are approximately 0.2 and 0.3, respectively. The St for the middle hydrofoil exhibits an intermediate value that decreases from 0.3 to 0.2 as the cavitation number (σ) declines, reflecting a transitional characteristic modulated by the cascade structure. Compared to a single hydrofoil, the cascade is subject to the combined effects of the three-layer hydrofoils; consequently, its lift is approximately three times that of a single hydrofoil, though its drag also increases threefold. The lift variation pattern of the top-layer hydrofoil in the cascade is similar to that of a single hydrofoil. In contrast, the middle-layer hydrofoil exhibits a more complex lift evolution, as both its suction and pressure sides are significantly influenced by the surrounding cascade structure. For the bottom-layer hydrofoil, the lift remains relatively low because no cavities are generated on its surface. Lift fluctuation frequencies that aligned with cavity collapse were identified at 45 Hz, 70 Hz, and 50 Hz across the top, middle, and bottom cascade layers, respectively.

Three cytochrome P450 genes contribute to chlorantraniliprole resistance in Phthorimaea absoluta with fitness costs - Lun Li; Zunzun Jia; Kaiyun Fu; Xinhua Ding; Jiahe Wu; Xiaowu Wang; Tursun. Ahmat; Weihua Jiang; Yangyang Yan; Xinyue Dong; Xiaoqin Ye; Yawen Li; et al. (Pesticide Biochemistry and Physiology, 2026)

Instantaneous ammonia emissions prediction for light-duty gasoline vehicles using ensemble learning - Jing Wang; Lei Zu; Han Jiang; Huayang Zhao; Haiguang Zhao; Mingliang Fu; Yitu Lai; Yunjing Wang; Sheng Su; Hefeng Zhang; Yan Ding (Fuel, 2026)

Characteristics and expression of the BES1 transcription factors family in foxtail millet (Setaria italica) reveal its potential roles in drought stress responses - Xueyan Xia; Xiaohong Fu; Yu Zhao; Jihan Cui; Nuoya Xiao; Meihong Huang; Yiwei Lu; Jingxin Wang; Cheng Chu; Shunguo Li; Mingwei Ding (Cereal Research Communications, 2026)

A novel electrostatic-assisted airflow pollination end-effector for kiwifruit flowers with optimized charging and spraying parameters - Yusong Ding; Leilei He; Juncai Huang; Xin Wei; Yufei Shi; Hin Lim; Spyros Fountas; Shaojin Wang; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2026)

Multi-media distribution, partitioning, and risks of tire additives and their transformation products in coastal waters of China - Chao Liu; Shuang Lu; Min Lv; Longwen Fu; Mingsan Man; Yize Du; Jing Ding; Wei Liu; Lingxin Chen (Marine Pollution Bulletin, 2026)

Enhancing urban bird corridor identification by integrating three-dimensional factors: A validation with citizen science data - Yaling Huang; Ziru Chen; Yankai Huang; Tongyan Li; Chengyu Ran; Ying Lin; Yinghong Ding; Deng Pan; Yuxiang Lan; Jiali Jin; Zhipeng Zhu; Weicong Fu (Urban Forestry & Urban Greening, 2026)

Identification of novel B-cell neutralizing epitopes in goose Astrovirus type 2 - Shichao Yuan; Rui Fu; Bangfeng Xu; Wenqing Wang; Huamao Ding; Xue Pan; Chunxiu Yuan; Qinfang Liu; Zhifei Zhang; Qiaoyang Teng; Xiaona Shi; Minghao Yan; et al. (Veterinary Microbiology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Enhancing aerobic granulation for recalcitrant wastewater treatment in continuous-flow systems via zonal retrofit and cyclic alternating aeration-sludge recirculation - Xiaoqing Chen; Jiahao Liang; Jiazheng Ding; Qinghong Wang; Changgang Li; Wenyu Xie; Fu Wen; Ziwei Lv; Xuan Sun; Chunmao Chen; Dehao Li; Jing Liu (Journal of Water Process Engineering, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Enhancing anaerobic digestion of sulfate-containing organic wastewater through an innovative integration of nitrate addition and microaeration - Jiazheng Ding; Jiahao Liang; Changgang Li; Qinghong Wang; Wenyu Xie; Xiang Tan; Chunmao Chen; Dehao Li; Yali Zhan; Xiaoqing Chen; Wen Fu (Journal of Cleaner Production, 2026)

Quantifying internal phosphorus loading based on high-resolution porewater monitoring and machine learning in the eutrophic Lake Taihu - Youzi Gong; Yan Wang; Yi Zhang; Shi Fu; Shuaishuai Gao; Askar Akida; Ziyi Xiong; Shuhang Wang; Xia Jiang; Xianfang Fan; Musong Chen; Yongjiu Cai; et al. (Journal of Environmental Sciences, 2026)

Yttrium and silicon co-doped carbon nanoparticles: multi-faceted collaborative enhancement of electroluminescence signals and aptasensor for high sensitivity detection of aflatoxin B1 - Yuqin Yang; Li Song; Yilan Ding; Shuchun Bu; Yingzi Fu; Ruo Yuan; Yaqin Chai (Food Chemistry, 2026)

Spectrum-compatible artificial accelerograms via conditional variational autoencoder with generative adversarial networks - Xiaohu Hu; Su Chen; Yi Ding; Lei Fu; Xiaojun Li (Engineering Structures, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Structural and compositional variations in the intact pulse cotyledon cells determine the in vitro digestion kinetics of starch - Shahid Ahmed Junejo; Junwen Luo; Li Ding; Xiong Fu; Savitree Ratanasumawong; Qiang Huang; Bin Zhang (Carbohydrate Polymers, 2026)

Manganese cycle-mediated synchronous bacteria-algae/anammox coupled denitrification system under low-temperature conditions: Performance and mechanisms - Peng-fei Yu; Dian-lin Jiang; Ding Wang; Xing-guan Ma; Jun-Li; Li-yao Han; Ao Wang; Yu-bo Fu; Xing Jin (Bioresource Technology, 2026)

Wheat-associated Antagonistic Bacteria Exerts Biocontrol Activity Against Fungal Growth and Deoxynivalenol Production in Fusarium Graminearum - Ziting Ding; Wenjing Fu; Ping Zhou; Tao Gao; Zhitian Zheng (Current Microbiology, 2026)

Mineral Association and Microbial Processing Jointly Prolong Carbon Turnover in Coastal Wetlands - Yuan Li; Chuancheng Fu; Peng Ren; Zhaoliang Song; Lingfang Ni; Ting Wang; Changxun Yu; Ji Chen; Laodong Guo; Iain P. Hartley; Ding He; Xiaoguang Ouyang; et al. (Global Change Biology, 2026)
Coastal margins are critical sites for carbon (C) sequestration, yet the mechanisms stabilizing preaged, allochthonous C (externally‐derived biospheric C) in these environments remain poorly understood. Specifically, the interplay between mineral association and microbial processing represents a significant knowledge gap. Here, we investigated C sequestration mechanisms in Chinese mangrove and saltmarsh soils by analyzing topsoils and cores across 36 sites spanning a 20‐degree latitudinal transect. We found that saltmarshes, characterized by high mineral accretion and lower relative autochthonous C accumulation, exhibited significantly longer soil organic C (SOC) turnover times than mangroves (topsoils: ~2200 vs. ~500 years, respectively). This difference corresponded to higher proportions of preaged (~50%) and petrogenic (rock‐derived; ~20%) SOC in saltmarshes. Linear mixed‐effects models (LMM) confirmed that proxies for mineral protection (e.g., Al/Si) and advanced decomposition (lignin oxidation) were robust, positive predictors of turnover time across the latitudinal gradient. Further structural equation modeling (SEM) indicated a depth‐dependent shift in drivers. In surface soils, microbial necromass accumulation was a significant predictor of C turnover (coefficient = 0.36). However, at depth (1 m), the degree of lignin degradation emerged as the primary predictor of multi‐millennial C persistence (coefficient = 0.45). These results suggest a joint regulation mechanism whereby microbial processing transforms organic matter into stable forms that are subsequently protected by minerals. This mechanism effectively sequesters old, allochthonous C, challenging the paradigm that blue C storage is dominated solely by recent biomass and necessitating a reevaluation of coastal C management frameworks.

Genomic inbreeding evaluation and its effects on phenotype and selection accuracy of resistance to Edwardsiella tarda in Turbot (Scophthalmus maximus) - Ding Lyu; Qiang Fu; Mianyu Liu; Yulong Hu; Guanzheng Lyu; Weiji Wang (Aquaculture, 2026)

The novel model INEDM and two traditional models for estimating the carrying capacity of Hong Kong oyster (Crassostrea hongkongensis) in two aquaculture systems in Guangdong Province of China [Aquaculture Volume 609, July 2025.] - Xing-Chi Guo; Wen-Ding Liu; Xiao-Yan Ye; Ting-Long Hou; Yao-Wu Fu; Qi-Zhong Zhang (Aquaculture, 2026)

Innovative cascade reservoir scheduling to ensure water environmental safety of drinking water source area - Zhen Liu; Yikun Xu; Yongrui Fu; Jiaxuan Gao; Han Wang; Xiaowen Ding (Process Safety and Environmental Protection, 2026)

Multi-target inhibition of Microcystis by allelochemicals: Linking oxidative stress, photosynthetic collapse, and toxin suppression - Yao Yue; Teer Wen; Chuqiao Li; Yunfei He; Juyang Fu; Xuetong Qu; Jiafeng Ding; Hangjun Zhang (Journal of Hazardous Materials, 2026)

Do biodegradable plastic residues pose lower ecological risks to crops than conventional plastic residues? A meta-analytic comparison - Feng Yuan; Teng Wang; Hongyu Chen; Yongcheng Ding; Jianguo Tao; Yue Xue; Linjie Zhang; Haiyan Lin; Baojie Li; Yifei Qiu; Guanghe Fu; Xinqing Zou (Journal of Hazardous Materials, 2026)

Nickel isotopic evidence for potential deep magmatic sulfide ore bodies in orogenic settings - Peng-Yi Li; Shui-Jiong Wang; Fu-Ping Pei; Guan-Wen Yu; Bing-Qian Ding; Zi-Cheng Guan; Kai Song; Wen-Liang Xu (Geochimica et Cosmochimica Acta, 2026)

Interaction mechanisms of short-chain fluorocarbon surfactants on metamorphic coal dust treatment: Insights from macroscopic experiments and molecular dynamics simulations - Zhenmin Luo; Kai Wang; Xuhan Ding; Yong Yang; Qingyun Fu; Tianting Wang; Yuting Wang; Tao Wang; Jingxiang Hao; Haipeng Jiang (Fuel, 2026)

Effects of galactomannan on the quality and component structure of hot-dry noodles during freeze-thaw cycles - Liuyu Wan; Yang Fu; Zhonghua Yuan; Peili Lin; Nian Cheng; Shensheng Xiao; Wenping Ding; Xuedong Wang (Food Chemistry, 2026)

Pseudocapacitive Fe4N nanoparticles encapsulated within interconnected graphene cavities as efficient binder-free capacitive deionization anodes - Liyan Liu; Shaojie You; Wenjun Fu; Jihui Cao; Zhengxin Ding; Chao Xu (Desalination, 2026)

TensorSymmetry: a package to get symmetry-adapted tensors disentangling spin-orbit coupling effect and establishing analytical relationship with magnetic order - Rui-Chun Xiao; Yuanjun Jin; Zhi-Fan Zhang; Zi-Hao Feng; Ding-Fu Shao; Mingliang Tian (Computer Physics Communications, 2026)

Modulating NLRP3 Inflammasome Activity and Enhancing Cortical Synaptic Plasticity: Nanoparticulate Hydrogen’s Role in Relief of Post-traumatic Anxiety-like Behaviors in Rats - Lanxia Wu; Congwen Yang; Yiqin Ding; Xinru Liu; Hao Sun; Xue Li; Yining Lu; Lifen Liu; Qingyang Fu; Min Li; Yingshuai Wang; Yuehan Zhao; et al. (Molecular Neurobiology, 2026)

Analysis of effects of shellfish harvesting methods on digging shovel performance using the discrete element method - Shancan Fu; Shaolei Zhang; Lei Yang; Haiyun Wu; Zhengliang Ding; Tao Zhang; Yongcheng Jiang (Aquacultural Engineering, 2026)

An Advanced Fluorescent Molecularly Imprinted Sensor Based on Carbon Quantum Dots for Highly Sensitive Detection of 6-Mercaptopurine - Yinuo Liu; Zhengyuan Dai; Ying Wang; Shanshan Fu; Li Li; Yaping Ding (Journal of Fluorescence, 2025)

Metagenomic insight into the ecological effects of the plastisphere in coastal salt marshes - Feng Yuan; Junjie Wang; Ming Lu; Qihang Liao; Teng Wang; Yue Xue; Hongyu Chen; Yongcheng Ding; Guanghe Fu; Penghua Qiu; Xinqing Zou (Marine Pollution Bulletin, 2025)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

High-resolution spatial mapping of electrocorticographic activities with NeuroCam: a 4096-channel, multiplexed flexible thin-film transistor array - Yang Xie; Zepeng Zhang; Muyang Liu; Jinhong Guo; Miao Xu; Lei Zhou; Lei Zhang; Lihao Yao; Xiaolin Zhou; Zhengwei Hu; Liang Ma; Xiaojian Li; et al. (Science Bulletin, 2025)

PcUGT203E1 and PcUGT203B2 are involved in abamectin susceptibility in Panonychus citri - Yuchao Shen; Zehao Huang; Sichen Li; Wanfu Yao; Liu Liu; Shijun Fu; Shijiang Yu; Binbin Shao; Lili Ding; Qiqi Yang; Yang Li; Shaohui Zhang; et al. (Pesticide Biochemistry and Physiology, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

The attribution of subseasonal extreme precipitation in arid and semi-arid regions based on extended convergent cross mapping - Tingxing Chen; Attilio Castellarin; Yonghua Zhu; Haishen Lü; Andrea Magnini; Yinghao Fu; Yuan Li; Yu Lin; Zhenzhou Ding; Jiaying Liu (Journal of Hydrology, 2025)

Formaldehyde emissions from light-duty gasoline vehicles: Emission characteristics and future trends - Junchao Zhao; Xinping Yang; Zhining Zhang; Mingliang Fu; Yunjing Wang; Songdi Liao; Zhipeng Tu; Lijuan Qi; Xiaotong Wang; Zhenyu Luo; Hang Yin; Yan Ding (Journal of Hazardous Materials, 2025)

Differential response of anode and cathode in dual chamber microbial electrochemical system for treatment of antibiotic and microplastic composite polluted wastewater - Nuchao Xu; Chuanning Xiao; Huilin Yin; Yun Fan; Zhenyu Ding; Ning Sun; Quankai Fu; Aizhong Ding (Journal of Cleaner Production, 2025)

Unraveling the diverse grazing effects: Examining the variations in spatial patterns of soil microbial diversity across dimensions, Kingdoms, and depths in Tibetan grasslands - Tianyu Li; Haorui Zhang; Rang Ding; Gang Fu (Global and Planetary Change, 2025)

Consolidation analysis of staged-filled soil slurry with combined grid-horizontal and vertical drains system under vacuum preloading - Ding-Bao Song; Yu Pan; Jian-Hua Yin; Zhen-Yu Yin; He-Fu Pu (Geotextiles and Geomembranes, 2025)

Deciphering microbial and metabolite dynamics in rice noodle fermentation: A metagenomic and untargeted metabolomic approach - Yuanyuan Ren; Yuhang Li; Yingjie Lei; Rui He; Jin Fu; Ding Ma; Geng Zhong (Food Chemistry, 2025)

UV-B-induced RrMYB62-RrOSC4 regulatory module promotes pentacyclic triterpenoid biosynthesis in Rosa roxburghii Tratt.: A molecular mechanism to enhancing functional phytochemicals - Di Xin; Xue Wu; Jiandong Wang; Huaming An; Yunkun Ding; Jiyu Du; Chengdong Nie; Yujie Fu (Food Bioscience, 2025)

Multifunctional metal-organic framework based nanozymes: From synthesis to fluorescent and colorimetric dual mode sensing in food safety - Bakhtawar Shafique; Zuyao Fu; Hao Wang; Jing Xie; Zhaoyang Ding (Food Control, 2025)

Comprehensive analysis and risk assessment of pyrethroid pesticide residues in the market-sold fruits from the Beijing-Tianjin-Hebei region, China - Jiangxue Dong; Qianwen Wu; Haoyun Yuan; Chenyu Ding; Zhaowei Fu; Zhuohan Liu; Hongyuan Yan; Xin Liu; Shigang Shen; Hui Li (Environmental Research, 2025)

Single-ion conductor covalently grafted onto MOFs to realize solid polymer electrolyte tripartite conducting channels in lithium metal batteries - Feixiang Zhou; Linfeng Fu; Qingping Wu; Chao Ding; Le Yu; Weidong Zhou; Fahai Cao; Hui Liu; Jun Xu (Chemical Engineering Journal, 2025)

Hydrophobic sponge spicule-mediated transdermal vaccination combines controlled skin inflammation as self-adjuvant with dual immune activation - Yutong Zeng; Huichao Xie; Mengzhu Liu; Qixia Jiao; Hui Huang; Shuxian Fu; Bao Li; Yongfeng Chen; Chi Zhang; Pingtian Ding; Ming Chen; Keda Zhang (Chemical Engineering Journal, 2025)

The BBX Gene Family in Papaya (Carica papaya L.): Genome-Wide Identification and Expression Profiling During Fruit Ripening - Meiling Ding; Shengjie Li; Jialin Hu; Sicheng Bai; Xianqi Fu; Zhimiao Liang; Xiaomin Liang; Yating Li; Miaoyu Zhao (Tropical Plant Biology, 2025)

HWI encoding/decoding of a non-invasive HWI—BCI paradigm based on temporal variation abundance scale - Peng Ding; Fan Wang; Lei Zhao; Anming Gong; Yunfa Fu (Cognitive Neurodynamics, 2025)

LiDAR-inertial coupled simultaneous localization and mapping for deformation monitoring of shield tunnel under construction - Qiushi Wang; Yafei Qiao; Kourosh Khoshelham; Wenqi Ding; Yiming Fu; Ruijia Li (Tunnelling and Underground Space Technology, 2025)

Unlocking the potential of fruit and vegetable waste: Sustainable biomanufacturing strategies for synergistic nutrient recovery and high-value bioproduct synthesis - Ziyi Fan; Zhipeng Gao; Yanjiao Fu; Yanfang Liao; Wenbin Xiao; Yunlong Ding; Chenqi Yang; Xin Li; Gaoyang Li; Donglin Su; Yang Shan; Jiajing Guo (Trends in Food Science & Technology, 2025)

The synthesis, performance, and functional mechanism of an eco-friendly suppressant derived from hydroxyethyl cellulose for the mitigation of coal dust pollution - Xuhan Ding; Qingyun Fu; Tianting Wang; Qian Xu; Zhenmin Luo; Kai Wang; Huitian Peng; Tao Wang (Process Safety and Environmental Protection, 2025)

Insights into the multi-media spatiotemporal distribution, partitioning, and risks of pharmaceuticals and personal care products in the southern Bohai Sea - Shuang Lu; Han Chen; Min Lv; Peng Zhang; Longwen Fu; Mingsan Man; Wei Zhang; Dongliang Wang; Jing Ding; Wei Liu; Lingxin Chen (Journal of Environmental Management, 2025)

Effects of fermentation by different strains on the Physico- chemical properties, quality, and metabolic profile of Rice noodles - Yuanyuan Ren; Yuhang Li; Rui He; Yingjie Lei; Yi Zhao; Zikuan Meng; Ding Ma; Jin Fu; Geng Zhong (Food Chemistry, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Electrochemiluminescence imaging of stimulus-responsive cell membrane protein dynamics via single-layer graphene electrodes and dendritic nanoprobes - Lurong Ding; Yajuan Yan; Jialian Ding; Wenxuan Fu; Yafeng Wang; Bin Su (Chemical Engineering Journal, 2025)

Deproteinization and controlled starch prehydrolysis in intact pulse cotyledon cells regulates starch retrogradation and digestion - Minghao Mao; Mario M. Martinez; Yunus Emre Tunçil; Li Ding; Chun Chen; Xiong Fu; Qiang Huang; Bin Zhang (Carbohydrate Polymers, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

Impact of grazing on plant species and functional community structure in Tibetan alpine grasslands: Implications for plant diversity conservation - Rang Ding; Haorui Zhang; Tianyu Li; Gang Fu (Agriculture, Ecosystems & Environment, 2025)

Editorial Expression of Concern: The nuclear translocation of endostatin is mediated by its receptor nucleolin in endothelial cells - Nan Song; Yanping Ding; Wei Zhuo; Ting He; Zhiguang Fu; Yang Chen; Xiaomin Song; Yan Fu; Yongzhang Luo (Angiogenesis, 2025)

The novel model INEDM and two traditional models for estimating the carrying capacity of Hong Kong oyster (Crassostrea hongkongensis) in two aquaculture systems in Guangdong Province of China - Xing-Chi Guo; Wen-Ding Liu; Xiao-Yan Ye; Ting-Long Hou; Yao-Wu Fu; Qi-Zhong Zhang (Aquaculture, 2025)

HySwinFormer: A hybrid deep learning architecture for fine-grained classification of marine microalgae - Jiaxuan Li; Min Fu; Lichi Ding; Jian Qi; Jingqiang Yang; Shimin Yang (Science of The Total Environment, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

The impacts of polypropylene microplastics on carbon and nitrogen cycling in coastal wetlands: Field evidence - Feng Yuan; Yue Xue; Zhuoyue Zhang; Jianguo Tao; Yuyang Song; Hongyu Chen; Qihang Liao; Haiyan Lin; Ming Lu; Yongcheng Ding; Teng Wang; Ruize Yang; et al. (Journal of Hazardous Materials, 2025)

Integration of metabolomics and transcriptomics unravels the molecular mechanisms underlying variations in flavor-related volatiles in Citrus reticulata ‘Chachi’ grafted onto different rootstocks - Ding Huang; Jinmei Li; Yuping Wei; Xiang Luo; Xin Xie; Jianhua Chen; Shaochang Yao; Liangbo Li; Jialing Fu; Jidi Xu; Chongling Deng; Rongshao Huang; et al. (Food Research International, 2025)

Hydrolyzed chicken meat extract and its effective cyclopeptides promote neurodevelopment by activating dopamine D1 receptor and cAMP/PKA/CREB pathway - Xinyang Hu; Yifan Zheng; Haojie Jin; Yi Zhang; Wenlong Yang; Kunying Ding; Zhengwei Fu; Yinhua Ni (Food Bioscience, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Synergistic neurotoxicity of polystyrene nanoparticles and MEHP in zebrafish (Danio rerio) - Yiyun Liu; Qi-Ping Tang; Si-Jia Zuo; Yuan Ding; Feng-Yi Guo; Bao-Fu Zhang; Qin-Hong Zhou; Dongmei Xie; De-Sheng Pei (Environmental Pollution, 2025)

Antilipotoxic framework nucleic acid-loaded injectable hydrogel microspheres for the targeted delivery of miR-34a-5p inhibitors to attenuate dietary fat-associated osteoarthritis - Zhichao Zhang; Liwei Fu; Yazhe Zheng; Jiang Wu; Zhixing Zhang; Chuanyang Long; Xun Yuan; ZhenGang Ding; Xiang Sui; Quanyi Guo; Sirong Shi; Shuyun Liu; et al. (Chemical Engineering Journal, 2025)

3D crosslinked semi-interpenetrating single-ion hybrid electrolytes for dendrite-free and high-voltage lithium metal batteries - Xiao Wang; Puyan Huang; Yuwei Zhong; Shicheng Zhang; Jifang Fu; Yu Ding; Liya Chen; Guorong Chen; Fei Lv; Shuai Yuan (Chemical Engineering Journal, 2025)

Machine learning-assisted biomass colorimetric dipsticks for portable clinical nephropathy diagnosis by using smart mobile terminal - Donglei Fu; Lin Ding; Bowen Zhang; Shuaibo Zhang; Junjie Deng; Ruyi Wei; Hua Shui; Xinghai Liu (Chemical Engineering Journal, 2025)

Photothermal-driven micromotor for enhanced lithium extraction from salt-lake brines - Shihao Ding; Wenqian Xing; Ling Chen; Linhui Fu; Xinle Zhang; Zhen Luo; Qianqian Li; Mengting Qin; Jiang Gong; Jinping Qu; Ran Niu (Chemical Engineering Journal, 2025)

Ortho-N-S/N-O dual-site synergistic COF for efficient selective removal and highly sensitive detection of hydrated lead ions - Huizhen Sun; Xiuhua Chen; Zongdeng Wu; Wenhui Ma; Shaoyuan Li; Chen Li; Dandan Wu; Kaixin Fu; Kexiang Ding (Chemical Engineering Journal, 2025)

Highly porous star-crosslinked POSS-based single-ion conducting hybrid electrolytes enabling fast ion transport for dendrite-free lithium metal batteries - Yu Ding; Liya Chen; Xiao Wang; Puyan Huang; Guorong Chen; Jifang Fu (Chemical Engineering Journal, 2025)

Reduced Usage of GLS Intronic Polyadenylation Promotes Cellular Senescence - Xueping Li; Yuxin Li; Dong Ding; Baiyun Xie; Jun Yao; Yu Chen; Zhaozhao Zhao; Peng Yu; Shengwei Zhang; Fu Yang; Ting Ni; Gang Wei (Phenomics, 2025)

Lipid droplet clearance inhibits esophageal cancer growth via metabolic reprogramming - Yan Pu; Yi Wan; Yuhua Fu; Kai Li; Yijiao Chen; Yunzhi Wang; Bin Li; Lingling Li; Zhaoyu Qin; Jingyan Xu; Dongxian Jiang; Yan Li; et al. (Science Bulletin, 2025)

Biogeochemical controls on metal distribution and pedogenesis in tropical island soils - Chin Yik LIN; Peili DENG; Mohd Talha ANEES; Fu-Jun YUE; Su Shiung LAM; Hu DING; Elanni AFFANDI; Baba MUSTA (Pedosphere, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Evaluation of real-world CO2 and NOX emissions of various in-use heavy-duty vehicles - Jia Ke; Han Jiang; Xinping Yang; Mingliang Fu; Zhihui Huang; Yunjing Wang; Yan Ding (Journal of Hazardous Materials, 2025)

Di-(2-ethylhexyl) phthalate (DEHP) and its metabolite promote multiple myeloma progression and bortezomib resistance - Wenxia Li; Hangjie Fu; Lijian Zhu; Wei Wang; Wenli Yang; Wenbin Yang; Hua Huang; Bin Ding; Jie Sun; Hongyan Tong (Journal of Hazardous Materials, 2025)

Bisphenol A caused abnormal spermatogenesis of Eriocheir sinensis through es-ERR/es-KIF4A pathway with discussion of BPA substitutes - Yu Yang; Di Wu; Tian Lei; Hang-Yuan Zhao; Jun-Jie Yu; Lan-Min Wang; Ding-Xi Liu; Yan-Shuang Zhao; Jia-Hao Ni; Fu-Qing Tan; Wan-Xi Yang (Journal of Hazardous Materials, 2025)

Numerical and molecular dynamics simulation on the wetting-coating-aggregating behaviors of biomass and betaine-based surfactants in suppression coal dust pollution - Xuhan Ding; Qian Xu; Kai Wang; Zhenmin Luo; Tao Wei; Tao Wang; Jiuzhu Wang; Qingyun Fu; Tianting Wang (Journal of Cleaner Production, 2025)

Studies on the key enzyme for the conversion of limonene to α-terpineol by Penicillium digitatum DSM62840 - Boyu Yang; Yingying Zhang; Xiwen Hu; Jingnan Ren; Gang Fan; Jinchu Yang; Qiuling Wang; Yongfeng Yang; Zhenzhen Huang; Yongming Xu; Haoliang Li; Yufeng Fu; et al. (Food Bioscience, 2025)

Quality enhancement and metabolic mechanism of fermented sausages with Lactiplantibacillus plantarum and Companilactobacillus alimentarius - Fangrui Han; Qiancheng Wu; Shan Li; Yuting Luo; Zengkang Ding; Tong Luo; Jiesong Liang; Chenxiang Fu; Yingchen Wang; Zhongjie Yu (Food Bioscience, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Predicting planting suitability of globally important grain crops using a hybrid model - Yongxia Ding; Darong Fu; Peixiang Jiao; Jielin Zhang; Shouzhang Peng (European Journal of Agronomy, 2025)

Evolution of fire activity in arid Central Asia since ∼12.9 ka: Transitioning from natural to anthropogenic forces - Wensheng Zhang; Guoqiang Ding; Yong Zhang; Yuecong Li; Bing Li; Chao Lu; Bo Tan; Aijun Sun; Yang Fu; Chengbang An (CATENA, 2025)

White matter microstructural abnormalities related to emotional dysfunction and childhood trauma characterize adolescents with borderline personality disorder - Xiaoping Yi; Xueying Wang; Liying Shen; Yan Fu; Qian Xiao; Jinfan Zhang; Jun Ding; Furong Jiang; Zhejia Zhang; Alessandro Grecucci; Bihong T. Chen (Brain Imaging and Behavior, 2025)

EEF1D signaling contributes to Bovine alpha herpesvirus 1 productive infection, potentially through regulation of viral replication compartments - Bin Hou; Xiaotian Fu; Yuanshan Luo; Xiuyan Ding; Liqian Zhu (Veterinary Microbiology, 2025)

Sterilized protective immunity induced by DAM and DAM+ in mouse models for both VACV and MPXV - Zhengrong Gao; Tingting Zheng; Jiahao Wu; Haoyi Ding; Jia Lu; Jiahui Si; Yuze Xu; Hao Liu; Guocan Yu; Renyi Ma; Jianxun Qi; Yunfei Zhao; et al. (Science Bulletin, 2025)

Three new methylene-bridged bisflavonoid glycosides with cardioprotective activity from Suaeda glauca - Xianrui Ding; Jia Jia; Xianjun Fu; Zhengwei Gu; Kuo Xu (Phytochemistry Letters, 2025)

Insights into the synergistic mechanisms of citric acid in detoxifying cadmium in tall fescue - Jian Cui; Wenqi Ding; Shuning Li; Xuanyang Wu; Jianing Wang; Qiuyu Su; Junxiang Qi; Xiaoyang Sun; Jinmin Fu (Journal of Hazardous Materials, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

Characteristics and influence factors of ammonia emissions from light-duty vehicles under real-world driving conditions - Xian Wu; Han Jiang; Haiguang Zhao; Yitu Lai; Lei Zu; Yunjing Wang; Mingliang Fu; Sheng Su; Yan Ding (Fuel, 2025)

Ellagic acid alleviates iron overload-induced liver damage by mitigating ferroptosis through modulation of the TGFβ/Smad signaling pathway - Hangjie Fu; Wenxia Li; Qimei Cheng; Zhiwei Weng; Zhiguang Huang; Lijian Zhu; Tao Ding; Bin Ding (Food Research International, 2025)

Self-healing carboxymethyl chitosan hydrogel with anthocyanin for monitoring the spoilage of flesh foods - Fuyuan Ding; Lin Fu; Xiaowei Huang; Jiyong Shi; Megan Povey; Xiaobo Zou (Food Hydrocolloids, 2025)

Degradation of 2- (2-hydroxy-5-methylphenyl) benzotriazole (UV-P) by ferrate(VI): key factors, reaction pathway, and toxicity assessment - Xiaochen Qi; Fuli Li; Chih-Huang Weng; Kai Liu; Renchuan Fu; Na Liu; Longzhen Ding (Chemical Engineering Journal, 2025)

Incorporating zinc coordination driven nanozyme into chitosan and hyaluronic acid based nanoplatform for scavenging H2S/ROS in managing inflammatory bowel disease - Jiafeng Zou; Wenxing Ding; You Chen; Xier Pan; Xiuzhi Fu; Shulei Zheng; Yiting Lin; Chuanhe Xia; Ying Ma; Xiaochun Zhang; Shuang Wu; Feng Gao (Carbohydrate Polymers, 2025)

Cascade assembly of metal-organic Framework–Immobilized enzyme complexes for enhanced catalytic activity and sensing applications - Zuyao Fu; Hao Wang; Lingfeng Yang; Zhaoyang Ding; Jing Xie (Chemical Engineering Journal, 2025)

Nano-sized coordination polymer particles (CPPs) for synergetic application in antibacterial and anticancer therapeutics - Wang Ding; Tikai Zhang; Ruiying Fu; Chengtao Yu; Cheng Zhang; Kuaibing Wang; Pengfei Zhang (Chemical Engineering Journal, 2025)

Synergistically modulating multiple polarizations of electrically insulating and thermally conductive SnO2@C hollow core–shell nanofasciculi for exceptional EM protection capabilities - Baoxin Fan; Junhao Ding; Shiyang Cai; Kang Fu; Xiangyang Liu; Lingling Lin; Zhenjie Yu; Guoxiu Tong; Wenhua Wu (Chemical Engineering Journal, 2025)

Enhanced photosynthetic CO2 fixation in mutualistic Chlorella sp. and Mesorhizobium loti co-cultures - Dandan Yao; Yunhui Li; Kun Tian; Meng Wang; Ding Tan; Xingjia Fu; Yonghong Wu; Yun Liu; Hui Wang (Chemical Engineering Journal, 2025)

Synergistic effect of charge-transfer bridge and surface defects for highly efficient photothermal catalytic CO2 reduction over 2D/3D SrTiO3/Zn0.5Cd0.5S - Peigen Ding; Zhanfei Fu; Liuna Zhang; Hongbin He; Jiarui Yang; Qi He; Zesheng Li; Jiale Cheng; Tian Gao; Xiaoming Gao (Chemical Engineering Journal, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Effect of hydrochemical conditions on transport of HFPO-DA in saturated quartz sand and limestone porous media - Yanfeng Shi; Xinle Han; Lixingzi Wu; Ling Fu; Weina Xue; Xuli Jing; Jing Xu; Zhibin Zhang; Botao Ding (Environmental Geochemistry and Health, 2025)

Identifying seasonal sources and processes controlling nitrate in a typical reservoir-type headwater watershed of Eastern China using stable isotopes - Mengyao Ding; Huawu Wu; Haixia Zhang; Qing Zhu; Ruiyu Lei; Kaiwen Li; Hongxiang Fan; Jing Li; Congsheng Fu (Agriculture, Ecosystems & Environment, 2025)

Eutrophication‐induced dinoflagellate succession contributes to marine carbon sequestration through refractory dissolved organic matter accumulation - Fu‐Tao Fang; Zhuo‐Yi Zhu; Yuan‐Bi Yi; Ding He; Hong‐Yan Bao; En‐Ren Zhang; Cheng‐Xu Zhou (Limnology and Oceanography, 2025)
The increasing eutrophication of coastal seas is causing a shift in the most important phytoplankton groups from diatoms to dinoflagellates, but its feedback to marine carbon cycling remains unclear. Here, we investigated the potential of the key coastal phytoplankton, the diatom Skeletonema costatum , and the dinoflagellate Prorocentrum donghaiense , for refractory dissolved organic carbon (DOC) accumulation over dark degradation incubations of 70 d. Our multi‐method approach showed that dinoflagellate detritus, rather than diatom detritus, significantly contributes to refractory DOC. This is evidenced by the fact that the detritus of dinoflagellates compared to that of diatoms (1) has a weaker transmittance in infrared spectrometry, indicating a lower content of labile organic substances (alcohol and amide groups); (2) has a higher release and/or transformation efficiency of particulate organic carbon to DOC (81% vs. 50%); (3) has a lower content of labile fraction, amino acid (8% vs. 17% carbon) and exhibits lower degradability of the DOC formed (23% vs. 30%); (4) has a lower content of labile compounds determined by Fourier transform ion cyclotron resonance mass spectrometry (maximum molecular lability boundary: 21% vs. 31%); and (5) has a higher proportion of refractory carboxylic‐rich alicyclic molecules (57% ± 0.5% vs. 51% ± 0.7%) over incubations. Our results emphasize that eutrophication‐triggered coastal dinoflagellate succession has a significant potential for positive feedback to carbon sequestration through the formation of refractory DOC.

An N-heterocyclic carbene-copper(I) functionalized metal-organic framework: Synthesis and recoverable applications in the carboxylation of CO2 with terminal alkynes - Li-Xin You; Tian-Cheng Han; Jin-Rong Li; Jie Guo; Gang Xiong; Fu ding; Ya-Guang Sun (Journal of Environmental Chemical Engineering, 2025)

Nickel recovery as nickel foil from electroplating sludge using a combination of bipolar membrane electrodialysis and electrodeposition - Xiaoyun Wu; Jianguo Ding; Yuying Fu; Mingzhi Lv; Yaoxing Liu (Journal of Environmental Chemical Engineering, 2025)

Experimental and molecular dynamics analysis on the mechanism of -pSO3H, -OSO3H and heavy alkyl functional groups in affecting wetting and agglomeration behaviour of coal particles during dust suppression - Xuhan Ding; Qingyun Fu; Kai Wang; Qian Xu; Tianting Wang; Zhenmin Luo; Yuting Wang; Minjun Ma; Yongzhe Zhang; Tao Wang; Jiuzhu Wang (Journal of Environmental Chemical Engineering, 2025)

UiO-66 MOFs with enhanced hydrogen bond for histamine capture - Yuanyuan Ji; Zuyao Fu; Zhaoyang Ding; Jing Xie (Journal of Environmental Chemical Engineering, 2025)

The effect and mechanisms of nano cerium dioxide (Nano-CeO2) on cardiovascular development in zebrafish (Danio rerio) - Yiyun Liu; Yan-Ling Liao; Jin-Xia Wang; Bao-Fu Zhang; Qi-Ping Tang; Yuan Ding; Si-Jia Zuo; Qin-Hong Zhou; De-Sheng Pei (Environmental Pollution, 2025)

Controllable spatial assembly of Mn doped RuO2 on Bi4NbO8Cl to promote Z-scheme photocatalytic overall water splitting - Kailong Gao; Qi He; Liuna Zhang; Peigeng Ding; Jiarui Yang; Hongxia Guo; Xiaoming Gao; Feng Fu (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Amorphous coating and gradient doping stabilizing LiCoO2 cathodes at 4.7 V and 45 °C - Xuelian Fu; Mingyang Yang; Lvjun Chen; Jing Hu; Zhiqiang Wang; Yulin Cao; Yongcong Huang; Huaiguo Huang; Ding Tang; Xingqun Liao; Dalin Hu; Zhouguang Lu (Chemical Engineering Journal, 2025)

Rapid degradation of frozen soil environments in thermokarst-affected alpine grasslands on the Qinghai-Tibet Plateau under climate change - Yuanhong Deng; Xiaoyan Li; Chao Yang; Fangzhong Shi; Shaojie Zhao; Sha Zhou; Chiyuan Miao; Ruiqiang Ding; Yongshuo H. Fu; Xiaofan Yang; Zhigang Wang (CATENA, 2025)

Cancer-Associated Fibroblasts Interact with Schwann Cells for Tumor Perineural Invasion by Oral Squamous Cell Carcinoma - Xinwen Zhang; Yijia He; Shixin Xie; Yuxian Song; Xiaofeng Huang; Qingang Hu; Yanhong Ni; Yi Wang; Yong Fu; Liang Ding (Neuroscience Bulletin, 2025)

Effects of carbon sources on nitrite removal and microbial diversity in mariculture water - Zhen Ding; Meiling An; Hongli Xu; Zhongping Xu; Ning Fu; Lushan Wang; Li Zhang; Guoping Li (Biologia, 2025)

Insect-YOLO: A new method of crop insect detection - Nan Wang; Shaowen Fu; Qiong Rao; Guiyou Zhang; Mingquan Ding (Computers and Electronics in Agriculture, 2025)

The depletion of TFAM and p-β-catenin(S552) in mitochondria in response to BoAHV-1 productive infection leads to decreased mitochondrial biogenesis - Jiayu Lin; Xiaotian Fu; Xuan Li; Xiuyan Ding; Shitao Li; Filomena Fiorito; Liqian Zhu (Veterinary Microbiology, 2025)

Abrupt loss of species richness caused by ecosystem transition - Li Fu; Jianping Huang; Guolong Zhang; Dongliang Han; Lei Ding; Yun Wei; Xiaoyue Liu; Changyu Li; Haipeng Yu (Science Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Comparison of the fully coupled dynamic responses of spar-type integrated wind-current floating energy systems with various tidal turbine layouts - Wei Liu; Jieyi Ding; Jianbin Fu; Zhen Zhang; Jie Yu; Haigang Hu; Musa Bashir; Shuai Li; Yang Yang (Ocean Engineering, 2025)

Environmental factors impacting phytoplankton response to the cold water mass in the Yellow Sea - Lichi Ding; Jiaxuan Li; Qian Zhang; Min Fu; Shimin Yang (Journal of Cleaner Production, 2025)

Effect of single and hybrid microplastic exposures on anaerobic sludge in microbial electrochemical technology (MET) - Kunpeng Zhou; Yun Fan; Huilin Yin; Quankai Fu; Chuanning Xiao; Nuchao Xu; Zhenyu Ding (Journal of Environmental Management, 2025)

Climatic driving mechanisms of the propagation from meteorological drought to agricultural and ecological droughts - Chong Li; Yongshuo Fu; Qianzuo Zhao; Xuan Zhang; Ruiqiang Ding; Fanghua Hao; Guodong Yin (Journal of Environmental Management, 2025)

Impact of particle-attached microbial denitrification on N2O production in an agricultural-urban watershed - Mengdi Yang; Hanjie Yang; Wencai Wang; Huaiyang Fang; Lu Huang; Dan Li; Lingfang Fu; Shiyuan Ding; Xiao-Dong Li; Cong-Qiang Liu; Gangjian Wei; Dongli Li; et al. (Journal of Environmental Management, 2025)

Inter-individual variation in human microbiota drives differential impacts on the fermentability of insoluble bran by soluble β-glucans from whole barley - Songtao Fan; Yiwei Ding; Zikang Hu; Zhihong Zhang; Lin Fu; Jiayan Zhang; Ying Zhu; Juan Bai; Xiang Xiao (Food Hydrocolloids, 2025)

Volatile organic compounds in a typical petrochemical production area in Shanghai, China: Source profiles, human health and environmental impacts - Zhijian Ding; Yuewu Li; Qingyan Fu; Mengke Tian; Fanglin Wang; Yunkai Wang; Kan Huang (Environmental Pollution, 2025)

Low-hysteresis, high-fidelity flexible strain sensor with interconnected conductive network design for harsh environments and manipulator control - Peng Ding; Jia Wang; Zhitao Xiao; Xinxin Zhao; Yi Zhao; Xiaofei Fu; Wei Zhai; Kangkang Zhou; Kun Dai; Guoqiang Zheng; Chuntai Liu; Changyu Shen (Chemical Engineering Journal, 2025)

Silent soils have been awakened by climate change - Dongliang Han; Jianping Huang; Xiaoyue Liu; Li Fu; Lei Ding; Guolong Zhang; Changyu Li; Fan Yang; Jinsen Shi; Beidou Zhang (CATENA, 2025)

Inter-annual and seasonal variations of meteorological drought and their drivers in the southwest karst region of China - Baowei Fu; Juanli Jing; Qifang Deng; Shunshun Ding (Environmental Science and Pollution Research, 2025)

Advancements in artificial pollination of crops: from manual to autonomous - Leilei He; Xiaojuan Liu; Yusong Ding; Xudong Jing; Haojie Dang; Bryan Gilbert Murengami; Lamin L. Janneh; Rui Li; Spyros Fountas; Jayme Garcia Arnal Barbedo; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Estimating groundwater discharge in the dam-affected rivers using 222Rn - Linlin Kong; Fu Liao; Peijie Yang; Guangcai Wang; Hanxiao Wang; Shengda Ding; Zhihao Wang; Huyang Ai; Pengpeng Zhou; Zheming Shi (Journal of Hydrology, 2025)

Electric field as an activator of inoculated Bacillus clausii enhances humification during electric field-assisted aerobic composting - Jiahuan Tang; Huan Mi; Chang Shen; Keren Ding; Shuqun Zhang; Huayuan Shangguan; Tao Fu; Jie Ye; Hao Lin (Journal of Environmental Management, 2025)

A novel injectable sodium alginate/chitosan/sulfated bacterial cellulose hydrogel as biohybrid artificial pancreas for real-time glycaemic regulation - Xiang Zhao; Wei Xue; Weixiao Ding; Yalei Qiao; Xuehui Chu; Yudong Qiu; Min Tang; Dongping Sun; Xiao Fu (Carbohydrate Polymers, 2025)

Coordinated transcriptional regulation of carbohydrate-related pathways contributes to the difference of starch accumulation between starchy cassava and sugary cassava - Zehong Ding; Lili Fu; Ganlu Chen; Yan Yan; Weiwei Tie; Xianwei Meng; Jinghao Yang; Xianjin Qiu; Jiaming Zhang; Wei Hu (Carbohydrate Polymers, 2025)

Taxonomic, phylogenetic, and functional β-diversity along an urbanization gradient in Taipei metropolitan area - Shu-Wei Fu; Jerome Chie-Jen Ko; Tzung-Su Ding (Urban Ecosystems, 2025)

Visualization of mitochondrial molecular dynamics during mitophagy process by label-free surface-enhanced Raman scattering spectroscopy - Hailan Jia; Chi Wang; Yan Fu; Yalin Wang; Xiaoyu Zhang; Yuezhou Tang; Jiahao Ding; Kun He; Jing Wang; Yanting Shen (Analytica Chimica Acta, 2025)

Fatigue Reliability Analysis of Offshore Wind Turbines Under Combined Wind–Wave Excitation via Direct Probability Integral Method - Jingyi Ding; Hanshu Chen; Xiaoting Liu; Youssef F. Rashed; Zhuojia Fu (Journal of Marine Science and Engineering, 2025)
As offshore wind turbines develop into deepwater operations, accurately quantifying the impact of stochastic excitation in complex sea environments on offshore wind turbines and conducting structural fatigue reliability analysis has become challenging. In this paper, based on long-term wind–wave reanalysis data from the South China Sea, a novel direct probability integral method (DPIM) is developed for the stochastic response and fatigue reliability analysis of the key components for the floating offshore wind turbine structures, under combined wind–wave excitation. A 5 MW floating offshore wind turbine is considered as the research object, and a comprehensive analysis of the wind turbine system is performed to assess the short-term fatigue damage at the tower base and blade root. The proposed method’s accuracy and efficiency are validated by comparing the results to those obtained from Monte Carlo simulations (MCS) and a subset simulation (SSM). Additionally, a sensitivity analysis is conducted to evaluate the impact of different environmental parameters on fatigue damage, providing valuable insights for the design and operation of FOWTs in varying sea conditions. Furthermore, the results indicate that the fatigue life of floating offshore wind turbine (FOWT) structures under combined wind–wave excitation meets the design requirements. Notably, the fatigue reliability of the wind turbine under aligned wind–wave conditions is lower compared to misaligned wind–wave conditions.

Revealing the mobilization and age of estuarine dissolved organic matter during floods using radiocarbon and molecular fingerprints - Zhao Liang Chen; Yuanbi Yi; Ruanhong Cai; Zhe-Xuan Zhang; Wenzhao Liang; Wenjing Fu; Penghui Li; Kai Wang; Lixin Zhang; Kejun Dong; Si-Liang Li; Sheng Xu; et al. (Water Research, 2025)

Glutathione-depleting supramolecular gold nano-assemblies for NIR-II imaging guided photodynamic immunotherapy - Ziyi Wang; Jianwen Wei; Zhongke Liu; Xiaobei Huang; Lei Pak In; Kui He; Yuan-Fu Ding; Ruibing Wang (Chemical Engineering Journal, 2025)

Rhizosphere bacterial communities mediate the effect of maize-soybean strip intercropping and nitrogen management on cadmium phytoextraction - Yuze Li; Ting Xing; Zhidan Fu; Tian Pu; Peng Ding; Yushan Wu; Feng Yang; Xiaochun Wang; Taiwen Yong; Wenyu Yang (Applied Soil Ecology, 2025)

Nonlinear response of soil microbial network complexity to long-term nitrogen addition in a semiarid grassland: Implications for soil carbon processes - Yaodan Zhang; Decao Niu; Qingwei Li; Huiying Liu; Ying Wang; Jingrun Xu; Baoming Du; Ding Guo; Yubing Liu; Hua Fu; Xiaobo Yuan (Agriculture, Ecosystems & Environment, 2025)

The Co‐Infection of ISKNV ‐ II and RGNNV Resulting in Mass Mortality of Juvenile Asian Seabass ( Lates calcarifer ), Zhuhai, Southern China - Qianqian Sun; Shan Ding; Xiangrong Liu; Wenfeng Zhang; Fangzhao Yu; Yuting Fu; Yong Li; Chuanfu Dong (Journal of Fish Diseases, 2025)
Infectious spleen and kidney necrosis virus (ISKNV) and nervous necrosis virus (NNV) are two common and important causative agents in marine‐cultured fish. However, high viral loads of both ISKNV and NNV in the same clinical case is unusual. In this study, a mass mortality event of Asian seabass Lates calcarifer juveniles occurred in Zhuhai, the main Asian seabass cultured area in mainland China. The fish samples were pooled for pathogen identification and both high viral loads of ISKNV and NNV were detected by real‐time microfluidic quantitative PCR and conventional PCR. Immunohistochemistry and immunofluorescence showed that strong ISKNV signals were detected in spleen and liver, while strong NNV signals were detected in brain and eye. The tissue homogenates were inoculated into MFF‐1 cell and SSN‐1 cell, respectively. After several viral passages, both individual ISKNV and NNV were purely isolated from each other, and designated as ASB‐ISKNV‐23 and ASB‐NNV‐23, respectively. The whole genome sequences of ASB‐ISKNV‐23 and ASB‐NNV‐23 were determined and annotated. The result showed that ASB‐ISKNV‐23 and ASB‐NNV‐23 are composed of 112,236 bp and 4441 bp, respectively. Phylogeny analysis showed that ASB‐ISKNV‐23 belongs to ISKNV‐II sub‐genotype and ASB‐NNV‐23 belongs to RGNNV genotype. Collectedly, coinfection of ISKNV‐II and RGNNV were firstly documented in mass mortality of Asian seabass in mainland China. Importantly, both individual ISKNV‐II and RGNNV were purely isolated using two different permissive cell lines. Our study provides useful information for better understanding the complex pathogenesis regarding the coinfection with ISKNV and NNV in farmed fish.

Dynamic analysis of intrahepatic T cells reveals a unique group of restorative Cxcr3+ tissue-resident CD4 T cells in acute liver injury - Shen-Xi Ouyang; Yong-Gang Xu; Peng Ding; Yue Long; Zhen Zhang; Si-Jia Sun; Yan Zhang; Hang Yin; Jia-Bao Zhang; Qi Cao; Fu-Ming Shen; Pei Wang; et al. (Toxicology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Human cardiac organoid model reveals antibacterial triclocarban promotes myocardial hypertrophy by interfering with endothelial cell metabolism - Nana Yang; Jiahong Chen; Yujie Zhu; Wenxin Shan; Zheng Cao; Yiwen Fu; Huanhuan Cao; Yanyan Li; Yukun Xiang; Shusi Ding; Huiqing Wang; Yaobo Zhao; et al. (Science Bulletin, 2025)

Calcium and iron isotope fractionation during felsic magma differentiation - Qiu-Yun Guan; Jin-Xiang Li; Ya-Li Sun; Shi-Lei Tang; Noreen J. Evans; Zhao-Feng Zhang; Li-Yun Zhang; Fu-Long Cai; Wei-Ming Fan; Lin Ding (Lithos, 2025)

Catalytic degradation of ethyl acetate at room temperature over Ni/NAC monolithic catalyst - Xiangci Wu; Chenglong Dai; Lisheng Zhang; Ge Gao; Jiahui Shi; Dan Zhao; Bingfeng Fu; Shejiang Liu; Jianfeng Fu; Hui Ding (Journal of Environmental Chemical Engineering, 2025)

Emission control status and future perspectives of diesel trucks in China - Shihai Zhang; Mingliang Fu; Hefeng Zhang; Hang Yin; Yan Ding (Journal of Environmental Sciences, 2025)

Unlocking the potential differences and effects of the anode and cathode regions on N2O emissions during electric field-assisted aerobic composting - Huayuan Shangguan; Chang Shen; Keren Ding; Xiangtian Peng; Huan Mi; Shuqun Zhang; Jiahuan Tang; Tao Fu; Hao Lin (Bioresource Technology, 2025)

Impacts of continuous potato cropping on soil microbial assembly processes and spread of potato common scab - Lichun Wang; Song Liu; Guokui Tian; Yang Pan; Haiyan Wang; Guangwei Qiu; Fengyun Li; Ze Pang; Kaixin Ding; Jinpeng Zhang; Hong Xue; Xinyuan Li; et al. (Applied Soil Ecology, 2025)

Global effects of livestock grazing on ecosystem functions vary with grazing management and environment - Weiling Niu; Jingyi Ding; Bojie Fu; Wenwu Zhao; David Eldridge (Agriculture, Ecosystems & Environment, 2025)

Study on the characteristics of bird communities in urban river corridor parks and green spaces - Yinghong Ding; Dulai Zheng; Yuxin Lin; Junyi Li; Weicong Fu; Ziru Chen; Jin Yang; Xiaoling Xu; Zhipeng Zhu (Environment, Development and Sustainability, 2025)

A Cross-Stage Focused Small Object Detection Network for Unmanned Aerial Vehicle Assisted Maritime Applications - Gege Ding; Jiayue Liu; Dongsheng Li; Xiaming Fu; Yucheng Zhou; Mingrui Zhang; Wantong Li; Yanjuan Wang; Chunxu Li; Xiongfei Geng (Journal of Marine Science and Engineering, 2025)
The application potential of unmanned aerial vehicles (UAVs) in marine search and rescue is especially of concern for the ongoing advancement of visual recognition technology and image processing technology. Limited computing resources, insufficient pixel representation for small objects in high-altitude images, and challenging visibility conditions hinder UAVs’ target recognition performance in maritime search and rescue operations, highlighting the need for further optimization and enhancement. This study introduces an innovative detection framework, CFSD-UAVNet, designed to boost the accuracy of detecting minor objects within imagery captured from elevated altitudes. To improve the performance of the feature pyramid network (FPN) and path aggregation network (PAN), a newly designed PHead structure was proposed, focusing on better leveraging shallow features. Then, structural pruning was applied to refine the model and enhance its capability in detecting small objects. Moreover, to conserve computational resources, a lightweight CED module was introduced to reduce parameters and conserve the computing resources of the UAV. At the same time, in each detection layer, a lightweight CRE module was integrated, leveraging attention mechanisms and detection heads to enhance precision for small object detection. Finally, to enhance the model’s robustness, WIoUv2 loss function was employed, ensuring a balanced treatment of positive and negative samples. The CFSD-UAVNet model was evaluated on the publicly available SeaDronesSee maritime dataset and compared with other cutting-edge algorithms. The experimental results showed that the CFSD-UAVNet model achieved an mAP@50 of 80.1% with only 1.7 M parameters and a computational cost of 10.2 G, marking a 12.1% improvement over YOLOv8 and a 4.6% increase compared to DETR. The novel CFSD-UAVNet model effectively balances the limitations of scenarios and detection accuracy, demonstrating application potential and value in the field of UAV-assisted maritime search and rescue.

53BP1, a known chromatin-associated factor that promotes DNA damage repair, is differentially modulated during bovine herpesvirus 1 infection in vitro and in vivo - Heci Zhao; Xiaotian Fu; Wenyuan Gu; Xiuyan Ding; Liqian Zhu (Veterinary Microbiology, 2025)

Review of vibration induced by gas-liquid two-phase flow inside pipes - Lin Ding; Yitong Fu; Xiang Li; Jingyu Ran (Ocean Engineering, 2025)

Combined application of the endophyte Bacillus K1 and sodium dehydroacetate alleviates postharvest gray mold in grapes - Baozhen Feng; Chunshuang Ding; Peiqian Li; Li Fu (Food Microbiology, 2025)

Transformer-embedded 1D VGG convolutional neural network for regional landslides detection boosted by multichannel data inputs - Bangjie Fu; Yange Li; Chen Wang; Zheng Han; Nan Jiang; Wendu Xie; Changli Li; Haohui Ding; Weidong Wang; Guangqi Chen (Environmental Modelling & Software, 2025)

R&D investment and corporate total factor productivity under the heterogeneous environmental regulations: evidence from Chinese micro firms - X. Ding; Y. Zhang; Y. Fu; Z. Xu (International Journal of Environmental Science and Technology, 2025)

An ultra-sensitive SERS approach by electrostatic enrichment of charged analytes on Ag/laponite nanocomposites - Hao Zhang; Chaopeng Fu; Jianhao Ding; Guoqiang Xu; Chunhui Zhou; Zhenyu He; Zhimin Ou; Dongshen Tong; Minyang Qiu; Xiangdong Zhou; Xiaonian Li (Applied Clay Science, 2025)

Study of LFG bubble accumulation and discontinuous flow in the highly saturated region of landfill below the leachate level - Qi-Teng Zheng; Jin-Shui Ju; Wen-Ding Fu; Shi-Jin Feng; Jun Wang (Waste Management, 2024)

SCARF: A new algorithm for continuous prediction of biomass dynamics using machine learning and Landsat time series - Yingchun Fu; Runhao Li; Zhe Zhu; Yufei Xue; Hu Ding; Xinyu Wang; Jiaming Na; Weijie Xia (Remote Sensing of Environment, 2024)

Recent development on drought propagation: A comprehensive review - Zhaoqiang Zhou; Ping Wang; Linqi Li; Qiang Fu; Yibo Ding; Peng Chen; Ping Xue; Tian Wang; Haiyun Shi (Journal of Hydrology, 2024)

Effects of iron oxide minerals on the pyrolysis of polyvinyl chloride: Catalytic dechlorination, chlorine capture, and carbon sequestration - Ziyi Ding; Runliang Zhu; Qingru Xie; Shiqin Long; Haoyang Fu; Qingze Chen; Yunfei Xi (Journal of Cleaner Production, 2024)

Insights into pore structure-activity relationships of iron catalysts supported on fluorine–cerium nanosheets for heterogeneous Fenton oxidation - Jing Lv; Hui Ye; Shurui Han; Jinli Zhao; Guodong Yang; Han Zhang; Xiaojian Fu; Jing Zhang; Qingping Xin; Lizhi Zhao; Hong Li; Ligang Lin; et al. (Journal of Environmental Chemical Engineering, 2024)

Experimental and molecular dynamics simulation of the synergistic mechanism of short-chain fluorocarbon surfactant and electrolyte on inhibiting coal dust pollution - Xuhan Ding; Kai Wang; Qingyun Fu; Tianting Wang; Zhenmin Luo; Yong Yang; Tao Wang; Haipeng Jiang; Xin Yi (Journal of Environmental Chemical Engineering, 2024)

Portable sensing of hydrogen peroxide using MOF-based nanozymes - LingFeng Yang; Zuyao Fu; Jing Xie; Zhaoyang Ding (Food Research International, 2024)

Constructing in-situ and real-time monitoring methods during soy sauce production by miniature fiber NIR spectrometers - Zhankai Zhang; Yanhua Ding; Feng Hu; Zhan Liu; Xiaodong Lin; Jiangyan Fu; Qingyu Zhang; Zhi-hong Zhang; Haile Ma; Xianli Gao (Food Chemistry, 2024)

Molecular phylogeny of Podoscypha (Basidiomycota, Podoscyphaceae) with descriptions of four new species, inferred from nuclear rDNA sequences - Fu-Chang Huang; Jian-Tian Lin; Hai-Fu Zheng; Yun-Long Liang; Miao-Miao Li; Cheng-Pei Ding (Mycological Progress, 2024)

A review of ethical considerations for the medical applications of brain-computer interfaces - Zhe Zhang; Yanxiao Chen; Xu Zhao; Wang Fan; Ding Peng; Tianwen Li; Lei Zhao; Yunfa Fu (Cognitive Neurodynamics, 2024)

Single-well fracture prediction based on R/S-FD numerical analysis method: a case study of Ordovician carbonate reservoir in Tahe Oilfield, Tarim Basin - Ziwen Wang; Wenlong Ding; Pengyuan Han; Chen Liang; Zhiyuan Jiang; Yuanhao Fu; Yukun Zhao (Carbonates and Evaporites, 2024)

Sustainability-inspired upcycling of plastic waste into porous carbon nanobulks for water decontamination via peroxymonosulfate activation - Kun Pang; Fangyu Fu; Haoqi Wang; Shun Ding; Yanfen Fang; Xiang Liu (Science of The Total Environment, 2024)

Revisiting the estimation indicator for HONO emissions from light-duty vehicles - Xinping Yang; Mingliang Fu; Songdi Liao; Zhipeng Tu; Weijie Feng; Yunjing Wang; Han Jiang; Qili Tian; Hang Yin; Junyu Zheng; Yan Ding (Journal of Hazardous Materials, 2024)

Blood mercury mediates the associations between fish consumption and serum uric acid levels among Chinese adults: A nationally representative study - Changzi Wu; Bing Wu; Yingli Qu; Hui Fu; Yue Chen; Yifu Lu; Saisai Ji; Liang Ding; Zheng Li; Qi Sun; Miao Zhang; Xu Zhang; et al. (Environmental Research, 2024)

Distribution, sources, impact factors and ecological risks of sediment heavy metals from typical estuarine wetlands in tropical islands - Kaizhe Fu; Zeheng Chen; Cheng Huang; Yuanyuan Chen; Dongming Wu; Xiwen Li; Yanwei Song; Weipin Ding; Xiujiu Yang; Junqiao Long (Estuarine, Coastal and Shelf Science, 2024)

Predicting cyclic liquefaction behavior of saturated granular materials using an updated state evolution model - Lihong Tong; Li Fu; Haibin Ding; Changjie Xu; C.W. Lim (Engineering Geology, 2024)

Centroid aggregation-based boundary detection algorithm in 3D-SPH form for simulating debris-flow dynamics considering boundary frictional effect - Wendu Xie; Yange Li; Zheng Han; Haohui Ding; Jiayong Huang; Yangfan Ma; Bin Su; Bangjie Fu; Changli Li; Weidong Wang (Engineering Geology, 2024)

A GWO-ML-based large deformation finite element variable mapping method: An example of RITSS large deformation finite element simulation - Kailin Ding; Yong Fu (Computers and Geotechnics, 2024)

Bioactives from biomass: Treasure for future potent antimicrobial applications - Weicheng Chen; Peng Zhang; Yucui Ding; Xiaobin Xie; Jianlong Fu; Rong Zhao; Yihan Xiao; Miodrag J. Lukic; Bin Li; Weishan Wang; Song Chen (Chemical Engineering Journal, 2024)

Impact of Atmospheric River and Local Topography on “21·7” Extremely Heavy Rainfall in Henan Province, China - Zhiwei Zhang; Jingjing Chen; Yunying Li; Xiaoxia Fu; Yamei Ding (Atmospheric Research, 2024)

Quinosumycin, a novel anti-MRSA thioether-linked quinolinone-quinazolinone heterodimer from a marine actinomycete Streptomyces diastaticus NBU2966 - Shuangling Tan; Yang Liu; Haonan Fu; Yutong Xue; Fangjian Feng; Jinling Li; Xiaojun Yan; Sitong Wu; Shan He; Lijian Ding (Journal of Oceanology and Limnology, 2024)

High resolution (1-km) surface soil moisture generation from SMAP SSM by considering its difference between freezing and thawing periods in the source region of the Yellow River - Xiaolei Fu; Yuchen Zhang; Luofujie Guo; Haishen Lü; Yongjian Ding; Xianhong Meng; Yu Qin; Yueyang Wang; Bin Xi; Shiqin Xu; Pengcheng Xu; Gengxi Zhang; et al. (Agricultural and Forest Meteorology, 2024)

Integrated transcriptomic and metabolomic analysis reveals the underlying mechanisms for male reproductive toxicity of polystyrene nanoplastics in mouse spermatocyte-derived GC-2spd(ts) cells - Hang Han; Zhen Zhang; Bo Xu; Liyang Ding; Hong Yang; Tiantian He; Xing Du; Xiuying Pei; Xufeng Fu (Toxicology in Vitro, 2024)

Aflatoxin B1 as a complicit in intestinal damage caused by Eimeria ovinoidalis in lambs: Novel insights to reveal parasite-gut battle - Pan Chen; Wen-li Ding; Bo-wen Xu; Mujeeb Ur Rehman; Kai-li Liu; Yan-feng He; Sen-yang Li; Fu-chun Jian; Shu-cheng(淑成) Huang(黄) (Science of The Total Environment, 2024)

High sensitivity of dissolved organic carbon transport during hydrological events in a small subtropical karst catchment - Caiqing Qin; Si-Liang Li; Yiping Wu; Adrian M. Bass; Weijun Luo; Hu Ding; Fu-Jun Yue; Pan Zhang (Science of The Total Environment, 2024)

Hydraulic conditions control the abundance of antibiotic resistance genes and their potential host microorganisms in a frequently regulated river–lake system - Jiewei Ding; Wei Yang; Xinyu Liu; Jiayue Zhao; Xianting Fu; Fangfei Zhang; Haifei Liu (Science of The Total Environment, 2024)

Characterizing ammonia emission from light-duty gasoline vehicles under the influence of multiple factors and its correlation with conventional pollutants - Han Jiang; Haiguang Zhao; Yitu Lai; Yu Kang; Yang Cao; Mingliang Fu; Yan Ding (Science of The Total Environment, 2024)

Comparative RNA-seq analysis of tomato (Solanum lycopersicum L.) provides insights into natural and postharvest ripening - Xiuming Zhao; Fujun Li; Jun Ding; Xiaodong Fu; Jing Shang; Xiangrong Kong; Xiaoan Li; Ling Li; Xinhua Zhang (Postharvest Biology and Technology, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

Transforming waste polystyrene foam to carbon on zeolite for efficient solar water desalination - Mingxin Yang; Hao Zhang; Yuning Fu; Zixuan Wang; Ying Zhang; Zhongwang Ding; Mingbo Yue (Journal of Environmental Chemical Engineering, 2024)

Extracellular vesicles in pulmonary infection: From pathophysiology to theranostic technologies - Xu Wang; Mai-Qing Shi; Yang Wang; Hao Zhou; Ke Peng; Jun Wang; Shi-Kun Sun; Xu-Rui Shen; Jia-Jia Wang; Zhi Zhao; Xian-Guang Ding; Fu-Hai Ji (Chemical Engineering Journal, 2024)

Enhanced uranium extraction using a nanostructured photothermal hydrogel membrane - Zhipeng Liu; Kai Feng; Xinle Zhang; Linhui Fu; Jiaxin Ren; Rui Gao; Shihao Ding; Wenqian Xing; Yiwen Li; Jiaji Cheng; Qiang Li; Jiang Gong; et al. (Chemical Engineering Journal, 2024)

A tetrahedral framework nucleic acids-based gene therapeutic nanococktail alleviates cartilage damage and protects against osteoarthritis progression - Liwei Fu; Jiang Wu; Sirong Shi; Zhichao Zhang; Yazhe Zheng; Pinxue Li; Xun Yuan; Zhengang Ding; Chao Ning; Xiang Sui; Shuyun Liu; Quanyi Guo; et al. (Chemical Engineering Journal, 2024)

Incorporating hydrogen bonding networks in microporous polymer membranes for high-flux hydrocarbon separation - Yanxiong Ren; Jingqi Fu; Rui Ding; Yunshu Li; Xu Liang; Zheyuan Guo; Jianyu Wang; Ziting Zhu; Hong Wu; Guangwei He; Zhongyi Jiang (Chemical Engineering Journal, 2024)

Organosilica with tunable pore structure and antibacterial activity for intelligent humidity control - Jin-Wei Liu; Tao Fu; Yang He; Liang-Jie Wang; Ke-Ren Ding; Hua-Zhang Zhao (Chemical Engineering Journal, 2024)

Unveiling the hidden dynamics of intermittent surface water: A remote sensing framework - Zhen Xiao; Runkui Li; Mingjun Ding; Panli Cai; Jingxian Guo; Haiyu Fu; Xiaoping Zhang; Xianfeng Song (Remote Sensing of Environment, 2024)

Human reliability analysis of offshore high integrity pressure protection system based on improved CREAM and HCR integration method - Yang Yu; Shibo Wu; Yiqin Fu; Xiaowei Liu; Qingze Zeng; Hongyu Ding; Yu Pan; Yuke Wu; Hao Guo; Yuheng Yang (Ocean Engineering, 2024)

Synergistic interactions in core microbiome Rhizobiales accelerate 1,4-dioxane biodegradation - Kun Tian; Yue Zhang; Dandan Yao; Ding Tan; Xingjia Fu; Ruihuan Chen; Ming Zhong; Yuanhua Dong; Yun Liu (Journal of Hazardous Materials, 2024)

Ecosystem multifunctionality is more related to the indirect effects than to the direct effects of human management in China's drylands - Weiling Niu; Jingyi Ding; Bojie Fu; Wenwu Zhao; Yi Han; Ao Zhou; Yue Liu; David Eldridge (Journal of Environmental Management, 2024)

CO2 capture performance, kinetic and corrosion characteristics study of CO2 capture by blended amine aqueous solutions based on 1-(2-hydroxyethyl) piperidine - Pan Zhang; Xuxin Ding; Yanxi Ji; Rujie Wang; Jialin Xie; Kun Zhao; Dong Fu; Lemeng Wang (International Journal of Greenhouse Gas Control, 2024)

Insight into the bacterial community composition of the plastisphere in diverse environments of a coastal salt marsh - Feng Yuan; Xinqing Zou; Qihang Liao; Teng Wang; Hexi Zhang; Yue Xue; Hongyu Chen; Yongcheng Ding; Ming Lu; Yuyang Song; Guanghe Fu (Environmental Pollution, 2024)

Molybdenum isotopic evidence for the initiation of a big mantle wedge beneath eastern Asia - Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Qi Chen; Jun Yan; Dayu Zhang; Ding-Sheng Jiang (Chemical Geology, 2024)

Dissolved Organic Matters, an Intermediary of the Microbial Community and Potassium Fertilizers in A. carmichaeli rhizosphere Soil - Fei Xia; Meng Fu; Chen Liu; Yulong Li; Yi Qiang; Ding He; Guoyan Zhang; Langjun Cui (Journal of Soil Science and Plant Nutrition, 2024)

Effects of three different protein levels on the growth, gonad development, and physiological biochemistry of female Pengze crucian carp (Carassius auratus var. Pengze) broodstock - Jun Xiao; Fan Long; Liyun Ding; Yuan Yao; Weihua Wu; Yilong Fu; Wenjing Chen (Frontiers in Marine Science, 2024)
A 56-days feeding experiment was conducted to evaluate the effect of dietary protein levels on fish growth, gonad development, and physiological biochemistry of female Pengze crucian carp ( Carassius auratus var. Pengze) broodstock. Three isoenergetic diets were formulated, and the crude protein levels were 26.85%, 35.73% and 44.38%, the lipid levels were 7.39%, 7.92% and 7.91%, respectively. The results showed that the weight gain rate (WGR), the specific growth rate (SGR) and the protein efficiency ratio (PER) of the female Pengze crucian carp broodstock increased significantly and the feed conversion ratio (FCR) decreased significantly when the dietary protein level was 35.73% ( P < 0.05). The WGR, the SGR and the PER were significantly higher in the 35.73% and 44.38% protein groups than in the 26.85% protein group ( P <0.05). Increasing dietary protein levels led to a significant increase in the gonad index and the egg menstrual length of the female Pengze crucian carp broodstock ( P <0.05). The higher protein levels resulted in a significant increase in total amino acids, total essential amino acids, and total nonessential amino acids ( P <0.05). The varying ovaries of each group of total saturated fatty acids, total highly unsaturated fatty acids, and total polyunsaturated fatty acids all increased significantly with increasing protein levels ( P <0.05). Furthermore, the aspartate transaminase (AST), low-density lipoprotein cholesterol (LDLC), and malondialdehyde (MDA) contents in plasma were significantly lower in the 35.73% and 44.38% groups than in the 26.85% group ( P < 0.05). The 35.73% group exhibited the highest plasma superoxide dismutase (SOD) activity,. The plasma vitellogenin (VTG), estradiol 2 (E2), and progesterone (PROG) in plasma of female Pengze crucian carp broodstock were significantly higher in the 35.73% and 44.38% protein groups than in the 26.85% protein group ( P <0.05). The results showed that the addition of an appropriate amount of protein to the feed can significantly improve the growth, gonadal development, and health of female Pengze crucian carp. In this study, the effect of 35.73% protein concentration was better than in the other two groups.

Effect of co-infection with Newcastle disease virus on Mycoplasma gallisepticum pathogenesis in vivo and in vitro - Di Zhang; Jiaxin Ding; Xibing Yu; Jindou Li; Kainan Chen; Yongheng Fu; Zhuang Ding; Xiaohong Xu (Veterinary Microbiology, 2024)

Boron and nitrogen hydrothermal co-doped sludge biochar towards efficiently activate peroxymonosulfate for sulfamethoxazole degradation - Huanhuan Wang; Quanbin Zhang; Huifu Ji; Youqi Zhang; Bo Fu; Yunjie Wu; Yongzhen Ding (Journal of Cleaner Production, 2024)

Discrimination and prediction of Qingzhuan tea storage year using quantitative chemical profile combined with multivariate analysis: Advantages of MRMHR based targeted quantification metabolomics - Zhi-Quan Li; Xiao-Li Yin; Hui-Wen Gu; Zhi-Xin Peng; Baomiao Ding; Zhenshun Li; Ying Chen; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Ultrathin-flexible multifunctional MXene composite hydrogels with good mechanical properties-high strain sensitivity and ultra-broadband EMI shielding performances - Wenchong Ouyang; Lin Mei; Qi Liu; Chengbiao Ding; Yanming Liu; Chengwei Zhao; Limin Xu; Fu Lu; Dongpeng Luo; Chunguang Miao; Yu Bai; Quanming Lu; et al. (Chemical Engineering Journal, 2024)

Promoting the systematic utilization of reclaimed asphalt pavement (RAP) through waste asphalt-derived carbon in batteries applications - Danqing Li; Xin He; Hu Fu; Wenqi Tan; Shigang Lu; Linlin Wang; Mei Ding; Chunhui Gao; Chuankun Jia (Chemical Engineering Journal, 2024)

Active sites of the cobalt catalysts controlled by surface silanols of silicalite-1 in CO2 hydrogenation to ethanol - Xuechun Ding; Jianye Fu; Yuchao Lyu; Lishuang Ma; Yakun Xu; Xinmei Liu (Chemical Engineering Journal, 2024)

Perturbation algorithm for refueling reactivity coefficient in the pebble-bed high temperature reactor - Zhongkai Sheng; Bing Xia; Ding She; Fu Li; Zuoyi Zhang (Annals of Nuclear Energy, 2024)

SlMsrB5-SlGRAS4 involved in methyl jasmonate-mediated ripening and quality of postharvest tomato fruit - Xiaodong Fu; Fujun Li; Maratab Ali; Yanan Song; Jun Ding; Xiangrong Kong; Jing Shang; Xiuming Zhao; Xiaoan Li; Xinhua Zhang (Postharvest Biology and Technology, 2024)

The distribution and fate of pesticides in full-scale drinking water treatment plants - Hui Tao; Junjie Fu; Yunxin Luo; Kailun Sun; Tao Lin; Hang Xu; Mingmei Ding (Journal of Water Process Engineering, 2024)

Reduction of haemoglobin is related to metal mixtures exposure in Chinese preschoolers: Joint effect models - Ye Fu; Minghui He; Yang Liu; Mingzhu Li; Meiqin Zhu; Yan Wang; Wei Lin; Lili Yu; Liting Yang; Yao Zhang; Yanli Liu; Hongxian Ji; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Reproducing surface water isoscapes of δ18O and δ2H across China: A machine learning approach - Huawu Wu; Hongxiang Fan; Jing Li; Fu-Jun Yue; Ergang Lian; Congsheng Fu; Ruiyu Lei; Mengyao Ding; Jinzhao Liu; Xiao-Yan Li (Journal of Hydrology, 2024)

Colorimetric aptasensor utilizing MOF-235 with exceptional peroxidase-like activity for the detection of oxytetracycline residues in raw milk - Long Wang; Xia Lu; Yan Zhang; Yuxin Wang; Yi Ding; Mengjia Liu; Shangchen Fu; Wupeng Ge (Food Chemistry, 2024)

Severe flood modulates the sources and age of dissolved organic carbon in the Yangtze River Estuary - Zhao Liang Chen; Yuanbi Yi; Wenjing Fu; Wenzhao Liang; Penghui Li; Kai Wang; Lixin Zhang; Kejun Dong; Si-Liang Li; Sheng Xu; Ding He (Environmental Research, 2024)

Construction of 2D/2D NH2-TiO2/ReS2 molecular-connected heterojunction to achieve selective carrier transport for photocatalytic hydrogen production - Huihui Weng; Houjiang Liu; Guijun Yang; Jiawei Ding; Chuangchuang Gong; Yuanyuan Fu; Jin Cui; Liying Ma; Chunnian He; Naiqin Zhao; Fang He (Chemical Engineering Journal, 2024)

Reversal of gentamicin sulfate resistance in avian pathogenic Escherichia coli by matrine combined with berberine hydrochloride - Jinwu Meng; Jinxue Ding; Weiran Wang; Bolin Gu; Fanting Zhou; Desheng Wu; Xiang Fu; Jiaguo Liu (Archives of Microbiology, 2024)

SLC11A1 promotes kidney renal clear cell carcinoma (KIRC) progression by remodeling the tumor microenvironment - Ding Wu; Yulin Zhou; Xiuquan Shi; Xiaoming Yi; Zhengcheng Sheng; Li Fan; Jingping Ge; Wen Cheng; Wenquan Zhou; Haowei He; Dian Fu (Toxicology and Applied Pharmacology, 2024)

Polyacrylate modified alkyd hybrid latex with high anti-corrosion performance synthesized via solvent-free and emulsifier-free method - Yan Bao; Rao Fu; Yifan Liu; Ruyue Guo; Ying Ding (Sustainable Chemistry and Pharmacy, 2024)

Ratiometric fluorescence platform for the ultrasensitive detection of kanamycin based on split aptamer co-recognition triggers Mg2+-DNAzyme-driven DNA walker systems - Xia Lu; Long Wang; Guowei Li; Yuxin Wang; Guo Hao; Yi Ding; Mengjia Liu; Shangchen Fu; Liqing Xu; Na Ge; Wupeng Ge (Science of The Total Environment, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

Evolution of pore structure and reactive transport parameters during acid leaching of sandstone uranium ore - Shuai Wang; Meng Lian; Dexin Ding; Guicheng He; Haiying Fu (Hydrometallurgy, 2024)

Integrating untargeted and pseudotargeted metabolomics and network analysis reveals the interventional effects of red yeast rice on rat serum metabolites - Ge Xun; Yingxuan Li; Yifan Zhang; Song Li; Yanhua Gao; Yujuan Chen; Ding Zhang; Hongyang Ni; Fangfang Liu; Yan Fu; Xu Wang; Qiao Wang (Food Bioscience, 2024)

The influence of the preheated PSf substrate on COF-LZU1 layer formation and the performance for salt and pharmaceutical rejection - Fan-xin Kong; Shi-yuan Zhang; Ding-wen Zhang; Ping Xia; Jin-fu Chen (Desalination, 2024)

Experimental data-centric prediction of penetration depth and holding capacity of dynamically installed anchors using machine learning - Yong Fu; Kailin Ding; Congcong Han (Computers and Geotechnics, 2024)

A Li-rich layered oxide cathode with remarkable capacity and prolonged cycle life - Tongxing Lei; Bin Cao; Wenbo Fu; Xiuling Shi; Zhiyu Ding; Qi Zhang; Junwei Wu; Kaikai Li; Tong-Yi Zhang (Chemical Engineering Journal, 2024)

Analysis of historical evolution characteristics and collapse process on July 18, 2023, of a dangerous rock mass at Guanyinyan in Baoxing County, Sichuan Province, China - Xing Wang; Xiaodong Fu; Kai Wu; Haifeng Ding; Wenjie Du; Qian Sheng; Jian Chen (Landslides, 2024)

Associations Between Exposure to Metal Mixtures and Insufficient Bone Strength: A Cross-Sectional Study Among Children Aged 2–6 Years - Yanli Liu; Yan Wang; Ye Fu; Yang Liu; Mingzhu Li; Minghui He; Yao Zhang; Chen Li; Hongcheng Ding; Xiaowen Li; Hongxian Ji; Jing Wang (Exposure and Health, 2024)

Identification of volatile compounds and their bioactivities from unpolar fraction of Alpinia oxyphylla Miq. and mining key genes of nootkatone biosynthesis - Fapetu Kemi Busayo; Jin-Ling Yang; Xu-Po Ding; Ya-Li Wang; Cui-Juan Gai; Fei Wu; Hao-Fu Dai; Wen-Li Mei; Hui-Qin Chen (Natural Product Research, 2024)

Anthropogenic-induced ecological risks on marine ecosystems indicated by characterizing emerging pollutants in Pearl River Estuary, China - He Liu; Bo Zhao; Meng Jin; Rui Wang; Zirong Ding; Xiong Wang; Wenjie Xu; Qianghua Chen; Rizhu Tao; Jianping Fu; Danping Xie (Science of The Total Environment, 2024)

Length-controlled hydrophobic CF3-COF as a highly efficient absorbent coating for dual-mode solid-phase microextraction of sixteen polycyclic aromatic hydrocarbons in water samples - Zirong Lan; Jin Huang; Shanliang Fu; Youwei Chen; Taoyu Meng; Wenli Zhou; Zhou Xu; Maolong Chen; Li Wen; Yunhui Cheng; Li Ding (Science of The Total Environment, 2024)

A comprehensive review of biodetoxification of trichothecenes: Mechanisms, limitations and novel strategies - Yue Qiu; Jiaping Yan; Aodong Yue; Zhongchao Lu; Jianzhuang Tan; Hong Guo; Yuting Ding; Fei Lyu; Yan Fu (Food Research International, 2024)

3D cross-linked POSS-containing borate single ion conductor organic-inorganic hybrid gel electrolytes for dendrite-free lithium metal batteries - Xingfa Zeng; Puyan Huang; Jia Zhou; Xiangrong Wei; Xiao Wang; Liya Chen; Yu Ding; Jifang Fu (Chemical Engineering Journal, 2024)

The investigation of wetting and agglomerating mechanism of short-chain fluorocarbon surfactant suppressing coal dust from macro and molecular scales - Xuhan Ding; Kai Wang; Zhenmin Luo; Qingyun Fu; Tianting Wang; Qian Xu; Xin Yi; Renkun Dai; Haipeng Jiang; Zhenqiang Xing (Chemical Engineering Journal, 2024)

Long-chain acyl-CoA synthetase 4-mediated mitochondrial fatty acid metabolism and dendritic cell antigen presentation - Yan Li; Wenlong Fu; JinYing Xiang; Yinying Ren; Yuehan Li; Mi Zhou; Jinyue Yu; Zhengxiu Luo; Enmei Liu; Zhou Fu; Bo Liu; Fengxia Ding (Inflammation Research, 2024)

Spatial and temporal patterns of above- and below- ground biomass over the Tibet Plateau grasslands and their sensitivity to climate change - Yatang Wu; Fu Li; Jing Zhang; YiLiang Liu; Han Li; Bingrong Zhou; Beibei Shen; Lulu Hou; Dawei Xu; Lei Ding; Shiyang Chen; Xiaoni Liu; et al. (Science of The Total Environment, 2024)

Chemodiversity of organic nitrogen emissions from light-duty gasoline vehicles is governed by engine displacements and driving speed - Huixia Han; Hongxuan Du; Shuang Chen; Yisheng Xu; Lihong Ren; Yu Chen; Yeguang Cai; Kexin Wang; Xinping Yang; Mingliang Fu; Yan Ding; Pingqing Fu (Science of The Total Environment, 2024)

Decolorization and detoxification of Brilliant Crocein GR by a newly enriched thermophilic consortium - Fang Tian; Guang Guo; Weilian Fu; Shiji Li; Keqiang Ding; Feng Yang; Chengyue Liang (Journal of Environmental Management, 2024)

Establishment and characterization of cisplatin-resistant cell lines from canine mammary gland tumors - Mengxin Hu; Jie Li; Yunwei Fu; Enshuang Xu; Ding Li; Siqi Huang; Danning Tong; Shengzi Jin; Tongxu Guan; Yun Liu (Theriogenology, 2024)

Root acquisitive traits mirror the functional modules of root-associated fungi - Gaigai Ding; Wenjing Zeng; Lijuan Sun; Fu-Sheng Chen; Yun Lyu; Jin Xu; Tao Yan; Huimin Wang; Zeqing Ma (Soil Biology and Biochemistry, 2024)

Manure derived hydrochar reduced phosphorus loss risk via an alteration of phosphorus fractions and diversified microbial community in rice paddy soil - Shudong Ding; Jing Li; Yu Wang; Shiying He; Huifang Xie; Haibin Fu; Yanfang Feng; Sabry M. Shaheen; Jörg Rinklebe; Lihong Xue (Science of The Total Environment, 2024)

Microplastics: A potential proxy for tracing extreme flood events in estuarine environments - Hongyu Chen; Yu Cheng; Ying Wang; Yongcheng Ding; Chenglong Wang; Xuguang Feng; Qinya Fan; Feng Yuan; Guanghe Fu; Bingfei Gao; Kai Liu; Xinqing Zou (Science of The Total Environment, 2024)

Effect of increased pCO2 and temperature on the phytoplankton community in the coastal of Yellow Sea - Xiaoting Fu; Jiahui Qin; Changling Ding; Yuqiu Wei; Jun Sun (Science of The Total Environment, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Reconstruction of Holocene precipitation patterns and vegetation evolution in the North China Plain: Deciphering the relative influence of climate and anthropogenic forcing - Wensheng Zhang; Bing Li; Baoshuo Fan; Yuecong Li; Qinghai Xu; Sai Wang; Nan Zhang; Jiaxing Yang; Yang Fu; Guoqiang Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Systematic identification of wheat spike developmental regulators by integrated multi-omics, transcriptional network, GWAS, and genetic analyses - Xuelei Lin; Yongxin Xu; Dongzhi Wang; Yiman Yang; Xiaoyu Zhang; Xiaomin Bie; Lixuan Gui; Zhongxu Chen; Yiliang Ding; Long Mao; Xueyong Zhang; Fei Lu; et al. (Molecular Plant, 2024)

A catchment-wide microplastic pollution investigation of the Yangtze River: The pollution and ecological risk of tributaries are non-negligible - Hongyu Chen; Teng Wang; Yongcheng Ding; Feng Yuan; Hexi Zhang; Chenglong Wang; Yameng Wang; Ying Wang; Yuyang Song; Guanghe Fu; Xinqing Zou (Journal of Hazardous Materials, 2024)

Selective enrichment of virulence factor genes in the plastisphere under antibiotic and heavy metal pressures - Lu Wang; Tian-Lun Zhang; Qian Xiang; Chen-Xi Fu; Min Qiao; Long-Jun Ding; Dong Zhu (Journal of Hazardous Materials, 2024)

Ni-CaO-CaZrO3 bi-functional materials for high purity hydrogen production via sorption enhanced steam reforming of ethanol - Yinxiang Wang; Hui Zhou; Dingding Yao; Gianni Olguin; Haixia Ding; Boyu Qu; Wensheng Xie; Zegang Fu; You Guo; Xin Wang; Aimin Li; Guozhao Ji (Journal of Cleaner Production, 2024)

Meta-analysis to identify inhibition mechanisms for the effects of submerged plants on algae - Xinyu Liu; Tao Sun; Wei Yang; Xiaoxiao Li; Jiewei Ding; Xianting Fu (Journal of Environmental Management, 2024)

Insight into the effect of cultivar and altitude on the identification of EnshiYulu tea grade in untargeted metabolomics analysis - Dan Zou; Xiao-Li Yin; Hui-Wen Gu; Zhi-Xin Peng; Baomiao Ding; Zhenshun Li; Xian-Chun Hu; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Propyl gallate exposure affects the mouse 2-cell stage embryonic development through inducing oxidative stress and autophagy - Sheng-Ji Yang; Fu-Yi Yang; Yi-Nuo Zou; Yong-Sheng Wang; Zhi-Ming Ding; Li-Dan Zhang; Xu Zhou; Ming Liu; Ze-Qun Duan; Li-Jun Huo (Food and Chemical Toxicology, 2024)

Highly efficient solution-processable four-coordinate boron compound: A thermally activated delayed fluorescence emitter with short-lived phosphorescence for OLEDs with small efficiency roll-off - Zhengqin Pan; Jie Pan; Long Sang; Zhenming Ding; Meihua Liu; Laichao Fu; Mengqiu Wang; Xiaokang Huang; Bowen Li; Shaofeng Chen; Dongcheng Chen; Yu Liu; et al. (Chemical Engineering Journal, 2024)

Synthesis of spherical CaO pellets incorporated with Mg, Y, and Ce inert carriers for CO2 capture - Ding Liu; Yingchao Hu; Qiannian Feng; Ruicheng Fu (Environmental Science and Pollution Research, 2024)

Influence of speed measurement method on performance of an electric-drive maize precision planter - Lin Ling; Guangwei Wu; Changkai Wen; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Jianhong Ding; Zhijun Meng; Bingxin Yan (Biosystems Engineering, 2024)

Source identification of sedimentary organic carbon in coastal wetlands of the western Bohai Sea - Juqin Zhang; Qian Hao; Qiang Li; Xiangwei Zhao; Xiaoli Fu; Weiqi Wang; Ding He; Yuan Li; Zhenqing Zhang; Xiaodong Zhang; Zhaoliang Song (Science of The Total Environment, 2024)

Assessment of identification performance for high emission heavy-duty diesel vehicles by means of remote sensing - Han Jiang; Junfang Wang; Miao Tian; Chen Zhao; Yingzhi Zhang; Xiaohu Wang; Jin Liu; Mingliang Fu; Hang Yin; Yan Ding (Science of The Total Environment, 2024)

Integrated transcriptomic, proteomic, and metabolomic approaches reveal the antifungal mechanism of methyl ferulate against Alternaria alternate - Hui Kong; Shuai Ge; Xia Chang; Saiqing Xu; Haishan Xu; Xincheng Fu; Rongrong Wang; Zisheng Luo; Yang Shan; Shenghua Ding (Postharvest Biology and Technology, 2024)

Repeated glacial fluctuations during the Last Glacial Maximum in the southeastern Tibetan Plateau: 10Be surface exposure dating of moraines in the Lahaku Valley, Haizishan Plateau, China - Jiangtao Wang; Weijian Zhou; Guocheng Dong; Feng Xian; Yunchong Fu; Li Zhang; Pengkai Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Hierarchically ordered microporous Ag2S QDs-CoOx/NC nanostructures for enhancing photocatalytic CO2 reduction to chemical fuels - Shengpeng Mo; Lili Huang; Xin Zhao; Jun Li; Xuegang Ding; Xiaobin Zhou; Yanan Zhang; Yinming Fan; Mingming Fu; Hongxiang Zhu; Qinglin Xie; Daiqi Ye (Fuel, 2024)

Effective degradation of phenol by activating PMS with bimetallic Mo and Ni Co-doped g C3N4 composite catalyst: A Fenton-like degradation process promoted by non-free radical 1O2 - Miao Tian; Xuechang Ren; Suying Ding; Ning Fu; Yajun Wei; Zhenyu Yang; Xiaoqing Yao (Environmental Research, 2024)

Ultrathin RhCu bimetallenes for the selective electro-oxidation of glycerol - Qing-Ling Hong; Yue Zhao; Xuan Ai; Yu Ding; Fu-Min Li; Pei Chen; Pu-Jun Jin; Yu Chen (Chemical Engineering Journal, 2024)

Revolutionizing aqueous Zn-ion batteries: Precision control of H2O activity and Zn deposition through ammonium oxalate additive - Wenhao Ding; Guolang Zhou; Xiangjie Guo; Cheng Liu; Tianshi Wang; Yongsheng Fu; Jingzhou Yin; Lili Zhang; Edison Huixiang Ang (Chemical Engineering Journal, 2024)

Long-term impact of nano zero-valent iron on methanogenic activity, microbial community structure, and transcription activity in anaerobic wastewater treatment system - Runhua Su; Huimin Fu; Lili Ding; Bo Fu; Su He; Haijun Ma; Haidong Hu; Hongqiang Ren (Bioresource Technology, 2024)

Atmospheric CO2 controls on the MIS 6 glaciation: 10Be chronology of moraines in the Haizishan area, southeastern Tibetan Plateau - Guocheng Dong; Weijian Zhou; Feng Xian; Yunchong Fu; Li Zhang; Ling Tang; Pengkai Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Garnet geochemistry reveals late-stage oxidation of tin-bearing fractionated granite - Jin-Xiang Li; Lin Ding; Noreen J. Evans; Fang Xu; Wei-Ming Fan; Li-Yun Zhang; Fu-Long Cai; Qiu-Yun Guan; Ya-Hui Yue; Jing Xie (Lithos, 2024)

Analyzing the impact of natural capital on socio- economic objectives under the framework of sustainable development goals - Yating Dai; Yuze Ding; Shuya Fu; Lixin Zhang; Jian Cheng; Daolin Zhu (Environmental Impact Assessment Review, 2024)

Interfacial coordination-assisted construction of mechanically robust, fluorescent and intumescent flame retardant epoxy resins - Xin-Miao Li; Wei-Bin Bai; Yu-Cai Lin; Fu-Chuan Ding; Rong-Kun Jian (Chemical Engineering Journal, 2024)

Unveiling the role of ABI3 and hub senescence-related genes in macrophage senescence for atherosclerotic plaque progression - Yajuan Fu; Juan Zhang; Qiujun Liu; Lan Yang; Qianqian Wu; Xiaomin Yang; Lexin Wang; Ning Ding; Jiantuan Xiong; Yujing Gao; Shengchao Ma; Yideng Jiang (Inflammation Research, 2024)
Background Atherosclerosis, characterized by abnormal arterial lipid deposition, is an age-dependent inflammatory disease and contributes to elevated morbidity and mortality. Senescent foamy macrophages are considered to be deleterious at all stages of atherosclerosis, while the underlying mechanisms remain largely unknown. In this study, we aimed to explore the senescence-related genes in macrophages diagnosis for atherosclerotic plaque progression. Methods The atherosclerosis-related datasets were retrieved from the Gene Expression Omnibus (GEO) database, and cellular senescence-associated genes were acquired from the CellAge database. R package Limma was used to screen out the differentially expressed senescence-related genes (DE-SRGs), and then three machine learning algorithms were applied to determine the hub DE-SRGs. Next, we established a nomogram model to further confirm the clinical significance of hub DE-SRGs. Finally, we validated the expression of hub SRG ABI3 by Sc-RNA seq analysis and explored the underlying mechanism of ABI3 in THP-1-derived macrophages and mouse atherosclerotic lesions. Results A total of 15 DE-SRGs were identified in macrophage-rich plaques, with five hub DE-SRGs (ABI3, CAV1, NINJ1, Nox4 and YAP1) were further screened using three machine learning algorithms. Subsequently, a nomogram predictive model confirmed the high validity of the five hub DE-SRGs for evaluating atherosclerotic plaque progression. Further, the ABI3 expression was upregulated in macrophages of advanced plaques and senescent THP-1-derived macrophages, which was consistent with the bioinformatics analysis. ABI3 knockdown abolished macrophage senescence, and the NF-κB signaling pathway contributed to ABI3-mediated macrophage senescence. Conclusion We identified five cellular senescence-associated genes for atherogenesis progression and unveiled that ABI3 might promote macrophage senescence via activation of the NF-κB pathway in atherogenesis progression, which proposes new preventive and therapeutic strategies of senolytic agents for atherosclerosis.

An Adversarial Single-Domain Generalization Network for Fault Diagnosis of Wind Turbine Gearboxes - Xinran Wang; Chenyong Wang; Hanlin Liu; Cunyou Zhang; Zhenqiang Fu; Lin Ding; Chenzhao Bai; Hongpeng Zhang; Yi Wei (Journal of Marine Science and Engineering, 2023)
In deep learning-based fault diagnosis of the wind turbine gearbox, a commonly faced challenge is the domain shift caused by differing operational conditions. Traditional domain adaptation methods aim to learn transferable features from the source domain and apply them to the target data. However, such methods still require access to target domain data during the training process, which limits their applicability in real-time fault diagnosis. To address this issue, we introduce an adversarial single-domain generalization network (ASDGN). It relies solely on data from a single length of data acquisition in wind turbine fault diagnosis. This novel approach introduces a more flexible and efficient solution to the field of real-time fault diagnosis for wind turbines.

A great start? Sustainability mission statements affect consumer behavior - May-Ching Ding; Yuan Shuh Lii; Kuan Fu Lai (Environment, Development and Sustainability, 2023)

Shikonin promotes ferroptosis in HaCaT cells through Nrf2 and alleviates imiquimod-induced psoriasis in mice - Zhiwei Weng; Hangjie Fu; Zhiguang Huang; Wenxia Li; Yixin Xie; Jianchang Yuan; Bin Ding (Chemico-Biological Interactions, 2023)

Study on Macroscopic Mechanical Behavior and Meso-failure Evolution of Gabbro of Different Particle Sizes - Haifeng Ding; Xiaodong Fu; Qian Sheng; Jian Chen; Chengzeng Yan; Kaiwei Tian; Bo Hu (Rock Mechanics and Rock Engineering, 2023)

A Review of the International Management Practice and Treatment Technology of Solid Waste Containing Perfluorooctane Sulfonic Acid - Jianying Fu; Shengdong Zhang; Mingxiu Zhan; Jinjian Ding; Xu Xu; Wenwen Ye; Hancheng Ma; Tong Chen; Wentao Jiao; Zheng Peng; John P. Giesy (Reviews of Environmental Contamination and Toxicology, 2023)

Responses of bird communities to riparian park habitat factors: a case study in a highly urbanized area of Fuzhou city, China - Dulai Zheng; Peilin Huang; Weizhen Xu; Ziluo Huang; YuJie Zhao; Yinghong Ding; Yuxin Lin; Ruoxian Zheng; Zhipeng Zhu; Ziru Chen; Weicong Fu (Environment, Development and Sustainability, 2023)

Insights from CMIP6 SSP scenarios for future characteristics of propagation from meteorological drought to hydrological drought in the Pearl River Basin - Zhaoqiang Zhou; Yibo Ding; Qiang Fu; Can Wang; Yao Wang; Hejiang Cai; Suning Liu; Shengzhi Huang; Haiyun Shi (Science of The Total Environment, 2023)

Genome-wide characterization of two homeobox families identifies key genes associated with grain-related traits in wheat - Yuting Li; Hongchun Xiong; Huijun Guo; Linshu Zhao; Yongdun Xie; Jiayu Gu; Shirong Zhao; Yuping Ding; Huiyuan Li; Chunyun Zhou; Meiyu Fu; Qingguo Wang; et al. (Plant Science, 2023)

Air pollution outcomes, land misallocation, and the transmission through urban sprawl - Yuwei Wang; Jianshuang Fan; Dongtao Liu; Jian Fu; Liang Ding; Junshen Zhang (Journal of Environmental Management, 2023)

Revealing the chemical differences and their application in the storage year prediction of Qingzhuan tea by SWATH-MS based metabolomics analysis - Zhi-Quan Li; Xiao-Li Yin; Hui-Wen Gu; Dan Zou; Baomiao Ding; Zhenshun Li; Ying Chen; Wanjun Long; Haiyan Fu; Yuanbin She (Food Research International, 2023)

Retrogradation inhibition of wheat starch with wheat oligopeptides - Liuyu Wan; Xuedong Wang; Hongyan Liu; Shensheng Xiao; Wenping Ding; Xiuyun Pan; Yang Fu (Food Chemistry, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Thermodynamic and kinetic analyses of Janus membrane scaling in membrane distillation for zero liquid discharge engineering - Ao Wang; Hang Xu; Jun Ma; Jiawei Fu; Tao Lin; Mingmei Ding (Desalination, 2023)

Analytical solutions for contaminant transport through a GMB/CCL composite liner system considering effective porosity and thermodiffusion - Jin-Wei Qiu; Lu-Sha Jiang; He-Fu Pu; Ding-Bao Song; Ming Min; Jun Tong (Computers and Geotechnics, 2023)

Large scalable, anti-ultraviolet, strong cellulose film with well-defined dual-pores for longtime daytime radiative cooling - Chenyang Cai; Fuling Chen; Zechang Wei; Chunxiang Ding; Yi Chen; Yibo Wang; Yu Fu (Chemical Engineering Journal, 2023)

Amino acids as in-situ electron donors drive medium chain fatty acids production from sludge acidogenic fermentation liquid by electro-fermentation enhancement - Ping Wu; Peng Ding; Qi-hao Cao; Chao Zhang; Bo Fu; Hong-bo Liu; Chong-jun Chen; He Liu (Chemical Engineering Journal, 2023)

In-situ precipitation of ultrafine Mg2Ni particles in Mg-Ni-Ag metal fibers and their hydrogen storage properties - Wenchao Cao; Xin Ding; Ruirun Chen; Jiaxin Zhang; Yong Zhang; Hongxian Shen; Hengzhi Fu (Chemical Engineering Journal, 2023)

Enhancing the stability of antimicrobial peptides: From design strategies to applications - Shenrui Xu; Peng Tan; Qi Tang; Tao Wang; Yakun Ding; Huiyang Fu; Yucheng Zhang; Chenlong Zhou; Mengda Song; Qingsong Tang; Zhihong Sun; Xi Ma (Chemical Engineering Journal, 2023)

A novel “Turn-on” fluorometric assays triggered reaction for β-glucosidase activity based on quercetin derived silicon nanoparticles and its potential use for cell imaging - Yves Iradukunda; Jing-Yan Kang; Xiao-bo Zhao; Stanislas Nsanzamahoro; Xiao-Kang Fu; Jia Liu; Yu-Zhu Ding; Wei Ha; Yan-Ping Shi (Analytica Chimica Acta, 2023)

Current advances in the detection and removal of organic arsenic by metal-organic frameworks - Wen-Qing Ding; Lazhar Labiadh; Lei Xu; Xiao-Ying Li; Chen Chen; Ming-Lai Fu; Baoling Yuan (Chemosphere, 2023)

How internal nutrient loading forms in shallow lakes: Insights from benthic organic matter mineralization - Xiaolong Yao; Runnan Ding; Yongqiang Zhou; Zhengwen Wang; Yanan Liu; Dafang Fu; Lu Zhang (Water Research, 2023)

Priority screening of contaminants of emerging concern in drinking water sources of eastern China: Assessing risks based on exposure-activity ratios (EARs) - Shijiao Ma; Huiyu Dong; Ding Li; Wei Fu; Qinkui Miao; Shengnian Wu; Zhimin Qiang (Science of The Total Environment, 2023)

Catalytic degradation of benzene at room temperature over FeN4O2 sites embedded in porous carbon - Hui Ding; Lingxiao Xue; Jiahao Cui; Yongqiang Wang; Dan Zhao; Xing Zhi; Rui Liu; Jianfeng Fu; Shejiang Liu; Bingfeng Fu; Jiahui Shi; Ximeng Xu; et al. (Journal of Hazardous Materials, 2023)

Profiling of the spatiotemporal distribution, risks, and prioritization of pharmaceuticals and personal care products in coastal waters of the northern Yellow Sea, China - Xiaotong Guo; Min Lv; Lehui Song; Jing Ding; Mingsan Man; Longwen Fu; Shuang Lu; Lijun Hou; Lingxin Chen (Journal of Hazardous Materials, 2023)

How does water diversion affect land use change and ecosystem service: A case study of Baiyangdian wetland, China - Yajing Cai; Panyue Zhang; Qingyan Wang; Yan Wu; Yiran Ding; Mohammad Nabi; Chuan Fu; Hongjie Wang; Qiang wang (Journal of Environmental Management, 2023)

Loading rate effect on the strength of granular material considering particle rotation - Lihong Tong; Li Fu; Changjie Xu; Haibin Ding; Min Xiao (Computers and Geotechnics, 2023)

Cloud Microphysical Processes and Atmospheric Water Budget during the 20 July 2021 Extreme Precipitation Event in Zhengzhou, China - Weixi Shu; Danhong Fu; Hui Xiao; Huiling Yang; Yue Sun; Xueliang Guo; Yang Zhao; Jianfang Ding; Shujing Shen (Journal of Meteorological Research, 2023)

Changes in Atmospheric Circulation during the Winter Regional Extreme Cold Events over China since 1960 - Dongxue Fu; Yihui Ding (Journal of Meteorological Research, 2023)

Effects of Weight Gain During Pregnancy in Normal-Weight Women on Changes in the Gut Microbiota of Pregnant Women in the Third Trimester - Fengping Fu; Fengqin Wang; Jian Ding; Li Xiao; Xia Song (Biochemical Genetics, 2023)

Factors Controlling the Pore Development of Low-Mature Marine–Continental Transitional Shale: A Case Study of the Upper Permian Longtan Shale, Western Guizhou, South China - Manting Zhang; Mingyi Hu; Sile Wei; Quansheng Cai; Wei Fu; Fang Shi; Lei Zhang; Haiyan Ding (Journal of Marine Science and Engineering, 2023)
The Upper Permian Longtan Shale is a significant reservoir in western Guizhou. To clarify the main factors controlling the low-mature marine–continental transitional shale pore development in western Guizhou, pore types were classified with scanning electron microscopy (SEM), and the pore developmental stages and morphological structures were quantitatively characterized by nitrogen adsorption isotherm analyses. Additionally, the qualitative or semi-quantitative relationships between the pore developmental stages and the main controlling factors were established via geochemical analysis. The results showed that the Longtan Shale pores include intergranular pores, intragranular pores, organic pores, and microfractures. The intergranular pore structures were categorized into ink-bottle, slit, layered, and irregular types. The intragranular pores were found to be of the elliptical, nearly circular, ink-bottle, and irregular varieties. The organic pores were categorized into elliptical, bubble-like, and irregular polygonal variants. The microfractures were only of the elongated type. The clay-mineral-related intergranular pores were the predominant pore type. The organic pores were found to be poorly developed. The mesopores were predominant, followed by macropores. The shale pore diameters ranged between 1 nm and 100 nm, and they are characterized by multiple peaks. The specific surface area (SSA) was primarily provided by nanopores in the range of 5 nm to 10 nm, such that the smaller pores provided a greater contribution to the SSA, and they are more conducive to shale gas adsorption and accumulation. Clay mineral content was the dominant internal factor controlling pore development and the SSA, with the illite–smectite mixed layer being the most obvious controlling factor. While too low or too high clay mineral content is adverse to macropore development, brittle mineral content, carbonate mineral content, and total organic carbon (TOC) content are adverse to pore development and the SSA. Thermal maturity has no remarkable control effect on pore volume and the SSA of non-organic pores.

Soil organic carbon stability and exogenous nitrogen fertilizer influence the priming effect of paddy soil under long-term exposure to elevated atmospheric CO2 - Hongyan Yu; Mixue Han; Chuang Cai; Fu Lv; Yue Teng; Luyi Zou; Guoqing Ding; Xuejia Bai; Junhou Yao; Kang Ni; Chunwu Zhu (Environmental Science and Pollution Research, 2023)

Reduction potential of vehicular emission in Chengdu, China: A case study of COVID-19 - Xinping Yang; Hefeng Zhang; Wei Li; Hong Tian; Yongdong Wang; Jing Zhou; Ze Bao; Xiaorui Chen; Teng Xiao; Yunjing Wang; Mingliang Fu; Xian Wu; et al. (Urban Climate, 2023)

Identification and contribution of potential sources to atmospheric lead pollution in a typical megacity: Insights from isotope analysis and the Bayesian mixing model - Wen-Jing Dai; Xiao-Dong Li; Yu-Cong Fu; Shi-Yuan Ding; Qin-Kai Li; Zhi-Qi Zhao (Science of The Total Environment, 2023)

Vegetation structural shift tells environmental changes on the Tibetan Plateau over 40 years - Yanfen Wang; Kai Xue; Ronghai Hu; Boyang Ding; Hong Zeng; Ruijin Li; Bin Xu; Zhe Pang; Xiaoning Song; Congjia Li; Jianqing Du; Xiuchun Yang; et al. (Science Bulletin, 2023)

ML based approach for inverting penetration depth of SAR signals over large desert areas - Jun Zhu; Guanxin Liu; Rong Zhao; Xiaoli Ding; Haiqiang Fu (Remote Sensing of Environment, 2023)

Nitrogen cycle pattern variations during seawater-groundwater-river interactions enhance the nitrogen availability in the coastal earth critical zone - Guiyao Xiong; Xiaobin Zhu; Mengwen Liu; Yun Yang; Guangquan Chen; Tengfei Fu; Runtian Ding; Xingyong Xu; Jichun Wu (Journal of Hydrology, 2023)

Exhaust aftertreatment device-derived ammonia emissions from conventional and hybrid light-duty gasoline vehicles over different driving cycles - Han Jiang; Hefeng Zhang; Haiguang Zhao; Mingliang Fu; Yunjing Wang; Xian Wu; Xinping Yang; Jianglin Ji; Hang Yin; Yan Ding (Journal of Hazardous Materials, 2023)

Decarbonizing ceramic industry: Technological routes and cost assessment - Kai Ding; Anjie Li; Jingxiang Lv; Fu Gu (Journal of Cleaner Production, 2023)

Effects of garlic peptides on rheology, moisture, microstructure, gluten distribution, and baking properties of dough - Xiaorong Liu; Qianran Xie; Dezheng Liu; Yuting Zhang; Shensheng Xiao; Wenping Ding; Yang Fu; Xuedong Wang (Journal of Cereal Science, 2023)

Gellan gum-based functional films integrated with bacterial cellulose and nano-TiO2/CuO improve the shelf life of fresh-cut pepper - Fei Chen; Xia Chang; Haishan Xu; Xincheng Fu; Shenghua Ding; Rongrong Wang (Food Packaging and Shelf Life, 2023)

Combined effects of climate change on urban resilience in the Tibetan Plateau - Lingna Liu; Zhicong Zhang; Shaoheng Ding; Feng Yang; Tongrong Fu (Environmental Impact Assessment Review, 2023)

Electrospun polyvinyl alcohol-chitosan dressing stimulates infected diabetic wound healing with combined reactive oxygen species scavenging and antibacterial abilities - Haibing Liu; Rong Chen; Pinkai Wang; Jinlang Fu; Zinan Tang; Jiajun Xie; Yanhong Ning; Jian Gao; Qiang Zhong; Xin Pan; Ding Wang; Mingyuan Lei; et al. (Carbohydrate Polymers, 2023)

Polysaccharides in contact lenses: From additives to bulk materials - Qiang Zhu; Qiao Zhang; Ding-Yi Fu; Gaoxing Su (Carbohydrate Polymers, 2023)

Theoretical modeling of molecular fractionation of dissolved organic matter on ferrihydrite and its impact on proton and metal binding properties - Xinyi Huang; Yuzhen Liang; Qianting Ye; Zecong Ding; Fu Liu; Zhenqing Shi (Science of The Total Environment, 2023)

Production of single-crystal Cu plates by electrodeposition on high-index Cu foils - Xingguang Li; Zhihong Zhang; Zhibin Zhang; Jinzong Kou; Muhong Wu; Mengze Zhao; Ruixi Qiao; Zhiqiang Ding; Zhiqiang Zhang; Fang Liu; Xiaonan Yang; Dingxin Zou; et al. (Science Bulletin, 2023)

Identification and functional study of detoxification-related genes in response to tolfenpyrad stress in Glyphodes pyloalis Walker (Lepidoptera: Pyralidae) - Xin Pan; Jian-Hao Ding; Shuai-Qi Zhao; Hui-Cong Shi; Wang-Long Miao; Fu-An Wu; Sheng Sheng; Wei-Hong Zhou (Pesticide Biochemistry and Physiology, 2023)

Highly efficient recovery of viscous oil through nondispersive solvent extraction using polydopamine modified PVDF Janus membrane - Mengmeng Liu; Jianqiang Wang; Yajie Ding; Yong Zhou; Fu Liu (Journal of Water Process Engineering, 2023)

Energy analysis and research on injection control parameter influence mechanism of air assisted spray system - Jin Zhao; Haoyu Ding; Luxin Fu; Bing Bai; Dapeng Zhang; Jun Liu; Xu He (Fuel, 2023)

A study on the analysis of dynamical transmission behavior and mining key monitoring stations in PM and O3 networks in the Beijing-Tianjin-Hebei region of China - Xiaofei Shi; Bo Li; Donglei Fu; Jiao Bai; Stephen Dauda Yabo; Kun Wang; Xiaoxiao Gao; Jie Ding; Hong Qi (Environmental Research, 2023)

TiO2 nanoparticles affect spermatogenesis and adhesion junctions via the ROS-mediated mTOR signalling pathway in Eriocheir sinensis testes - Lan-Min Wang; Ke Jia; Zhen-Fang Li; Hong-Yu Qi; Ding-Xi Liu; Ya-Jing Liang; Shuang-Li Hao; Fu-Qing Tan; Wan-Xi Yang (Environmental Pollution, 2023)

ED-DQN: An event-driven deep reinforcement learning control method for multi-zone residential buildings - Qiming Fu; Zhu Li; Zhengkai Ding; Jianping Chen; Jun Luo; Yunzhe Wang; You Lu (Building and Environment, 2023)

Hsa-miR-195-5p Inhibits Autophagy and Gemcitabine Resistance of Lung Adenocarcinoma Cells via E2F7/CEP55 - Linhai Fu; Zhupeng Li; Yuanlin Wu; Ting Zhu; Zhifeng Ma; Lingjun Dong; Jianyi Ding; Chu Zhang; Guangmao Yu (Biochemical Genetics, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Comparative analysis of domestic and foreign coal mine safety supervision modes based on knowledge map - Xiangchun Li; Dengyu Xu; Cui Ding; Weidong Lu; Mengya Wang; Wenyu Yan; Yukun Fu; Shuang Zhang; Yi Li (Environmental Science and Pollution Research, 2023)

Effects of microplastics on the toxicity of co-existing pollutants to fish: A meta-analysis - Feng Yuan; Hongyu Chen; Yongcheng Ding; Ying Wang; Qihang Liao; Teng Wang; Qinya Fan; Ziyue Feng; Chuchu Zhang; Guanghe Fu; Xinqing Zou (Water Research, 2023)

RETRACTED: Using organo–mineral complex material to prevent the migration of soil Cd and As into crops: An agricultural practice and chemical mechanism study - Xuehao Zheng; Miaomiao Zhao; Lina Sun; Luge Rong; Bin Zhang; Fengjie Fan; Fangxi Zhang; Chengqiang Shu; Xiangyu Shi; Dan Zhao; Jianfeng Fu; Yuxin Zhang; et al. (Science of The Total Environment, 2023)

Hypothermic neuroprotection by targeted cold autologous blood transfusion in a non-human primate stroke model - Jian Chen; Shuaili Xu; Hangil Lee; Longfei Wu; Xiaoduo He; Wenbo Zhao; Mo Zhang; Yanhui Ma; Yuchuan Ding; Yongjuan Fu; Chuanjie Wu; Ming Li; et al. (Science Bulletin, 2023)

Efficient removal mechanism of an electrical conductivity-enhanced constructed wetlands under particle accumulated conditions - Jiajun Wang; Qin Zhang; Ya-nan Zhang; Mingming Fu; Yanli Ding; Xutao Gao; Lanqian Qin; Ronghua Wang; Shaoyuan Bai (Journal of Cleaner Production, 2023)

BCE-Net: Reliable building footprints change extraction based on historical map and up-to-date images using contrastive learning - Cheng Liao; Han Hu; Xuekun Yuan; Haifeng Li; Chao Liu; Chunyang Liu; Gui Fu; Yulin Ding; Qing Zhu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Scaling analysis of diffusion–reaction process in proton exchange membrane fuel cell with the second Damköhler number - Yujie Ding; Xi Fu; Liangfei Xu; Jianqiu Li; Minggao Ouyang; Huijun Wu (Chemical Engineering Journal, 2023)

Fine mapping and genetic analysis identified a C2H2-type zinc finger as a candidate gene for heading date regulation in wheat - Yuting Li; Hongchun Xiong; Huijun Guo; Chunyun Zhou; Meiyu Fu; Yongdun Xie; Linshu Zhao; Jiayu Gu; Shirong Zhao; Yuping Ding; Chaojie Wang; Ahsan Irshad; et al. (Theoretical and Applied Genetics, 2023)

Effects of intra-year precipitation variability on shrub community productivity depend on the annual total rainfall - Ming-Han Yu; Ying-Ying He; Fu-Chong Zhang; Guo-dong Ding; Chun-Yuan Wang (Plant and Soil, 2023)

Transient Receptor Potential Mucolipin-1 Participates in Intracerebral Hemorrhage-Induced Secondary Brain Injury by Inducing Neuroinflammation and Neuronal Cell Death - Jinzhao Shi; Xiang Li; Jiasheng Ding; Jinrong Lian; Yi Zhong; Haiying Li; Haitao Shen; Wanchun You; Xi’an Fu; Gang Chen (NeuroMolecular Medicine, 2023)

Revealing the potential of organo-mineral complexes in agricultural application using bibliometrics - Xuehao Zheng; Belay Tafa Oba; Han Wang; Bin Zhang; Chengqiang Shu; Yan Song; Jianfeng Fu; Shejiang Liu; Yuxin Zhang; Nan Dai; Dan Song; Hui Ding (Journal of Cleaner Production, 2023)

Experimental and simulation study on hydroxyl group promoting low-temperature oxidation of active groups in coal - Xun Zhang; Bing Lu; Jing Zhang; Xiang Fu; Hanzhong Deng; Ling Qiao; Cong Ding; Fei Gao (Fuel, 2023)

Transcriptomics and gas chromatography-mass spectrometry metabolomics reveal the mechanism of heat shock combined with 1-methylcyclopropene to regulate the cuticle wax of jujube fruit during storage - Shuai Ge; Rongrong Wang; Lvzhu Yang; Hui Kong; Xia Chang; Xincheng Fu; Yang Shan; Shenghua Ding (Food Chemistry, 2023)

Impacts on real-world extra cold start emissions: Fuel injection, powertrain, aftertreatment and ambient temperature - Xian Wu; Haiguang Zhao; Liqiang He; Xinping Yang; Han Jiang; Mingliang Fu; Hang Yin; Yan Ding (Environmental Pollution, 2023)

Hollow cavity engineering of MOFs-derived hierarchical MnOx structure for highly efficient photothermal degradation of ethyl acetate under light irradiation - Jun Li; Shengpeng Mo; Xuegang Ding; Lili Huang; Xiaobin Zhou; Yinming Fan; Yanan Zhang; Mingming Fu; Qinglin Xie; Daiqi Ye (Chemical Engineering Journal, 2023)

Soil nitrogen transformation in different land use and implications for karst soil nitrogen loss controlling - Zhong-Jun Wang; Fu-Jun Yue; Li-Li Xue; Yu-Chun Wang; Cai-Qing Qin; Jie Zeng; Hu Ding; Yu-Cong Fu; Si-Liang Li (CATENA, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

In-cloud scavenging of chemically segregated particle types by individual particle observation - Yuxiang Yang; Xiaocong Peng; Guohua Zhang; Xiaodong Hu; Ziyong Guo; Wei Sun; Yuzhen Fu; Feng Jiang; Jie Ou; Xiang Ding; Xinming Wang; Xinhui Bi (Applied Geochemistry, 2023)

Biogenic emissions-related ozone enhancement in two major city clusters during a typical typhoon process - Jiawei Xu; Derong Zhou; Jian Gao; Xin Huang; Likun Xue; Juntao Huo; Qingyan Fu; Aijun Ding (Applied Geochemistry, 2023)

Long-term cover cropping improved soil bacterial community and soil multifunctionality in a Carya cathayensis plantation - Yingbing Hu; Jin Jin; Kai Ding; Zihao Ye; Xiaoxuan Wang; Kumuduni Niroshika Palansooriya; Weijun Fu; Jiasen Wu (Agriculture, Ecosystems & Environment, 2023)

Green finance network evolution and prediction: fresh evidence from China - Rui Ding; Yiming Du; Linyu Du; Jun Fu; Shihui Chen; Kexin Wang; Wenqian Xiao; Lina Peng; Juan Liang (Environmental Science and Pollution Research, 2023)

Multi-scale spectral-spatial dual-transformer network for hyperspectral image classification - Zhaojie Pan; Sunjinyan Ding; Genyun Sun; Aizhu Zhang; Xiuping Jia; Hang Fu (International Journal of Remote Sensing, 2023)

Timing and seismic origin of the historic Luanshibao rock avalanche in the Maoyaba basin, SE Tibetan Plateau: New evidence from 10Be exposure-ages - Jiangtao Wang; Weijian Zhou; Guocheng Dong; Feng Xian; Yunchong Fu; Li Zhang; Ling Tang; Pengkai Ding; Guoqing Zhao (Quaternary Geochronology, 2023)

Preparation of a g-C3N4/Ag3PO4 composite Z-type photocatalyst and photocatalytic degradation of Ofloxacin: Degradation performance, reaction mechanism, degradation pathway and toxicity evaluation - Renhua Chen; Suying Ding; Ning Fu; Xuechang Ren (Journal of Environmental Chemical Engineering, 2023)

Molecular insights into enhanced nitrogen removal induced by trace fluoroquinolone antibiotics in an anammox system - Xuejiao Qiao; Chenkun Fu; Yizhen Chen; Fang Fang; Yaoyu Zhang; Lingyun Ding; Kai Yang; Baozhu Pan; Nan Xu; Ke Yu; Huchun Tao; Lijuan Zhang (Bioresource Technology, 2023)

How do montane plants manage to survive? Inferring from non-structural carbohydrates - Wensheng Chen; Huihui Ding; Jiangrong Li; Fangwei Fu; Yueyao Li; Siying Xiao; Di Xu; Jie Lu; Jiangping Fang (Trees, 2023)

New hydrous phases in the Al2O3-SiO2-H2O system under the mantle transition zone conditions - Baoyun Wang; Jin Liu; Suyu Fu; Pu Xiao; Li Li; Xing Ding; Wansheng Xiao (Science China Earth Sciences, 2023)

Inhibition mechanisms of urea combined with nitrification on cadmium uptake by rice (Oryza sativa L.) seedlings - Li Li; Yuling Liu; Shijing Zhang; Siduo Ding; Xin Fu; Qingru Zeng; Liang Peng; Si Luo (Plant and Soil, 2023)

Repetitive transcranial magnetic stimulation enhances the neuronal excitability of mice by regulating dynamic characteristics of Granule cells’ Ion channels - Haijun Zhu; Xiaonan Yin; Huilan Yang; Rui Fu; Wentao Hou; Chong Ding; Guizhi Xu (Cognitive Neurodynamics, 2023)

Constitutive model for Ya’an mudstone based on mesoscopic breakage mechanism - Yun-yong He; Cong Chen; Fu-ming Wang; Cheng-chao Guo; Bo Xiang; Di Yu; En-long Liu; Chun Ding (Journal of Mountain Science, 2023)

Spatiotemporal analysis and prediction of water quality in Pearl River, China, using multivariate statistical techniques and data-driven model - HaoNan Ding; Xiaojun Niu; Dongqing Zhang; Mengyu Lv; Yang Zhang; Zhang Lin; Mingli Fu (Environmental Science and Pollution Research, 2023)

Deciphering roles of microbiota in arsenic biotransformation from the earthworm gut and skin - Hong-Tao Wang; Zong-Zheng Liang; Jing Ding; Gang Li; Sheng-Lei Fu; Dong Zhu (Journal of Hazardous Materials, 2023)

Heavy-metal resistant bio-hybrid with biogenic ferrous sulfide nanoparticles: pH-regulated self-assembly and wastewater treatment application - Xian-Zhong Fu; Jie Wu; Jie Li; Jian Ding; Shuo Cui; Xue-Meng Wang; Yun-Jie Wang; Hou-Qi Liu; Xin Deng; Dong-Feng Liu; Wen-Wei Li (Journal of Hazardous Materials, 2023)

Perfluorooctanoic acid induces tight junction injury of Sertoli cells by blocking autophagic flux - Yuan Yang; Guoqing Fu; Xueyi Zhao; Xiaoping Wu; Kaili Zhu; Shangyu Liu; Ding Yuan; Jie Wu; Ting Wang; Changcheng Zhang; Haixia Zhao (Food and Chemical Toxicology, 2023)

Tailoring the crumpled structures of a polyamide membrane with a heterostructural MXene-TiO2 interlayer for high water permeability - Jiawei Fu; Hang Xu; Tao Lin; Ao Wang; Anqi Wang; Chen Yao; Weihang Chen; Mingmei Ding; Chunxia Geng; Li Gao (Desalination, 2023)

UV-Laser ablation enhanced Joule-heating catalyst support for electrified MSR in microreactor - Xinying Li; Ding Yuan; Tian Xie; Quancong Zhang; Wenjun Xu; Ting Fu; Xuyang Chu; Tao Luo; Linjing Wu; Wei Zhou (Chemical Engineering Journal, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

How anaerobic sludge microbiome respond to different concentrations of nitrite, nitrate, and ammonium ions: a comparative analysis - Runhua Su; Lina Zhou; Lili Ding; Bo Fu; Huimin Fu; Yanan Shuang; Lin Ye; Haidong Hu; Haijun Ma; Hongqiang Ren (Environmental Science and Pollution Research, 2023)

The ester derivatives of ferulic acid exhibit strong inhibitory effect on the growth of Alternaria alternata in vitro and in vivo - Hui Kong; Xincheng Fu; Xia Chang; Zemin Ding; Yang Yu; Haishan Xu; Rongrong Wang; Yang Shan; Shenghua Ding (Postharvest Biology and Technology, 2023)

Ag-Fe3O4 nanozyme with peroxidase-like activity for colorimetric detection of sulfide ions and dye degradation - Yong Wang; Yue Ding; Yiyun Tan; Xiaohui Liu; Lixian Fu; Weixia Qing (Journal of Environmental Chemical Engineering, 2023)

Ultrasonication significantly enhances grafting efficiency of chitosan-ferulic acid conjugate and improves its film properties under Fenton system - Haishan Xu; Xincheng Fu; Hui Kong; Fei Chen; Xia Chang; Zemin Ding; Rongrong Wang; Yang Shan; Shenghua Ding (Food Research International, 2023)

A green and designable natural deep eutectic solvent-based supramolecular solvents system: Efficient extraction and enrichment for phytochemicals - Zi-Hui Cai; Jian-Dong Wang; Lin Liu; Liu-Ding Ruan; Qi Gu; Xin-Yu Yan; Li-Na Fu; Peng-Quan Zhao; Su Zhang; Yu-Jie Fu (Chemical Engineering Journal, 2023)

Elevational distribution patterns and drivers of soil microbial diversity in the Sygera Mountains, southeastern Tibet, China - Fangwei Fu; Jiangrong Li; Shuaifeng Li; Wensheng Chen; Huihui Ding; Siying Xiao; Yueyao Li (CATENA, 2023)

Estimation of Crack Initiation Stress Based on Axial Crack Strain Expansion Rate - Dongsheng Wen; Xinzhi Wang; Haozhen Ding; Zhibin Fu (Rock Mechanics and Rock Engineering, 2023)

AIFM1 variants associated with auditory neuropathy spectrum disorder cause apoptosis due to impaired apoptosis-inducing factor dimerization - Yue Qiu; Hongyang Wang; Huaye Pan; Jing Guan; Lei Yan; Mingjie Fan; Hui Zhou; Xuanhao Zhou; Kaiwen Wu; Zexiao Jia; Qianqian Zhuang; Zhaoying Lei; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Human factors engineering of BCI: an evaluation for satisfaction of BCI based on motor imagery - Xiaotong Lyu; Peng Ding; Siyu Li; Yuyang Dong; Lei Su; Lei Zhao; Anmin Gong; Yunfa Fu (Cognitive Neurodynamics, 2023)

Cognitive changes are associated with increased blood-brain barrier leakage in non-brain metastases lung cancer patients - Da-Fu Zhang; Zhen-Hui Li; Zhi-Ping Zhang; Yin-Fu He; Bin-Li Shang; Xiu-Feng Xu; Ying-Ying Ding; Yu-Qi Cheng (Brain Imaging and Behavior, 2023)
To explore the relationship between cognitive function and blood–brain barrier leakage in non-brain metastasis lung cancer and healthy controls. 75 lung cancers without brain metastasis and 29 healthy controls matched with age, sex, and education were evaluated by cognitive assessment, and the Patlak pharmacokinetic model was used to calculate the average leakage in each brain region according to the automated anatomical labeling atlas. After that, the relationships between cognitive and blood–brain barrier leakage were evaluated. Compared with healthy controls, the leakage of bilateral temporal gyrus and whole brain gyrus were higher in patients with lung cancers ( P < 0.05), mainly in patients with advanced lung cancer ( P < 0.05), but not in patients with early lung cancer ( P > 0.05). The cognitive impairment of advanced lung cancers was mainly reflected in the damage of visuospatial/executive, and delayed recall. The left temporal gyrus with increased blood–brain barrier leakage showed negative correlations with delayed recall (r = -0.201, P = 0.042). An increase in blood–brain barrier leakage was found in non-brain metastases advanced lung cancers that corresponded to decreased delayed recall. With progression in lung cancer staging, blood–brain barrier shows higher leakage and may lead to brain metastases and lower cognitive development.

Effects of Soil Hydraulic Properties on Soil Moisture Estimation - Xiaolei Fu; Haishen Lyu; Zhongbo Yu; Xiaolei Jiang; Yongjian Ding; Donghai Zheng; Jinbai Huang; Hongyuan Fang (Journal of Meteorological Research, 2023)

Spatial-temporal variations of short-lived mesoscale eddies and their environmental effects - Shidong Liu; Jishang Xu; Lulu Qiao; Guangxue Li; Jinghao Shi; Dong Ding; Di Yu; Xue Yang; Yufeng Pan; Siyu Liu; Xiaoshuang Fu (Frontiers in Marine Science, 2023)
Mesoscale eddies (MEs) affect the transport and redistribution of oceanic matter and energy. The long-lived and long-distance propagation of individual eddies has garnered extensive attention; however, short-lived MEs (< 7 days) have been widely overlooked. In this study, the basic features of short-lived MEs and their spatial-temporal variations in a tropical eddy-rich region were extracted and analyzed for the first time. Short-lived cyclonic and anticyclonic eddies (CEs/AEs) were found to be widespread in two eddy belts in the tropical region of the western Pacific warm pool (WPWP). The CEs and AEs were formed by the shear instability between large-scale circulations and were distributed on both sides of the North Equatorial Countercurrent, with significant differences in spatial distribution. The variations in sea surface temperature, mixed layer depth, and surface chlorophyll-a concentration in the core of the WPWP were spatially and temporally related to the development of the two eddy belts. This new insight into short-lived MEs in the tropical region contributes to our current understanding of ocean eddies. The potential impacts of short-lived MEs on climate change, global air–sea interactions, and tropical cyclone formation should receive adequate attention and further assessment in future research.

Enhanced high-salinity brines treatment using polyamide nanofiltration membrane with tunable interlayered MXene channel - Ao Wang; Hang Xu; Jiawei Fu; Tao Lin; Jun Ma; Mingmei Ding; Li Gao (Science of The Total Environment, 2023)

Recent advances and perspectives towards emission inventories of mobile sources: Compilation approaches, data acquisition methods, and case studies - Han Jiang; Hefeng Zhang; Mingliang Fu; Zhihui Huang; Hong Ni; Hang Yin; Yan Ding (Journal of Environmental Sciences, 2023)

Study on the quality characteristics of hot-dry noodles by microbial polysaccharides - Yixuan Liu; Xiaorong Liu; Liuyu Wan; Peng Xu; Xiaoyi Deng; Beibei Ding; Xuedong Wang; Yang Fu (Food Research International, 2023)

Geographical variation in the effect of ambient temperature on infectious diarrhea among children under 5 years - Hao Zheng; QingQing Wang; Jianguang Fu; Zhen Ding; Jian Cheng; Zhiwei Xu; Yan Xu; Yankai Xia (Environmental Research, 2023)

Can phosphobacteria simultaneously achieve phosphorus recovery and Pb2+ removal from wastewater by biomineralization? - Pei Zhang; Yi-Min Ding; Tian-Lei Zhao; Yu-Han Wang; Qi-Zhi Yao; Sheng-Quan Fu; Gen-Tao Zhou (Chemical Engineering Journal, 2023)

Effect of natural organic matter on Cr(VI) reduction by reduced nontronite - Liyan Deng; Fu Liu; Zecong Ding; Yuzhen Liang; Zhenqing Shi (Chemical Geology, 2023)

Responses of soil carbon and nitrogen mineralization to nitrogen addition in a semiarid grassland: The role of season - Xiaobo Yuan; Decao Niu; Ding Guo; Hua Fu (CATENA, 2023)

Using whole exome sequencing to identify susceptibility genes associated with nonsyndromic cleft lip with or without cleft palate - Zhenzhen Fu; Jin Yue; Lingfa Xue; Yaoxiang Xu; Qian Ding; Wenlin Xiao (Molecular Genetics and Genomics, 2023)

Arylation of indole at C2 catalyzed by palygorskite grafted covalent organic frameworks supported palladium catalyst - Ning Ding; Shang Wu; Qiang Hu; Jutao Liu; Penghui Zhang; Shuaishuai Fu; Huanlei Zhao; Hong Zhang; Fenping Yin; Quanlu Yang (Applied Clay Science, 2023)

Distribution of organophosphate ester fractions in sediment of the Eastern China Marginal Seas and the influencing factors - Qinya Fan; Hongyu Chen; Qihang Liao; Chuchu Zhang; Yongcheng Ding; Xinqing Zou; Guanghe Fu (Environmental Science and Pollution Research, 2022)

Remediation of uranium-contaminated acidic red soil by rice husk biochar - Haiying Fu; Shuai Wang; Hui Zhang; Zhongran Dai; Guicheng He; Guangyue Li; Dexin Ding (Environmental Science and Pollution Research, 2022)

Efficient adsorption of Cr(VI) in acidic environment by nano-scaled schwertmannite prepared through pH regulation: characteristics, performances, and mechanism - Baoting Ding; Xiaomeng Wang; Kun Feng; Jingran Fu; Jianru Liang; Lixiang Zhou (Environmental Science and Pollution Research, 2022)

Genomic characterization and pathogenicity analysis of a porcine deltacoronavirus strain isolated in western China - Zemei Wang; Shuxian Li; Yongheng Shao; Yabin Lu; Chen Tan; Yaru Cui; Guangming Ding; Yuguang Fu; Guangliang Liu; Jianing Chen; Yonghao Hu (Archives of Virology, 2022)

The Dynamic Deformation Properties of Rock Materials Under Different Types of Seismic Load - Yongqiang Zhou; Qian Sheng; Xiaodong Fu; Haifeng Ding (Rock Mechanics and Rock Engineering, 2022)

Application of an improved hollow fiber liquid phase microextraction technique coupled to LC-MS/MS to studying migration of fluorescent whitening agents from plastic food contact materials - Wen-Li Zhou; Li Ding; Yun-Hui Cheng; Zhou Xu; Mao-Long Chen; Xian-Shu Fu (Food Additives & Contaminants: Part A, 2022)

Oct4 facilitates chondrogenic differentiation of mesenchymal stem cells by mediating CIP2A expression - Lexiang Li; Qiwei Fu; Jiahua Shao; Bo Wang; Zheru Ding; Shuai Yuan; Jinhui Peng; Wei Xin; Jun Zhu; Yi Chen (Cell and Tissue Research, 2022)

Transboundary watershed pollution control and product market competition with ecological compensation and emission tax: a dynamic analysis - Yongxi Yi; Caini Ding; Chunyan Fu; Yuqiong Li (Environmental Science and Pollution Research, 2022)

A Significant Fluorescent Aptamer Sensor Based on Carbon Dots and Graphene Oxide for Highly Selective Detection of Progesterone - Hanyue Cui; Huan Lu; Jing Yang; Yao Fu; Yan Huang; Li Li; Yaping Ding (Journal of Fluorescence, 2022)

Dexmedetomidine post-conditioning alleviates myocardial ischemia–reperfusion injury in rats by ferroptosis inhibition via SLC7A11/GPX4 axis activation - Peng Yu; Jing Zhang; Yi Ding; Dandan Chen; Haijian Sun; Fenglai Yuan; Siyuan Li; Xiaozhong Li; Pingping Yang; Linghua Fu; Shuchun Yu; Jiru Zhang (Human Cell, 2022)

NPC1-regulated dynamic of clathrin-coated pits is essential for viral entry - Guoli Li; Bingqian Su; Pengfei Fu; Yilin Bai; Guangxu Ding; Dahua Li; Jiang Wang; Guoyu Yang; Beibei Chu (Science China Life Sciences, 2022)

Identification and Characterization of Immunoglobulin T Heavy Chain in Large Yellow Croaker (Larimichthys crocea) - Yan Teng; Qiuling Fu; Yuanzhen Tan; Yangyang Ding; Yang Ding; Xinhua Chen (Fishes, 2022)
Three immunoglobulin (Ig) isotypes have been identified in teleosts, IgM, IgD, and IgT or IgZ. IgT, a new teleost Ig isotype, plays a vital role in mucosal immunity. However, information on molecular and functional characteristics of fish IgT is still limited. In this study, an IgT heavy chain (LcIgT) gene was cloned and characterized in large yellow croaker (Larimichthys crocea). Complete cDNA of LcIgT was 1930 bp in length, encoding a protein of 554 amino acids. The deduced LcIgT contains a VH region and only three CH regions (CH1, CH2, CH4), but no transmembrane region was predicted. Phylogenetic analysis showed that IgT heavy chain sequences from all fish species are grouped together. Homology comparison showed that LcIgT shares the highest amino acid identity of 58.73% with IgT heavy chain in Scophthalmus maximus. The VH domain of LcIgT has the highest identity of 72.50% with that of Scophthalmus maximus IgT. Relatively, each constant domain of LcIgT exhibits the highest amino acid identity with that of IgT in Oreochromis niloticus (67.61% identity for CH1, 61.11% identity for CH2, and 63.74% identity for CH4). LcIgT was constitutively expressed in various tissues tested, with the highest levels in mucosa-associated tissues such as gills and skin. After Cryptocaryon irritans infection, the mRNA levels of LcIgT were significantly up-regulated in the spleen (3.27-fold) at 4 d, in the head kidney (3.98-fold) and skin (2.11-fold) at 7 d, and in gills (4.45-fold) at 14 d. The protein levels in these detected tissues were all significantly up-regulated; the peak of its up-regulation was 6.33-fold at 28d in gills, 3.44-fold at 7d in skin, and 3.72-fold at 14d in spleen. These results showed that IgT response could be simultaneously induced in both systemic and mucosal tissues after parasitic infection and that IgT may be involved in systemic immunity and mucosal immunity against parasitic infection.

A community effort to assess and improve computerized interpretation of 12-lead resting electrocardiogram - Zijian Ding; Guijin Wang; Huazhong Yang; Ping Zhang; Dapeng Fu; Zhen Yang; Xinkang Wang; Xia Wang; Zhourui Xia; Chiming Zhang; Wenjie Cai; Binhang Yuan; et al. (Medical & Biological Engineering & Computing, 2022)
Computerized interpretation of electrocardiogram plays an important role in daily cardiovascular healthcare. However, inaccurate interpretations lead to misdiagnoses and delay proper treatments. In this work, we built a high-quality Chinese 12-lead resting electrocardiogram dataset with 15,357 records, and called for a community effort to improve the performances of CIE through the China ECG AI Contest 2019. This dataset covers most types of ECG interpretations, including the normal type, 8 common abnormal types, and the other type which includes both uncommon abnormal and noise signals. Based on the Contest, we systematically assessed and analyzed a set of top-performing methods, most of which are deep neural networks, with both their commonalities and characteristics. This study establishes the benchmarks for computerized interpretation of 12-lead resting electrocardiogram and provides insights for the development of new methods.

Does the new-type urbanization construction improve the efficiency of agricultural green water utilization in the Yangtze River Economic Belt? - Xuhui Ding; Zhongyao Cai; Zhu Fu (Environmental Science and Pollution Research, 2021)

Effects of Food Deprivation Duration on the Behavior and Metabolism of Black Rockfish (Sebastes schlegelii) - Fengyuan Shen; Zonghang Zhang; Yiqiu Fu; Zhen Zhang; Xin Sun; Jianyu Dong; Xiayang Ding; Muyan Chen; Xiumei Zhang (Fishes, 2021)
Fish often undergo food shortages in nature, especially for juveniles that are relatively vulnerable in most aspects. Therefore, the effects of food deprivation on fish behavior and physiology are worth exploring. Here, we investigated the behavioral and metabolic adaptations of the juvenile black rockfish Sebastes schlegelii to different durations of food deprivation. In this study, three treatments were set: control group, short-term food deprivation (STFD) group, and long-term food deprivation (LTFD) group. The rearing lasted for six weeks. During this period, videos were recorded three times per week to assess the locomotor activity and aggression. After this, the fishes’ boldness, neophobia, and aggressiveness were assessed using different behavioral assessment devices, while the standard metabolic rate (SMR) was measured by flow-type respirometry. In general, the values of the four indicators (swimming time, the number of turns, movement number, and attack number) for the STFD group were significantly higher than those for the control and LTFD group during the same period of rearing. In a subsequent personality assessment, the STFD group was observed to be significantly bolder in an assessment measuring boldness than the control and LTFD group (indicated by time in the circle, swimming time, number of times through the circle, and frequency in the circle). The LTFD group was observed to be more exploratory in the assessment of neophobia (indicated by duration in the exploratory area, distance from novelty item, and frequency of stay in the exploratory area). Indeed, the LTFD group was observed to be significantly less aggressive in the assessment of aggressiveness than the control and STFD group (indicated by attack number, attack range frequency, first attack, and winner). SMR was noted to be significantly higher in the STFD group than in the control and LTFD group. In conclusion, this study firstly reported the effects of food deprivation duration on the personalities of black rockfish, as well as the behavioral and physiological mechanisms. Thus, we hope to provide insights into the work of stock enhancement.

miR-106b-5p upregulation is associated with microglial activation and inflammation in the mouse hippocampus following status epilepticus - Tao Yu; Hui Fu; Jing-Jing Sun; Dan-Rui Ding; Hua Wang (Experimental Brain Research, 2021)

Purification effect evaluation of the designed new volcanic soil adsorption material containing bioreactor for eutrophic water treatment - Huiling Fu; Linxian Ding; Jingyu Zhai; Xuesong Wang (Environmental Science and Pollution Research, 2021)

Ecological carrying capacity of alpine grassland in the Qinghai–Tibet Plateau based on the structural dynamics method - Yi-ping Fang; Fu-biao Zhu; Shu-hua Yi; Xiao-ping Qiu; Yong-jiang Ding (Environment, Development and Sustainability, 2021)

Individual variation in metabolic rate, locomotion capacity and hypoxia tolerance and their relationships in juveniles of three freshwater fish species - Xu Pang; De-Yong Pu; Dan-Yang Xia; Xiao-Hong Liu; Shi-Hua Ding; Yun Li; Shi-Jian Fu (Journal of Comparative Physiology B, 2021)

Ensemble machine learning to evaluate the in vivo acute oral toxicity and in vitro human acetylcholinesterase inhibitory activity of organophosphates - Liangliang Wang; Junjie Ding; Peichang Shi; Li Fu; Li Pan; Jiahao Tian; Dongsheng Cao; Hui Jiang; Xiaoqin Ding (Archives of Toxicology, 2021)

Laboratory investigation on calcium nitrate induced coupling reactions between nitrogen, phosphorus, sulfur, and metals in contaminated sediments - Juan Lin; Zhen Fu; Shiming Ding; Mingyin Ren; Shuaishuai Gao (Environmental Science and Pollution Research, 2021)

Molecular cloning, characterization and expression analysis of major histocompatibility complex class I alpha gene of pufferfish ( Takifugu obscurus ) - Shengli Fu; Haisu Liu; Yu Huang; Junru Wang; Kun Qian; Mingmei Ding; Jianmin Ye (Journal of Fish Diseases, 2021)
The major histocompatibility complex (MHC) genes play a key role in immune response in vertebrates. In this study, an MHC I alpha homolog gene ( PfMHC Ⅰα ) from pufferfish ( Takifugu obscurus ) was identified and its subcellular localization and expression patterns of PfMHC Ⅰα after challenge in vivo and in vitro were analysed. The open reading frame of PfMHC Ⅰα was 1,089 bp in length, encoding 362 aa. The immunofluorescence result revealed that PfMHC Ⅰα was presented on the membrane of lymphocytes. qRT‐PCR analysis indicated that PfMHC Ⅰα was expressed in all examined tissues, with the highest expression in skin, followed by the expression in gills and whole blood. After challenge of Aeromonas hydrophila or polyinosinic: polycytidylic acid (Poly I:C) in vitro, the expression levels of PfMHC Ⅰα on pufferfish kidney lymphocytes were significantly up‐regulated, with the highest expression level at 48 hr post‐challenge. After infection with A. hydrophila or Poly I:C in vivo, the expression levels of PfMHC Ⅰα in the skin, whole blood and kidneys were significantly up‐regulated. Taken together, it is speculated that PfMHC Ⅰα associates with resistance to both intracellular and extracellular antigens and plays an important role in the host response against pathogen infection in pufferfish.

The XGBoost and the SVM-based prediction models for bioretention cell decontamination effect - Xiaocheng Wang; DaFang Fu; Yajun Wang; Ying Guo; Yunfei Ding (Arabian Journal of Geosciences, 2021)

The study of changing characteristics of the winter temperature and extreme cold events in China over the past six decades - Dongxue Fu; Yihui Ding (International Journal of Climatology, 2021)
By using winter (December–February) daily temperature at 1629 meteorological stations over China during 1960/61‐2017/18, spatial–temporal changes and probability distribution characteristics of winter temperature and extreme cold events in China were analysed, with a special emphasis on the warming hiatus in China. The results are as follows: (1) the winter temperature in China showed an overall upward trend during the past six decades. However, since the winter of 2006 (so‐called the warming hiatus period), the winter temperature in China has remained stable and even decreased slightly. (2) There is an obvious difference in winter temperature between South China and North China. North China witnessed a more obvious temperature rise during the warm period (1986–2005) than South China did. However, since 2006, winter temperature in most parts of North China has dropped slightly, with a marked increase in extreme cold events. In contrast, South China did not undergo an obvious temperature drop during the hiatus period. (3) The range of temperature change in North China is larger than that in South China. The range of minimum temperature is also wider than that of maximum temperature, with a noticeable increase in extreme low temperature events since 2006. In such situation, North China is more likely to encounter extreme low temperature events, such as cold wave and low temperature weather. (4) China has experienced an increase in extreme cold events during the hiatus period. There is an obvious upward trend in regional long‐lasting extreme cold events (3–5 and 11–20 days duration). Consequently, this study has revealed that winter temperature and frequency of extreme cold events in China was not only influenced by global warming, with a persistent warming, but also showed an obvious inter‐decadal variation which is associated with the natural forcing. It indicates that the natural forcing factor is also a main factor influencing and modulating the winter temperature change at the inter‐decadal scale at the regional scale as China even in the era of the global warming caused by anthropogenic forcing.

Response of palladium in receiving water bodies to rainfall-runoff - Fangfang Ding; Yuyan Liu; Zucheng Wang; Caiye Ji; Dan Wu; Lin Wang; Bo Fu; Lan Zhang; Haofeng Liu (Environmental Science and Pollution Research, 2021)

Field tests of micro screw anchor piles under different loading conditions at three soil sites - Shi-Jin Feng; Wen-Ding Fu; Hong-Xin Chen; Hong-Xing Li; Yan-Li Xie; Shao-Feng Lv; Jin Li (Bulletin of Engineering Geology and the Environment, 2021)

The Role of Reward System in Dishonest Behavior: A Functional Near-Infrared Spectroscopy Study - Yibiao Liang; Genyue Fu; Runxin Yu; Yue Bi; Xiao Pan Ding (Brain Topography, 2021)

CARD9 Deficiency in a Chinese Man with Cutaneous Mucormycosis, Recurrent Deep Dermatophytosis and a Review of the Literature - Xiaopo Wang; Hui Ding; Zhiming Chen; Xuesi Zeng; Jianfang Sun; Hao Chen; Meihua Fu (Mycopathologia, 2020)

Identifying genes for resistant starch, slowly digestible starch, and rapidly digestible starch in rice using genome-wide association studies - Ning Zhang; Maike Wang; Ji Fu; Yi Shen; Yi Ding; Dianxing Wu; Xiaoli Shu; Wenjian Song (Genes & Genomics, 2020)

Transgenic merA and merB expression reduces mercury contamination in vegetables and grains grown in mercury-contaminated soil - Rui Li; Han Wu; Jing Ding; Nan Li; Weimin Fu; Lijun Gan; Yi Li (Plant Cell Reports, 2020)

An integrated system for rapid assessment of ecological quality based on remote sensing data - Qian Ding; Li Wang; Meichen Fu; Ni Huang (Environmental Science and Pollution Research, 2020)

Discrimination of geographical origin of camellia seed oils using electronic nose characteristics and chemometrics - Qi Peng; Qinxia Xu; Bealu Girma Dula; Jiazheng Wang; Jianwei Fu; Lan Wang; Bin Qian; Jiandi Zhou; Jianjiang Wu; Jiali Wang; Yinjun Ding (Journal of Consumer Protection and Food Safety, 2020)

Patients with radiation enteritis present regulatory T cell impairment associated with CTLA-4 - Xufeng Gong; Genhua Yu; Zongchang Song; Shuqi Huang; Yan Hou; Ning Wang; Wei Zhao; Jingjing Ouyang; Zhengzhou Gu; Haili Hu; Lei Fei; Aixia Fu; et al. (Immunologic Research, 2020)

Functional genetic variants in centrosome-related genes CEP72 and YWHAG confer susceptibility to gastric cancer - Jing Ni; Jinchen Wang; Yao Fu; Caiwang Yan; Meng Zhu; Yue Jiang; Jiaping Chen; Yanbing Ding; Xiangshan Fan; Gang Li; Guangfu Jin (Archives of Toxicology, 2020)

MiR-615 Regulates NSC Differentiation In Vitro and Contributes to Spinal Cord Injury Repair by Targeting LINGO-1 - Hongfu Wu; Lu Ding; Yuhui Wang; Tang-Bin Zou; Tao Wang; Wenjin Fu; Yong Lin; Xiaomin Zhang; Kangzhen Chen; Yutian Lei; Caitang Zhong; Chuanming Luo (Molecular Neurobiology, 2020)

Evoked-potential audiogram variability in a group of wild Yangtze finless porpoises (Neophocaena asiaeorientalis asiaeorientalis) - Zhi-Tao Wang; Jiao Li; Peng-Xiang Duan; Zhi-Gang Mei; Fu-Qiang Niu; Tomonari Akamatsu; Pei-Yu Lei; Lu Zhou; Jing Yuan; Yu-Wei Chen; Alexander Ya Supin; Ding Wang; et al. (Journal of Comparative Physiology A, 2020)

Numerical simulation study of strip filling for water-preserved coal mining - Wei Bo Sun; Yan Wang; Hua Fu Qiu; Zi Wei Ding (Environmental Science and Pollution Research, 2020)

Environmental policy, tax, and the target of sustainable development - Jie Yang; Mei-Lan Chen; Chung-Yuan Fu; Xi-Ding Chen (Environmental Science and Pollution Research, 2020)

Prolonged Neo-Tethyan magmatic arc in Myanmar: evidence from geochemistry and Sr–Nd–Hf isotopes of Cretaceous mafic–felsic intrusions in the Banmauk–Kawlin area - Jin-Xiang Li; Wei-Ming Fan; Li-Yun Zhang; Tou-Ping Peng; Ya-Li Sun; Lin Ding; Fu-Long Cai; Kyaing Sein (International Journal of Earth Sciences, 2020)

Reference Point Based Multi-Objective Optimization of Reservoir Operation: a Comparison of Three Algorithms - Rong Tang; Ke Li; Wei Ding; Yuntao Wang; Huicheng Zhou; Guangtao Fu (Water Resources Management, 2020)

Bone marrow mesenchymal stem cell-secreted exosomes carrying microRNA-125b protect against myocardial ischemia reperfusion injury via targeting SIRT7 - Qi Chen; Yu Liu; Xueyan Ding; Qinfeng Li; Fuyu Qiu; Meihui Wang; Zhida Shen; Hao Zheng; Guosheng Fu (Molecular and Cellular Biochemistry, 2020)
MicroRNA-125b (miR-125b) reduces myocardial infarct area and restrains myocardial ischemia reperfusion injury (I/R). In this study, we aimed to investigate the effect of bone marrow mesenchymal stem cell (BMSC)-derived exosomes carrying miR-125b on I/R rats. The myocardial I/R model in rats was constructed by ligation of the left anterior descending coronary artery (LAD). Rats were randomly divided into I/R and Sham group. Lv-cel-miR-67 (control) or Lv-miR-125b was transfected into BMSCs. Exosomes were extracted from transfected BMSCs, and separately named BMSC-Exo-67, BMSC-Exo-125b, and BMSC-Exo. MTT assay and flow cytometry were used to detect the viability and apoptosis of I/R myocardium cells, respectively. The expression of cell apoptosis proteins and the levels of inflammatory factors were examined by Western blot and ELISA assay, respectively. The target relationship between miR-125b and SIRT7 was predicted by using StarBase3.0, and was confirmed by using dual-luciferase reporter gene assay. qRT-PCR, immunohistochemistry staining, and Western blot were used to evaluate the expression of SIRT7 in myocardium tissues in I/R rats. BMSC-derived exosomes were successfully isolated and identified by TEM and positive expression of CD9 and CD63. The expression of miR-125b was down-regulated in I/R myocardium tissues and cells. BMSC-Exo-125b significantly up-regulated miR-125b in I/R myocardium cells. The intervention of BMSC-Exo-125b significantly increased the cell viability, decreased the apoptotic ratio, down-regulated Bax and caspase-3, up-regulated Bcl-2, and decreased the levels of IL-1β, IL-6, and TNF-α in I/R myocardium cells. SIRT7 was a target of miR-125b, and BMSC-Exo-125b significantly down-regulated SIRT7 in myocardium cells. In addition, the injection of BMSC-Exo-125b alleviated the pathological damages and down-regulated SIRT7 in myocardium tissues of I/R rats. BMSC-derived exosomes carrying miR-125b protected against myocardial I/R by targeting SIRT7.

The acclimation of leaf photosynthesis of wheat and rice to seasonal temperature changes in T‐FACE environments - Chuang Cai; Gang Li; Lijun Di; Yunjie Ding; Lin Fu; Xuanhe Guo; Paul C. Struik; Genxing Pan; Haozheng Li; Weiping Chen; Weihong Luo; Xinyou Yin (Global Change Biology, 2020)
Crops show considerable capacity to adjust their photosynthetic characteristics to seasonal changes in temperature. However, how photosynthesis acclimates to changes in seasonal temperature under future climate conditions has not been revealed. We measured leaf photosynthesis ( A n ) of wheat ( Triticum aestivum L.) and rice ( Oryza sativa L.) grown under four combinations of two levels of CO 2 (ambient and enriched up to 500 µmol/mol) and two levels of canopy temperature (ambient and increased by 1.5–2.0°C) in temperature by free‐air CO 2 enrichment (T‐FACE) systems. Parameters of a biochemical C 3 ‐photosynthesis model and of a stomatal conductance ( g s ) model were estimated for the four conditions and for several crop stages. Some biochemical parameters related to electron transport and most g s parameters showed acclimation to seasonal growth temperature in both crops. The acclimation response did not differ much between wheat and rice, nor among the four treatments of the T‐FACE systems, when the difference in the seasonal growth temperature was accounted for. The relationships between biochemical parameters and leaf nitrogen content were consistent across leaf ranks, developmental stages, and treatment conditions. The acclimation had a strong impact on g s model parameters: when parameter values of a particular stage were used, the model failed to correctly estimate g s values of other stages. Further analysis using the coupled g s –biochemical photosynthesis model showed that ignoring the acclimation effect did not result in critical errors in estimating leaf photosynthesis under future climate, as long as parameter values were measured or derived from data obtained before flowering.

De novo assembly, transcriptome characterization, and simple sequence repeat marker development in duckweed Lemna gibba - Lili Fu; Zehong Ding; Anuwat Kumpeangkeaw; Deguan Tan; Bingying Han; Xuepiao Sun; Jiaming Zhang (Physiology and Molecular Biology of Plants, 2020)

The response of reference evapotranspiration to climate change in Xinjiang, China: Historical changes, driving forces, and future projections - Qing Dong; Weiguang Wang; Quanxi Shao; Wanqiu Xing; Yimin Ding; Jianyu Fu (International Journal of Climatology, 2020)
Reference evapotranspiration (ET 0 ), which is an indicator of atmospheric evaporation demand over a hypothetical reference surface, is expected to alter along with global climate change. In this study, the changes and driving forces of historical ET 0 and its future projections in Xinjiang, China, were comprehensively conducted. The trend analysis revealed that regional ET 0 decreased significantly at a rate of −4.1 mm/year 2 during 1961–1993 and increased at a rate of 3.4 mm/year 2 during 1994–2010. To explore the possible causes, the contributions of major climatic variables to the ET 0 trends were derived based on the differential equation method. During 1961–1993, the decreasing trend of ET 0 was primarily ascribed to the wind speed. The integrated negative effect from the decrease in wind speed ( U ) and increase in relative humidity ( RH ) was more significant than the positive effect from the increase in air temperature ( T ), resulting in the decrease in ET 0 . During 1994–2010, combined with increasing T and decreasing RH , the increase in U offset the effect of the net radiation ( R n ) decrease and led to an increase in ET 0 . Future ET 0 projections over three periods (2010–2039, 2040–2069, and 2070–2099, which are named as 2020s, 2050s, and 2080s, respectively) were conducted based on the general circulation models under two representative concentration pathways scenarios (RCP4.5 and RCP8.5). A continuous increasing trend in ET 0 was demonstrated in the 21st century. The increase in ET 0 will increase the irrigated water resource consumption and bring new challenge to water resource management in this area.

Transport of uranium(VI) in red soil in South China: influence of initial pH and carbonate concentration - Haiying Fu; Dexin Ding; Yang Sui; Hui Zhang; Nan Hu; Feng Li; Zhongran Dai; Guangyue Li; Yongjun Ye; Yongdong Wang (Environmental Science and Pollution Research, 2019)

Characterization of the immunological factors in turbot (Scophthalmus maximus) seminal plasma and their correlation with sperm quality - Ming Ming Han; Fu Hong Ding; Jun Li (Aquaculture International, 2019)

Extracellular production of recombinant N-glycosylated anti-VEGFR2 monobody in leaky Escherichia coli strain - Ning Ding; Xin Fu; Yao Ruan; Jing Zhu; Pingping Guo; Lichi Han; Jianing Zhang; Xuejun Hu (Biotechnology Letters, 2019)

Neural Stem Cells Transfected with Leukemia Inhibitory Factor Promote Neuroprotection in a Rat Model of Cerebral Ischemia - Lili Tian; Wenli Zhu; Yuanchu Liu; Ye Gong; Aowei Lv; Zhen Wang; Xiaoli Ding; Shaowu Li; Ying Fu; Yi Lin; Yaping Yan (Neuroscience Bulletin, 2019)

Differentiation of the Agonists and Antagonists of the α7 Nicotinic Acetylcholine Receptor - Guanzhao Wu; Qingliang Xu; Yilei Bao; Yuwei Liu; Qian Li; Zhengyu Fang; Jingyi Fu; Yuhang Ding; Zhiqing Liang; Tao Jiang; Rilei Yu (Journal of Ocean University of China, 2019)

Extensive changes in gene expression and alternative splicing due to homoeologous exchange in rice segmental allopolyploids - Zhibin Zhang; Tiansi Fu; Zhijian Liu; Xutong Wang; Hongwei Xun; Guo Li; Baoxu Ding; Yuzhu Dong; Xiuyun Lin; Karen A. Sanguinet; Bao Liu; Ying Wu; et al. (Theoretical and Applied Genetics, 2019)

Transcriptome and hormone analyses provide insights into hormonal regulation in strawberry ripening - Tingting Gu; Shufen Jia; Xiaorong Huang; Lei Wang; Weimin Fu; Guotao Huo; Lijun Gan; Jing Ding; Yi Li (Planta, 2019)

Evolution Characteristics of Government-Industry-University Cooperative Innovation Network of Electronic Information Industry in Liaoning Province, China - Fei Peng; Qiqi Zhang; Zenglin Han; Yan Ding; Ningning Fu (Chinese Geographical Science, 2019)

Estimating the potential of energy saving and carbon emission mitigation of cassava-based fuel ethanol using life cycle assessment coupled with a biogeochemical process model - Dong Jiang; Mengmeng Hao; Jingying Fu; Guangjin Tian; Fangyu Ding (International Journal of Biometeorology, 2019)

Profiling of nuclear copper-binding proteins under hypoxic condition - Haiying Fu; Xueqin Ding; Wenjing Zhang; Y. James Kang (BioMetals, 2019)

Evaluating Soil Moisture Predictions Based on Ensemble Kalman Filter and SiB2 Model - Xiaolei Fu; Zhongbo Yu; Ying Tang; Yongjian Ding; Haishen Lyu; Baoqing Zhang; Xiaolei Jiang; Qin Ju (Journal of Meteorological Research, 2019)

Gene coexpression analysis reveals dose-dependent and type-specific networks responding to ionizing radiation in the aquatic model plant Lemna minor using public data - Lili Fu; Zehong Ding; Anuwat Kumpeangkeaw; Xuepiao Sun; Jiaming Zhang (Journal of Genetics, 2019)

Meteorological conditions during a severe, prolonged regional heavy air pollution episode in eastern China from December 2016 to January 2017 - Xueliang Deng; Weihua Cao; Yanfeng Huo; Guanying Yang; Caixia Yu; Dongyan He; Weitao Deng; Wei Fu; Heming Ding; Jing Zhai; Long Cheng; Xuhui Zhao (Theoretical and Applied Climatology, 2019)

Improving seed germination and oil contents by regulating the GDSL transcriptional level in Brassica napus - Li-Na Ding; Xiao-Juan Guo; Ming Li; Zheng-Li Fu; Su-Zhen Yan; Ke-Ming Zhu; Zheng Wang; Xiao-Li Tan (Plant Cell Reports, 2019)

Optimized back analysis method for stress determination based on identification of local stress measurements and its application - Qitao Pei; Xiuli Ding; Yuankun Liu; Bo Lu; Shuling Huang; Jing Fu (Bulletin of Engineering Geology and the Environment, 2019)

Role of permafrost in resilience of social-ecological system and its spatio-temporal dynamics in the source regions of Yangtze and Yellow Rivers - Yi-ping Fang; Fu-biao Zhu; Shu-hua Yi; Xiao-ping Qiu; Yong-jian Ding (Journal of Mountain Science, 2019)

A warming tropical central Pacific dries the lower stratosphere - Qinghua Ding; Qiang Fu (Climate Dynamics, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Long-term plastic film mulching and fertilization treatments changed the annual distribution of residual maize straw C in soil aggregates under field conditions: characterization by 13C tracing - Xinxin Jin; Tingting An; Aaron R. Gall; Shuangyi Li; Liangjie Sun; Jiubo Pei; Xiaodan Gao; Xuan He; Shifeng Fu; Xueli Ding; Jingkuan Wang (Journal of Soils and Sediments, 2018)

How do organ-specific metastases affect prognosis and surgical treatment for patients with metastatic upper tract urothelial carcinoma: first evidence from population based data - Fan Dong; Hangcheng Fu; Xiao Shi; Yifan Shen; Tianyuan Xu; Fengbin Gao; Xianjin Wang; Shan Zhong; Qiang Ding; Zhoujun Shen; Shanwen Chen (Clinical & Experimental Metastasis, 2017)

Complete plastid genomes of the genus Ammopiptanthus and identification of a novel 23-kb rearrangement - Lei Feng; Li-Fei Gu; Juan Luo; Ai-Si Fu; Qiong Ding; Siu-Ming Yiu; Jun-Xian He (Conservation Genetics Resources, 2017)

Bi-Level Optimization for Determining Operating Strategies for Inter-Basin Water Transfer-Supply Reservoirs - Xueping Zhu; Chi Zhang; Guangtao Fu; Yu Li; Wei Ding (Water Resources Management, 2017)

The Physicochemical Investigation of 17β-Estradiol Crystalline Prepared by In Situ pH-Dependent Solubility Technique with Polyvinylpyrrolidone - Hui Xiong; Jinping Fu; Hanjing Sun; Enfu Wang; Yunhui Ding; Guobin Ren; Qiufang Jing; Fuzheng Ren (AAPS PharmSciTech, 2017)

Brg1 inhibits E-cadherin expression in lung epithelial cells and disrupts epithelial integrity - Ting Wang; Wenjing Zou; Chao Niu; Fengxia Ding; Yaping Wang; Shuang Cai; Hua Zhu; Daiyin Tian; Jihong Dai; Enmei Liu; Qing Lu; Zhou Fu; et al. (Journal of Molecular Medicine, 2017)

Observation-based estimation of aerosol-induced reduction of planetary boundary layer height - Jun Zou; Jianning Sun; Aijun Ding; Minghuai Wang; Weidong Guo; Congbin Fu (Advances in Atmospheric Sciences, 2017)

Forest-type shift and subsequent intensive management affected soil organic carbon and microbial community in southeastern China - Xianghua Fang; Jinchi Zhang; Miaojing Meng; Xiaoping Guo; Yanwen Wu; Xin Liu; Keli Zhao; Lizhong Ding; Yangfeng Shao; Weijun Fu (European Journal of Forest Research, 2017)

Effects of starvation and feeding on blood chemistry, fatty acid composition and expression of vitellogenin and fatty acid-binding protein genes in female swimming crab Portunus trituberculatus broodstock - Liyun Ding; Huiyun Fu; Yingmei Hou; Min Jin; Peng Sun; Qicun Zhou (Fisheries Science, 2017)

Aerosol properties over an urban site in central East China derived from ground sun-photometer measurements - Qi Liu; WeiDong Ding; Lei Xie; JinQiang Zhang; Jun Zhu; XiangAo Xia; DongYang Liu; RenMin Yuan; YunFei Fu (Science China Earth Sciences, 2017)

Analysis of QTL for seed oil content in Brassica napus by association mapping and QTL mapping - Ying Fu; Dongqing Zhang; Madeleine Gleeson; Yaofeng Zhang; Baogang Lin; Shuijin Hua; Houdong Ding; Martin Frauen; Jiana Li; Wei Qian; Huasheng Yu (Euphytica, 2017)

Characterization, promoter analysis and expression of the interleukin-6 gene in blunt snout bream, Megalobrama amblycephala - Xiaoqin Fu; Zhujin Ding; Jun Fan; Huanling Wang; Fengjuan Zhou; Lei Cui; Chen Boxiang; Weimin Wang; Hong Liu (Fish Physiology and Biochemistry, 2016)

Dynamic behaviour of the CO2 bubble in a bubble column bioreactor for microalgal cultivation - Yu-Dong Ding; Sha Zhao; Xun Zhu; Qiang Liao; Qian Fu; Yun Huang (Clean Technologies and Environmental Policy, 2016)

Statistical downscaling of reference evapotranspiration in Haihe River Basin: applicability assessment and application to future projection - Wanqiu Xing; Weiguang Wang; Quanxi Shao; John Taylor; Yimin Ding; Jianyu Fu; Xiaozhou Feng (Hydrological Sciences Journal, 2016)

Endo-1,4-β-glucanase gene involved into the rapid elongation of Phyllostachys heterocycla var. pubescens - Ming-Bing Zhou; Ying Zheng; Zhi-Gang Liu; Xiang-Wan Xia; Ding-Qin Tang; Ying Fu; Ming Chen (Trees, 2016)

Silicon Alleviates Cadmium Toxicity in Two Cypress Varieties by Strengthening the Exodermis Tissues and Stimulating Phenolic Exudation of Roots - Bin Guo; Chen Liu; Nengfei Ding; Qinglin Fu; Yicheng Lin; Hua Li; Ningyu Li (Journal of Plant Growth Regulation, 2016)

Development of a quantitative PCR for detection and quantification of Prorocentrum donghaiense - Chun Yun Zhang; Guo Fu Chen; Jin Zhou; Yuan Yuan Wang; Dou Ding Lu (Journal of Applied Phycology, 2016)

Combinatorial enzymatic digestion with thermolysin and collagenase type I improved the isolation and culture effects of hair cell progenitors from rat cochleae - Yong-li Song; Ke-yong Tian; Wen-juan Mi; Peng Han; Zhong-jia Ding; Yang Qiu; Fu-quan Chen; Jian-jua Qiu (In Vitro Cellular & Developmental Biology - Animal, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

Environmental factors and phytohormones enhancing expression of α-momorcharin gene in Momordica charantia - Shuzhen Wang; Hongyuan Zhang; Yinzhen Zheng; Zhiliang Li; Fu Xiang; Yi Ding; Jun Xiang (Biologia, 2016)

The Impact of Small RNA Interference Against Homer1 on Rats with Type 2 Diabetes and ERK Phosphorylation - Jun Lu; Jihong Gan; Guoqiang Fu; Lu Ding; Qiangsun Zheng (Cell Biochemistry and Biophysics, 2015)

Treatment of Benign Prostatic Hyperplasia by Ultrasound-Guided Botulinum Toxin Type A Injection - Xu-Dong Ding; Huan-Xian Chen; Hong-Qiong Xiao; Wei Wang; Zhi-Gang Ding; Gui-Bin Zhang; Du-Guan Fu (Cell Biochemistry and Biophysics, 2015)

Single-nucleotide polymorphisms in CD8A and their associations with T lymphocyte subpopulations in pig - Wenwen Wang; Yang Liu; Weixuan Fu; Jingen Xu; Jianfeng Liu; Xiangdong Ding; Qin Zhang (Molecular Genetics and Genomics, 2015)

Chronic Metformin Preconditioning Provides Neuroprotection via Suppression of NF-κB-Mediated Inflammatory Pathway in Rats with Permanent Cerebral Ischemia - Xi-Chen Zhu; Teng Jiang; Qiao-Quan Zhang; Lei Cao; Meng-Shan Tan; Hui-Fu Wang; Zheng-Zheng Ding; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2015)

Analysis of methylation-sensitive amplified polymorphism in different cotton accessions under salt stress based on capillary electrophoresis - Baohua Wang; Rong Fu; Mi Zhang; Zhenqian Ding; Lei Chang; Xinyu Zhu; Yafeng Wang; Baoxiang Fan; Wuwei Ye; Youlu Yuan (Genes & Genomics, 2015)

Multiple Mesozoic magma processes formed the 240–185 Ma composite Weishan pluton, South China: evidence from geochronology, geochemistry, and Sr-Nd isotopes - Xing Ding; Wei-Dong Sun; Wei-Feng Chen; Pei-Rong Chen; Tao Sun; Sai-Jun Sun; Chiou-Ting Lin; Fu-Kun Chen (International Geology Review, 2015)

Biological Responses and Proteomic Changes in Maize Seedlings under Nitrogen Deficiency - Xining Jin; Weihua Li; Desheng Hu; Xia Shi; Xiaoxiang Zhang; Fangfang Zhang; Zhiyuan Fu; Dong Ding; Zonghua Liu; Jihua Tang (Plant Molecular Biology Reporter, 2015)

Two Different Emission-Wavelength Fluorescent Probes for Aluminum Ion based on Tunable Fluorophores in Aqueous Media - Yanxia Li; Zengchen Liu; Wenping Zhu; Hao Fu; Yongjie Ding; Jianping Xie; Weijie Yang; Lili Li; Chao Cheng (Journal of Fluorescence, 2015)

Investigating the molecular genetic basis of heterosis for internode expansion in maize by microRNA transcriptomic deep sequencing - Peng Zhao; Dong Ding; Fangfang Zhang; Xiaofeng Zhao; Yadong Xue; Weihua Li; Zhiyuan Fu; Haochuan Li; Jihua Tang (Functional & Integrative Genomics, 2015)

Direct interspecies electron transfer accelerates syntrophic oxidation of butyrate in paddy soil enrichments - Huijuan Li; Jiali Chang; Pengfei Liu; Li Fu; Dewen Ding; Yahai Lu (Environmental Microbiology, 2015)
Summary Syntrophic interaction occurs during anaerobic fermentation of organic substances forming methane as the final product. H 2 and formate are known to serve as the electron carriers in this process. Recently, it has been shown that direct interspecies electron transfer ( DIET ) occurs for syntrophic CH 4 production from ethanol and acetate. Here, we constructed paddy soil enrichments to determine the involvement of DIET in syntrophic butyrate oxidation and CH 4 production. The results showed that CH 4 production was significantly accelerated in the presence of nano Fe 3 O 4 in all continuous transfers. This acceleration increased with the increase of nano Fe 3 O 4 concentration but was dismissed when Fe 3 O 4 was coated with silica that insulated the mineral from electrical conduction. Nano Fe 3 O 4 particles were found closely attached to the cell surfaces of different morphology, thus bridging cell connections. Molecular approaches, including DNA ‐based stable isotope probing, revealed that the bacterial S yntrophomonadaceae and G eobacteraceae , and the archaeal M ethanosarcinaceae , M ethanocellales and M ethanobacteriales , were involved in the syntrophic butyrate oxidation and CH 4 production. Among them, the growth of G eobacteraceae strictly relied on the presence of nano Fe 3 O 4 and its electrical conductivity in particular. Other organisms, except M ethanobacteriales , were present in enrichments regardless of nano Fe 3 O 4 amendment. Collectively, our study demonstrated that the nano Fe 3 O 4 ‐facilitated DIET occurred in syntrophic CH 4 production from butyrate, and G eobacter species played the key role in this process in the paddy soil enrichments.

Optimized Preparation of a 99mTc-Radiolabeled Probe for Tracing MicroRNA - Lei Kang; Xiao-jie Xu; Chao Ma; Rong-fu Wang; Ping Yan; Chun-li Zhang; Hong-wei Sun; Ding Li (Cell Biochemistry and Biophysics, 2015)

Composition profiles of organic aerosols from Chinese residential cooking: case study in urban Guangzhou, south China - Xiuying Zhao; Qihou Hu; Xinming Wang; Xiang Ding; Quanfu He; Zhou Zhang; Ruqin Shen; Sujun Lü; Tengyu Liu; Xiaoxin Fu; Laiguo Chen (Journal of Atmospheric Chemistry, 2015)

Factors affecting spring bloom in the South of Cheju Island in the East China Sea - Dongyang Fu; Zhaojun Huang; Yuanzhi Zhang; Delu Pan; Youzhua Ding; Dazhao Liu; Ying Zhang; Zhihua Mao; Jianfang Chen (Acta Oceanologica Sinica, 2015)

Removal and Recovery of U(VI) from Low Concentration Radioactive Wastewater by Ethylenediamine-Modified Biomass of Aspergillus niger - De Xin Ding; Xin Xin; Le Li; Nan Hu; Guang Yue Li; Yong Dong Wang; Ping Kun Fu (Water, Air, & Soil Pollution, 2014)

Association of PPARγ gene polymorphisms with osteoarthritis in a southeast Chinese population - DING ZHERU; FU PEILIANG; WU YULI; WU HAISHAN; QIAN QIRONG; LI XIAOHUA; ZHAO HUI; WANG BO; FU QIWEI (Journal of Genetics, 2014)

Detecting Concealed Information Using Functional Near-Infrared Spectroscopy - Liyang Sai; Xiaomei Zhou; Xiao Pan Ding; Genyue Fu; Biao Sang (Brain Topography, 2014)

Conceptual study of lunar-based SAR for global change monitoring - HuaDong Guo; YiXing Ding; Guang Liu; DaoWei Zhang; WenXue Fu; Lu Zhang (Science China Earth Sciences, 2014)

Structure–activity relationships of anthocyanidin glycosylation - Chang Ling Zhao; Zhong Jian Chen; Xue Song Bai; Can Ding; Ting Ju Long; Fu Gang Wei; Kang Ru Miao (Molecular Diversity, 2014)

Co-delivery of Dexamethasone and Green Tea Polyphenols Using Electrospun Ultrafine Fibers for Effective Treatment of Keloid - Jinrong Li; Rong Fu; Long Li; Guang Yang; Shan Ding; Zhendong Zhong; Shaobing Zhou (Pharmaceutical Research, 2014)

CO2 mineral sequestration by wollastonite carbonation - Wenjin Ding; Liangjie Fu; Jing Ouyang; Huaming Yang (Physics and Chemistry of Minerals, 2014)

Magnesium Lithospermate B Reduces Inflammatory Response in a Mouse Model of Hepatic Ischemia–Reperfusion Injury - Shaohua Song; Wenyu Liu; Fang Liu; Zhengxin Wang; Guoshan Ding; Wenyuan Guo; Zhiren Fu (Cell Biochemistry and Biophysics, 2014)

Improved Insecticidal Toxicity by Fusing Cry1Ac of Bacillus thuringiensis with Av3 of Anemonia viridis - Fu Yan; Xing Cheng; Xuezhi Ding; Ting Yao; Hanna Chen; Wenping Li; Shengbiao Hu; Ziquan Yu; Yunjun Sun; Youming Zhang; Liqiu Xia (Current Microbiology, 2014)

Estrogen receptor α gene PvuII polymorphism and coronary artery disease: a meta-analysis of 21 studies - Jie Ding; Hui Xu; Xiang Yin; Fu-rong Zhang; Xiao-ping Pan; Yi-an Gu; Jun-zhu Chen; Xiao-gang Guo (Journal of Zhejiang University-SCIENCE B, 2014)

Epigallocatechin-3-gallate induces apoptosis, inhibits proliferation and decreases invasion of glioma cell - Hong Li; Zhe Li; Ya-Ming Xu; Yue Wu; Kang-Kang Yu; Can Zhang; Yong-Hua Ji; Gang Ding; Fu-Xue Chen (Neuroscience Bulletin, 2014)

Activation of mammalian target of rapamycin contributes to pain nociception induced in rats by BmK I, a sodium channel-specific modulator - Feng Jiang; Li-Ming Hua; Yun-Lu Jiao; Pin Ye; Jin Fu; Zhi-Jun Cheng; Gang Ding; Yong-Hua Ji (Neuroscience Bulletin, 2014)

Boletus roseoflavus, a new species of Boletus in section Appendiculati from China - Haibo Li; Hailong Wei; Huazheng Peng; Hongmei Ding; Liling Wang; Liang He; Lizhong Fu (Mycological Progress, 2014)

The secretion of organic acids is also regulated by factors other than aluminum - Haiyan Ding; Danni Wen; Zhengwei Fu; Haifeng Qian (Environmental Monitoring and Assessment, 2014)

Proteomic analysis of plumules and coleoptiles in maize between hybrids and their corresponding inbred lines - Xining Jin; Zhiyuan Fu; Dong Ding; Weihua Li; Zonghua Liu; Yanmin Hu; Jihua Tang (Acta Physiologiae Plantarum, 2014)

Two new dammarane-type glycosides from Phlomis umbrosa - Ming-Ming Ding; Fu-Lin Yan; Jing Tan; Yi-Xiao Bai; Xiang Wang; Yan-Xia Yang (Natural Product Research, 2014)

Hemoglobin-Induced Nitric Oxide Synthase Overexpression and Nitric Oxide Production Contribute to Blood–Brain Barrier Disruption in the Rat - Shuo Yang; Yizhao Chen; Xinqing Deng; Weiping Jiang; Bing Li; Zhenghao Fu; Mouxuan Du; Rui Ding (Journal of Molecular Neuroscience, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Effects of nitric oxide on the germination of cucumber seeds and antioxidant enzymes under salinity stress - Huai-Fu Fan; Chang-Xia Du; Ling Ding; Yan-Li Xu (Acta Physiologiae Plantarum, 2013)

Bird species migration ratio in East Asia, Australia, and surrounding islands - Yiliang Kuo; Da-Li Lin; Fu-Man Chuang; Pei-Fen Lee; Tzung-Su Ding (The Science of Nature, 2013)

An integrated East China Sea–Changjiang Estuary model system with aim at resolving multi-scale regional–shelf–estuarine dynamics - Jianzhong Ge; Pingxing Ding; Changsheng Chen; Song Hu; Gui Fu; Lunyu Wu (Ocean Dynamics, 2013)

Development of rRNA-targeted probes for detection of Prorocentrum micans (Dinophyceae) using whole cell in situ hybridization - Guo Fu Chen; Yang Liu; Chun Yun Zhang; Chao Shuai Ma; Bao Yu Zhang; Guang Ce Wang; Zhong Xu; Dou Ding Lu (Journal of Applied Phycology, 2013)

Fluid inclusion analysis for constraining the hydrocarbon accumulation periods of the Permian reservoirs in Northeast Ordos Basin - Gang Chen; Shuheng Li; Huiruo Zhang; Fu Yang; Chao Ding; Panpan Lei; Yanxu Hu (Journal of Earth Science, 2013)

Interstitial cells of Cajal mediate excitatory sympathetic neurotransmission in guinea pig prostate - Jiang-ping Wang; Guo-fu Ding; Qin-zhang Wang (Cell and Tissue Research, 2013)

Investigation of the relationship between chromobox homolog 8 and nucleus pulposus cells degeneration in rat intervertebral disc - Xu Zhou; Hai-Long Zhang; Guang-Fei Gu; Yue Ding; Jian-Bo Jia; Qing-Song Fu; Shi-Sheng He (In Vitro Cellular & Developmental Biology - Animal, 2013)

Knockdown of dishevelled-1 attenuates cyclosporine A-induced apoptosis in H9c2 cardiomyoblast cells - Yejing Zhu; Jinyu Chi; Yue Liu; Yihua Sun; Yu Fu; Xiaohui Zhang; Xueliang Ding; Xinhua Yin; Dechao Zhao (Molecular and Cellular Biochemistry, 2013)

Comparative transcriptome analysis of tobacco (Nicotiana tabacum) leaves to identify aroma compound-related genes expressed in different cultivated regions - Bo Lei; Xue-Hua Zhao; Kai Zhang; Jie Zhang; Wei Ren; Zhu Ren; Yi Chen; Hui-Na Zhao; Wen-Jie Pan; Wei Chen; Hong-Xun Li; Wen-Ya Deng; et al. (Molecular Biology Reports, 2013)

Arsenic accumulation and distribution in the tissues of inbred lines in maize (Zea mays L.) - Z. H. Liu; W. H. Li; H. Y. Qi; G. L. Song; D. Ding; Z. Y. Fu; J. B. Liu; J. H. Tang (Genetic Resources and Crop Evolution, 2012)

The nuclear translocation of endostatin is mediated by its receptor nucleolin in endothelial cells - Nan Song; Yanping Ding; Wei Zhuo; Ting He; Zhiguang Fu; Yang Chen; Xiaomin Song; Yan Fu; Yongzhang Luo (Angiogenesis, 2012)

The impact of E-cadherin expression on non-small cell lung cancer survival: a meta-analysis - Ying Wu; Hong-Bing Liu; Ming Ding; Jian-Nan Liu; Ping Zhan; Xiao-Su Fu; Gan Lu (Molecular Biology Reports, 2012)

Reduction of the thermocline feedback associated with mean SST bias in ENSO simulation - Baoqiang Xiang; Bin Wang; Qinghua Ding; Fei–Fei Jin; Xiouhua Fu; Hyung-Jin Kim (Climate Dynamics, 2012)

Progress in the study of nonlinear atmospheric dynamics and predictability of weather and climate in China (2007–2011) - Feifan Zhou; Ruiqiang Ding; Guolin Feng; Zuntao Fu; Wansuo Duan (Advances in Atmospheric Sciences, 2012)

Ouabain-Induced Cochlear Degeneration in Rat - Yong Fu; Dalian Ding; Haiyan Jiang; Richard Salvi (Neurotoxicity Research, 2012)

Soil microbial communities and enzyme activities in a reclaimed coastal soil chronosequence under rice–barley cropping - Qinglin Fu; Chen Liu; Nengfei Ding; Yicheng Lin; Bin Guo; Jiafa Luo; Hailong Wang (Journal of Soils and Sediments, 2012)

Sphingosine 1-phosphate acts as an activator for the porcine Gpr3 of constitutively active G protein-coupled receptors - Bao-le Zhang; Ye Li; Jian-hua Ding; Fu-lu Dong; Yan-jun Hou; Bao-chun Jiang; Fang-xiong Shi; Yin-xue Xu (Journal of Zhejiang University-SCIENCE B, 2012)

Comparative Screening of K-ras Mutations in Colorectal Cancer and Lung Cancer Patients Using a Novel Real-Time PCR with ADx-K-ras Kit and Sanger DNA Sequencing - Haiping Zhang; Xiongwei Zheng; Tianhai Ji; Li Fu; Dongyu Bai; Yongqiang Liao; Haifang Zhang; Yi Ding; Limou Zheng (Cell Biochemistry and Biophysics, 2012)

The monitoring results of electromagnetic radiation of 110-kV high-voltage lines in one urban location in Chongqing P.R. China - Qi-zhong Qin; Yu Chen; Ting-ting Fu; Li Ding; Ling-li Han; Jian-chao Li (Environmental Monitoring and Assessment, 2012)

Speciation in the Rana chensinensis species complex and its relationship to the uplift of the Qinghai–Tibetan Plateau - WEI‐WEI ZHOU; YANG WEN; JINZHONG FU; YONG‐BIAO XU; JIE‐QIONG JIN; LI DING; MI‐SOOK MIN; JING CHE; YA‐PING ZHANG (Molecular Ecology, 2012)
Speciation remains a fundamental issue in biology. Herein, we report an investigation into speciation in the Rana chensinensis species complex using DNA sequence data from one mitochondrial and five nuclear genes. A phylogenetic analysis of the data revealed four major clades in the complex, and each of them was found to likely represent a species, including one cryptic species. Ecological niche models were generated from 19 climatic variables for three of the four major clades, which were represented by widespread sampling, including R. chensinensis , Rana kukunoris and the potential cryptic species. Each clade is associated with a unique ecological unit, and this indicates that ecological divergence probably drove speciation. Ecological divergence is likely related to the late Cenozoic orogenesis of the Qinghai–Tibetan Plateau. In addition, gene flow between species was detected but only in peripheral portions of the ranges of the four major clades, thus likely had little influence on the speciation processes. Discordances between mitochondrial and nuclear genes were also found; the nominal species, R. chensinensis , contains multiple maternal clades, suggesting potential mitochondrial introgression between R. chensinensis and R. kukunoris .

Positive feedback between acidification and organic phosphate mineralization in the rhizosphere of maize (Zea mays L.) - Xiaodong Ding; Li Fu; Chenjia Liu; Fanjun Chen; Ellis Hoffland; Jianbo Shen; Fusuo Zhang; Gu Feng (Plant and Soil, 2011)

Erratum to: Co-administration of Cisplatin and Furosemide Causes Rapid and Massive Loss of Cochlear Hair Cells in Mice - Yongqi Li; Dalian Ding; Haiyan Jiang; Yong Fu; Richard Salvi (Neurotoxicity Research, 2011)

Co-administration of Cisplatin and Furosemide Causes Rapid and Massive Loss of Cochlear Hair Cells in Mice - Yongqi Li; Dalian Ding; Haiyan Jiang; Yong Fu; Richard Salvi (Neurotoxicity Research, 2011)

Noradrenaline regulates substance P release from rat dorsal root ganglion neurons in vitro - Yan-Jie Wang; Xing-Fu Li; Feng Ding; Qiang Shu; Li-Jun Song; Xiao Yu; Hua-Xiang Liu (Neuroscience Bulletin, 2011)

Resveratrol attenuates apoptosis of pulmonary microvascular endothelial cells induced by high shear stress and proinflammatory factors - Liang Xia; Fang Ding; Jun-Hui Zhu; Guo-Sheng Fu (Human Cell, 2011)

Assessing adaptability of planted trees using leaf traits: A case study with Robinia pseudoacacia L. in the Loess Plateau, China - Tiantian Jin; Guohua Liu; Bojie Fu; Xiaohui Ding; Lei Yang (Chinese Geographical Science, 2011)

COD removal from expanded granular sludge bed effluent using a moving bed biofilm reactor and their microbial community analysis - Bo Fu; Xiaoyi Liao; Rui Liang; Lili Ding; Ke Xu; Hongqiang Ren (World Journal of Microbiology and Biotechnology, 2011)

PaPTP1, a Gene Encoding Protein Tyrosine Phosphatase from Orchid, Phalaenopsis amabilis, is Regulated During Floral Development and Induced by Wounding - Shih-Feng Fu; Chung-Wen Lin; Tien-Wen Kao; Dinq-Ding Huang; Hao-Jen Huang (Plant Molecular Biology Reporter, 2011)

Characterization of microbial community in an aerobic moving bed biofilm reactor applied for simultaneous nitrification and denitrification - Bo Fu; Xiaoyi Liao; Lili Ding; Hongqiang Ren (World Journal of Microbiology and Biotechnology, 2010)

Osteogenic role of endosomal chloride channels in MC3T3-E1 cells - Huan Wang; Na Huo; Feifei Li; Shanmin Fu; Yang Xue; Ting Yang; Xuan Wen; Yin Ding; Xiaohong Duan (Molecular and Cellular Biochemistry, 2010)

Erratum to: Early administration of propofol protects against endotoxin-induced acute lung injury in rats by inhibiting the TGF-β1-Smad2 dependent pathway - Ju Gao; Wei-Xian Zhao; Fu-Shan Xue; Luo-Jing Zhou; Shao-qun Xu; Ning Ding (Inflammation Research, 2010)

Early administration of propofol protects against endotoxin-induced acute lung injury in rats by inhibiting the TGF-β1-Smad2 dependent pathway - Ju Gao; Wei-Xian Zhao; Fu-Shan Xue; Luo-Jing Zhou; Shao-qun Xu; Ning Ding (Inflammation Research, 2010)

Photolytical property of L(+)-α-phenylglycine in aqueous solution - Minghong Wu; Wenyan Shi; Haijiao Zhang; Zheng Jiao; Jie Chen; Side Yao; Guoji Ding; Jiamo Fu (Environmental Chemistry Letters, 2010)

Pancreas-specific protein disulfide isomerase has a cell type-specific expression in various mouse tissues and is absent in human pancreatic adenocarcinoma cells: implications for its functions - Xin-Miao Fu; Xiangchen Dai; Jian Ding; Bao Ting Zhu (Journal of Molecular Histology, 2009)

Short hairpin RNA targeting NP mRNA inhibiting Newcastle disease virus production and other viral structural mRNA transcription - Hua Yue; Shu Deng; Fa-long Yang; Ding-fei Li; An-jing Fu; Fan Yang; Cheng Tang (Virus Genes, 2009)

Nonlinear cooperation of p53-ING1-induced bax expression and protein S-nitrosylation in GSNO-induced thymocyte apoptosis: a quantitative approach with cross-platform validation - Shaojin Duan; Lin Wan; Wenjiang J. Fu; Hong Pan; Qi Ding; Chang Chen; Peiwei Han; Xiaoyan Zhu; Liying Du; Hongxiao Liu; Yuxia Chen; Ximing Liu; et al. (Apoptosis, 2009)

Extensive population expansion of Pedicularis longiflora (Orobanchaceae) on the Qinghai‐Tibetan Plateau and its correlation with the Quaternary climate change - FU‐SHENG YANG; YU‐FEI LI; XIN DING; XIAO‐QUAN WANG (Molecular Ecology, 2008)
The Qinghai‐Tibetan Plateau (QTP) is thought to be more strongly affected by the Quaternary glaciations than most other regions of the same latitude. It would be of great interest to investigate the population genetic structure of organisms distributed on the platform and its correlation with the Quaternary climatic oscillations. Here we used the chloroplast (cp)DNA trn T‐ trn F sequence to study genetic variation and phylogeography of Pedicularis longiflora , an alpine herb with extensive distribution on the QTP. Based on a range‐wide sampling comprising 41 populations and 910 individuals, we detected 30 cpDNA haplotypes that were divided into five clades by phylogenetic and network analyses and a strong phylogeographical structure. All haplotypes but one in the three basal clades occur exclusively in the southeast QTP, whereas haplotypes in the young clade V occupy almost the whole species range. In particular, the young haplotype H18 occurs in 420 individuals, even at a frequency of 100% in some QTP platform populations and the Altai population. The haplotype distribution pattern, together with molecular clock estimation and mismatch distribution analysis, suggests that the southeast QTP was either a refuge for P . longiflora during the Quaternary climatic change or is the place of origin of the species. The present wide distribution of the species on the QTP platform has resulted from recent population expansions which could be dated back to 120 000–17 000 years ago, a period mostly before the last glacial maximum. The possible relationships among geographic genetic structure, climatic change and species diversification in Pedicularis are also discussed.

Genome sequence and characterization of a new virus infecting Mikania micrantha H.B.K. - Rui-Long Wang; Ling-Wen Ding; Qiao-Yang Sun; Jing Li; Zeng-Fu Xu; Shao-Lin Peng (Archives of Virology, 2008)

Molecular cloning and characterization of two novel cellulase genes from the mollusc Ampullaria crossean - Rui Guo; Ming Ding; Si-Liang Zhang; Gen-jun Xu; Fu-kun Zhao (Journal of Comparative Physiology B, 2008)

Purification and characterization of a psychrophilic glutathione reductase from Antarctic ice microalgae Chlamydomonas sp. Strain ICE-L - Yu Ding; Jin-Lai Miao; Quan-Fu Wang; Zhou Zheng; Guang-You Li; Ji-Chang Jian; Zao-He Wu (Polar Biology, 2007)

Nonlinear atmospheric and climate dynamics in China (2003–2006): A review - Ruiqiang Ding; Guolin Feng; Shida Liu; Shikuo Liu; Sixun Huang; Zuntao Fu (Advances in Atmospheric Sciences, 2007)

Edaravone neuroprotection effected by suppressing the gene expression of the Fas signal pathway following transient focal ischemia in rats - Bo Xiao; Fang -Fang Bi; Yue -Qiang Hu; Fa -Fa Tian; Zhi -Guo Wu; Hadi M. Mujlli; Ling Ding; Xin -Fu Zhou (Neurotoxicity Research, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Sustainability Evaluation of the Grain for Green Project: From Local People’s Responses to Ecological Effectiveness in Wolong Nature Reserve - Jian-Ying Xu; Li-Ding Chen; Yi-He Lu; Bo-Jie Fu (Environmental Management, 2007)

Geochemical evidence for the variation of historical seabird population on Dongdao Island of the South China Sea - X. D. Liu; S. P. Zhao; L. G. Sun; H. H. Luo; X. B. Yin; Z. Q. Xie; Y. H. Wang; K. X. Liu; X. H. Wu; X. F. Ding; D. P. Fu (Journal of Paleolimnology, 2006)

Biological control of invasive plants through collaboration between China and the United States of America: a perspective - Jianqing Ding; Richard Reardon; Yun Wu; Hao Zheng; Weidong Fu (Biological Invasions, 2006)

Expression of CspA and GST by an Antarctic psychrophilic bacterium Colwellia sp. NJ341 at near-freezing temperature - Quan-Fu Wang; Jin-Lai Miao; Yan-Hua Hou; Yu Ding; Guang-You Li (World Journal of Microbiology and Biotechnology, 2006)

Purification and Characterization of an Extracellular Cold-Active Serine Protease from the Psychrophilic Bacterium Colwellia sp. NJ341 - Quan-Fu Wang; Jin-Lai Miao; Yan-Hua Hou; Yu Ding; Guo-Dong Wang; Guang-You Li (Biotechnology Letters, 2005)

Identification of cry-Type Genes on 20-kb DNA Associated with Cry1 Crystal Proteins from Bacillus thuringiensis - Liqiu Xia; Yunjun Sun; Xuezhi Ding; Zujiao Fu; Xiangtao Mo; He Zhang; Zhiming Yuan (Current Microbiology, 2005)

Eco-hydrological effects of landscape pattern change - Bo-Jie Fu; Wen-Wu Zhao; Li-Ding Chen; Zhan-Feng Liu; Yi-He Lü (Landscape and Ecological Engineering, 2005)

Specific amino acid restriction inhibits attachment and spreading of human melanoma via modulation of the integrin/focal adhesion kinase pathway and actin cytoskeleton remodeling - Ya-Min Fu; Hui Zhang; Mingjie Ding; Yi-Qi Li; Xing Fu; Zu-Xi Yu; Gary G. Meadows (Clinical & Experimental Metastasis, 2005)

Cardiovascular effects of agmatine within the rostral ventrolateral medulla are similar to those of clonidine in anesthetized rats - Jun Yang; Wei-Zhong Wang; Fu-Ming Shen; Ding-Feng Su (Experimental Brain Research, 2005)

Effective induction of immune tolerance by portal venous infusion with IL-10 gene-modified immature dendritic cells leading to prolongation of allograft survival - Ming Zhang; Quanxing Wang; Yushan Liu; Yanping Sun; Guoshan Ding; Zhiren Fu; Zhilian Min; Youhua Zhu; Xuetao Cao (Journal of Molecular Medicine, 2004)

Breeding bird species richness in Taiwan: distribution on gradients of elevation, primary productivity and urbanization - Pei‐Fen Lee; Tzung‐Su Ding; Fu‐Hsiung Hsu; Shu Geng (Journal of Biogeography, 2004)
Aim To examine the richness of breeding bird species in relation to elevation, primary productivity and urbanization. Location The island of Taiwan (120°–122° E, 22°–25° N). Methods We arranged bird species richness (BSR) data from 288 bird censuses undertaken in Taiwan into a 2 × 2 km quadrat system and calculated average values of elevation, primary productivity [surrogated by normalized difference vegetation index (NDVI)], and urbanization (surrogated by road density and percentage of built area) for each 2 × 2 km quadrat. Results Bird species richness showed a hump‐shaped relationship with elevation. It increased with elevation from sea level (10–64 species per 2 × 2 km quadrat), peaked around 2000 m (43–76 species), and then decreased with elevation towards its minimum at the highest elevation. Road density and percentage of built area decreased with elevation, and NDVI showed a hump‐shaped relationship with elevation and inverse relationships with road density and percentage of built area. BSR increased with NDVI and decreased with road density and percentage of built area. Linear and cubic terms of elevation together explained 31.3% of the variance in BSR, and road density explained additional 3.4%. The explanatory power of NDVI on BSR was insignificant after the effects of elevation and road density had been justified. Main conclusions We argue that urbanization plays an important role in the BSR of Taiwan. Urbanization might indirectly decrease BSR through decreasing primary productivity and therefore change the hypothetical inverse relationship between BSR and elevation into a hump‐shaped relationship. We also propose a time hypothesis that the biotic communities in the mid‐elevation zone of Taiwan had relatively longer periods of existence during the Pleistocene glacial cycles, which might be one underlying process of the observed hump‐shaped relationship between species diversity and elevation.

Use of oligonucleotide fingerprinting and faecal DNA in identifying the distribution of the Chinese tiger (Panthera tigris amoyensis Hilzheimer) - Qiu-Hong Wan; Sheng-Guo Fang; Guo-Fu Chen; Zhang-Ming Wang; Ping Ding; Mu-Yuan Zhu; Kong-Shou Chen; Jiu-Hua Yu; Yue-Ping Zhao (Biodiversity and Conservation, 2003)

New Method to Obtain Ultrasonic Angle Independent Doppler Color Images Using a Sector Transducer - Ding-Yu Fei; Cai-Ting Fu (Annals of Biomedical Engineering, 1999)

Study of the structure of a monsoon depression over the Bay of Bengal during Summer MONEX - Yihui Ding; Xiuqin Fu; Baoyan Zhang (Advances in Atmospheric Sciences, 1984)